Synthesis of a calcium alginate hydrogel-modified phosphorus-enriched Douglas fir biochar controlled-release fertilizer - Hashani P. Abeysinghe; Olalekan Olabode; Jac J. Varco; Praveen Gajula; Prashan M. Rodrigo; Amanda J. Kaplan; Kacy Crothers; Abdul Raheem Azeezat; Daniel O. Oguntuyi; Charles U. Pittman; Todd E. Mlsna (Biomass and Bioenergy, 2026)

New plesiosaur from the uppermost Cretaceous of Patagonia sheds light on thoracic and caudal anatomy in plesiosaurs - Fernando E. Novas; Julia D'Angelo; Federico Agnolín; Rodrigo Otero; Jordi Garcia Marsà; Silvio Casadio; Kenneth Lacovara; Marcelo Isasi (Cretaceous Research, 2026)

Genesis of bedding-parallel gypsum veins (beef) in a tectonically relaxed basin: Insights from the Malargüe Group (Cretaceous-Paleogene), Neuquén Basin, Argentina - Rodrigo J. Suárez; Gerson A. Greco; Santiago N. González; Raúl E. Giacosa (Journal of South American Earth Sciences, 2026)

Lianas and trees 30-years after liana cutting and selective logging in the Amazon - Vitoria Duarte Derisso; Maria Tereza Grombone-Guaratini; Francis E. Putz; Rodrigo Costa Pinto; Iran Paz Pires; Edson Vidal (Forest Ecology and Management, 2026)

Connectivity and phylogenetic diversity of a fish metacommunity in subtropical coastal lakes - Otávio Gutierrez e Silva; Rodrigo Barbosa Fontana; Taís de Fátima Ramos Guimarães; Fernando Gertum Becker; Sandra Maria Hartz (Hydrobiologia, 2026)
Neotropical freshwater biodiversity is remarkable, mainly due to historical, biotic, and environmental processes. Landscape connectivity can promote or restrict species dispersal in fish metacommunities, thereby influencing the diversity and phylogenetic structure of communities. This study evaluated whether structural landscape variables of the Tramandaí River basin affect the phylogenetic diversity of the component communities of a fish metacommunity. The variables considered were primary and estuarine connection, lake shape and area, and distance from the sea. Phylogenetic diversity was estimated using a time-calibrated fish phylogeny and multiple phylogenetic diversity metrics, while the relationships between landscape variables and each metric were assessed using path analysis. The distribution of phylogenetic lineages across lakes was examined using Principal Coordinates of Phylogenetic Structure. The results revealed a negative effect of primary connection on the Nearest Relative Index and a negative effect of distance from the sea on the Nearest Taxon Index, as well as phylogenetic structuring associated with more isolated lakes and greater saline influence. The results highlight the importance of connectivity and distance from the sea in shaping the phylogenetic organization of fish metacommunities in the Tramandaí River basin, contributing to a better understanding of the processes that structure diversity in Neotropical coastal systems.

Jaguar Range‐Wide Connectivity: Prioritising Core Areas and Corridors Between and Within Protected Areas and Indigenous Lands - Guilherme Costa Alvarenga; Caroline C. Sartor; Ana Carolina Srbek‐Araujo; Ana Cristina Mendes‐Oliveira; Bart Harmsen; Carlos De Angelo; Carolina Franco Esteves; Claudia Bueno de Campos; Daiana Jeronimo Polli; Diego F. Passos Viana; Diogo Maia Gräbin; Emiliano Donadio; et al. (Global Change Biology, 2026)
Anthropogenic habitat transformation has led to population declines and increasing isolation of populations of many species, particularly top predators, where small and fragmented populations often experience limited dispersal and reduced genetic diversity. Jaguars ( Panthera onca ), for example, have lost half of their historical range and most populations outside the Amazon biome are small, isolated and highly threatened. Here, we assess jaguar population connectivity across the species' range by identifying and ranking core areas and dispersal corridors, including linkages among Protected Areas and Indigenous Lands (hereafter, PAs). We used cumulative resistant kernels and factorial Least‐Cost Paths (fLCP) in two complementary approaches: core area‐based and PA‐based connectivity. We identified 307 core areas for jaguar movement, covering ~7.75 million km 2 (55% of the current range), of which approximately half lies within PAs. The largest and highest‐ranked core area spans ~6.5 million km 2 across four biomes (Amazon, Llanos, Chaco and Pantanal). We identified 176 dispersal corridors connecting core areas, although connectivity was not continuous across the entire range. Northern populations (Mexico and Central America) showed several connectivity gaps, whereas South America displayed a large, highly interconnected network linking the Amazon, Llanos, Chaco, Pantanal, Cerrado, Caatinga, Iberá and the Atlantic Forest's Green Corridor. In contrast, coastal Atlantic Forest patches appeared largely isolated. The PA‐based analysis predicted 507 potential corridors connecting 905 PAs, including potential links absent from the core area model, particularly across Central America and between the Darién Gap, Amazon and coastal Atlantic Forest. The core‐area approach provides a more biologically realistic representation of current connectivity, while the PA‐based approach complements it by identifying pragmatic opportunities for long‐term connectivity conservation. Together, these approaches identify priority areas and regions of uncertainty, providing a spatial framework to guide jaguar conservation and connectivity planning under accelerating global change.

Oat vs. corn grain for finishing Merino Dohne lambs: Intake stability, growth performance, and meat quality during wet-aging - María Sol Villaverde; Ethel E. Pérez; Hugo M. Arelovich; Mariano Menghini; Rodrigo D. Bravo; Marcela F. Martínez (Small Ruminant Research, 2026)

Seed desiccation tolerance and conservation of sapucaia, an emerging functional Brazil nut tree from the Atlantic and Amazon forest biomes - Caroline Palacio de Araujo; Ingridh Medeiros Simões; Joana Silva Costa; Taísa de Fátima Rodrigues de Almeida; Débora Pellanda Fagundes; Eduardo Santos Cade; Emanuel Bizareli de Moraes; Jéssica Batista Ribeiro e Oliveira; Edilson Romais Schmildt; José Eduardo Macedo Pezzopane; José Carlos Lopes; Heloisa Oliveira dos Santos; et al. (Journal of Stored Products Research, 2026)

Climate-driven regime shift associated with range contraction at warm range edge of Macrocystis pyrifera forests - Marisol Atela; Jeremie Bauer; Rodrigo Beas-Luna; Alicia Abadía-Cardoso; Mark H. Carr; Dillon Dolinar; Matthew S. Edwards; Luis Malpica-Cruz; Nemer E. Narchi; Kyle Cavanaugh; Julio Lorda (Marine Biology, 2026)

A Design and Life Cycle Assessment Framework for Electrochemical Ozone-based Indoor Air Treatment in Hospitals - V. Pertegal; S. E. Correia; A. Rodríguez-Gómez; C. M. Fernández-Marchante; M. A. Rodrigo; C. Sáez; E. Lacasa (Environmental Processes, 2026)

A mechanistic approach about oxidative, mutagenic, and cytotoxic effects of an organotellurane - Felipe Emannuel Alvino de Jesus; Octávio Augusto de Carvalho Maia; Antonielly Campinho dos Reis; Audinei de Sousa Moura; Anderson Nogueira Mendes; Glissia Lysandra dos Santos Marciel; Jefferson da Cruz Esteves; Shamya Gabriella Corrêa Coêlho; Isabela Ribeiro de Sá Guimarães Nolêto; Maria Luísa Lima Barreto do Nascimento; Adriana Maria Viana Nunes; Débora Caroline do Nascimento Rodrigues; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Organotellurium (OTe) compounds have pharmacological properties, including leishmanicidal, antimalarial, and antifungal activities. Herein, we assessed cytotoxicity effects of OTe RF07 in a panel of tumor cell lines, as well as its oxidative, toxicity, and hemolytic actions. The toxicity was evaluated on Allium cepa and Artemia salina larvae. Cell viability was also assessed by resazurin in murine cells (Sarcoma 180), human cells (HL-60, leukemia; AGP01, gastric adenocarcinoma; SKMEL-28, human melanoma; MRC-5, normal fibroblasts), and dog erythrocytes. The oxidative capacity of RF07 was evaluated by wild-type and antioxidant-mutated enzyme strains of Saccharomyces cerevisiae . RF07 presented cytotoxic action on all normal and tumor cells, whose IC 50 ranged from 0.07 μg/mL (HL-60) to 73.45 μg/mL (Sarcoma 180) and toxicological activity on A. salina nauplii in a concentration-dependent manner after exposure for 24 h and 48 h (LC 50 values of 15.02 and 5.43 μg/mL for 24 h and 48 h, respectively). Moreover, RF07 reduced mitotic index of meristematic A. cepa cells at 5, 10 and 20 μg/mL, caused arrest in interphase, and increased chromosomal changes, including micronucleus, c -metaphases, and chromosomal bridges, loss, and delays. In summary, RF07 exhibits antiproliferative action on animal cells, high toxicity on Artemia salina nauplii, as well as clastogenic effects on growing roots. This antimitotic action is not related to direct membrane damage, although it relies on chromosomal injuries and may be related to the induction of oxidative stress as observed in yeast cells.

Abscisic Acid Modulates Physiological and Proteomic Changes During Histodifferentiation and Germination of Somatic Embryos in Euterpe edulis - Débora Pellanda Fagundes; Joana Silva Costa; Jociel Nascimento de Noronha; Mateus Santana Rodrigues; Caroline Palacio de Araujo; Simone Wellita Simão de Carvalho; Ingridh Medeiros Simões; Jéssica Batista Ribeiro e Oliveira; Edilson Romais Schmildt; Elias Terra Werner; Marcia Flores da Silva Ferreira; Amir Ali Khoddamzadeh; et al. (Journal of Plant Growth Regulation, 2026)
Euterpe edulis Martius (juçara palm) is an endangered species of high ecological and economic importance. Its propagation via reproduction is limited by the recalcitrance of its seeds, which hinders conservation and genetic improvement. Somatic embryogenesis represents an efficient alternative for large-scale clonal propagation and conservation. The present study evaluated the effect of abscisic acid (ABA) on histodifferentiation and germination of somatic embryos, to optimize in vitro regeneration of E. edulis . High rates of histodifferentiation (~ 98%) and germination (~ 95%) were achieved with 5 µM ABA, resulting in vigorous embryos with well-developed haustoria. Higher ABA concentrations (10–15 µM) were associated with reduced germination and delayed developmental progression, whereas the absence of ABA impaired histodifferentiation and embryo vigor. Proteomic profiling revealed increased accumulation of structural proteins (β-TUB7, TUBB1, TUBB5), chaperones (HSP83), proteasome components (PSMA2-like), energy metabolism enzymes (GAPDH2, PFK, PFP-α), tricarboxylic acid/glyoxysomal enzymes (SDH5, MDH-glyox), and nitrogen/methylation enzymes (GS, AHCY) in embryos treated with 5 µM ABA, suggesting associations with cytoskeletal remodeling, mitochondrial stability, epigenetic adjustments, and selective translation. In contrast, a decrease in defense proteins such as PR1 reflected a typical developmental trade-off. ABA also involves the integration of hormonal adjustments and the regulation of antioxidant enzymes. In summary, 5 µM ABA promotes efficient histodifferentiation and germination of embryos, enabling in vitro cloning, conservation, and genetic improvement of the species.

Addressing imbalanced data and feature engineering for abnormal water consumption detection with machine learning models - Mahelvson Bazilio Chaves; Fábio Rodrigo de Lima e Silva; Adiel Teixeira de Almeida Filho (Utilities Policy, 2026)

Electrochemically generated reactive chlorine species for the inactivation of hospital bioaerosols - Sergio E. Correia; Víctor Pertegal; Manuel A. Rodrigo; Cristina Sáez; Engracia Lacasa (Journal of Aerosol Science, 2026)

First plastome assembly of rice cytoplasmic male sterility (CMS) A/B lines reveals wild maternal origin - Renerio P. Gentallan; Edelweiss E. Sajise; Juan Rodrigo A. Vera Cruz; Bjorn Q. Manuel; Kristine Joyce O. Quiñones-Arribado; Jeremaiah L. Estrada; Emmanuel Bonifacio S. Timog; Patricia Izabelle M. Lopez; Wendy A. Gaspar; Sancho G. Bon; Mark Ian C. Calayugan; Teresita H. Borromeo (Genetic Resources and Crop Evolution, 2026)

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Association between restless legs syndrome and erectile dysfunction: a systematic review and meta-analysis - Rafael Matos Vieira Gordilho; Nilo Jorge Carvalho Leão Barreto; Felipe Pinho E. Albuquerque Silva; João Victor Pereira Gonzalez; Nathalia Pedreira Santos de Lemos; Kenzo Ogasawara Donato; Paula Alana Morais Seixas; Gabriela Nunes E. Brito; Henrique Brasileiro Terceiro; Felipe Pereira Garrido Pazos; Rodrigo Barbosa Freire Silvão; Cristina Salles (Sleep and Biological Rhythms, 2026)
Objective To evaluate whether patients with RLS have increased odds of ED compared with non-RLS controls. Methods We conducted a systematic review and meta-analysis analyzing the odds of ED in patients with RLS. We included studies that: (i) evaluated adults with a diagnosis of RLS established by the pre-established criteria; (ii) included a control group without RLS; and (iii) evaluated outcomes related to the odds of ED in patients with RLS. We followed the PRISMA 2020 protocol. Results This systematic review included a total sample of 33,740 participants. Patients with RLS had 70% higher odds of ED compared with non-RLS controls (OR = 1.70; 95% CI: 1.52–1.91; p < 0.001; I² = 0%). The group with severe RLS had lower odds of ED than the mild-moderate RLS group (OR = 0.67; 95% CI: 0.53–0.84; p = 0.0005). The RLS group presented increased odds of severe ED compared with non-RLS controls (OR = 4.51; 95% CI: 1.52–13.33; p = 0.006; I² = 0%), but no significant difference compared with controls for mild or moderate ED ( p > 0.05). Conclusion Individuals with RLS have 70% higher odds of ED compared with non-RLS controls. Severe ED was more frequent among patients with RLS, while no significant differences were observed for mild or moderate ED. These findings support ED screening in patients with RLS.

Untangling the Overexploitation Trap: Governance, Politics of Concepts, and the Sustainability Claims of Chilean Southern Hake - Manuel E. Martínez‐González; Renato Gozzer‐Wuest; Enrique Alonso‐Población; Juan Alfaro‐Fuentes; José T. Montero; Rodrigo Wiff (Fisheries Management and Ecology, 2026)
Despite a 2013 legal reform introducing polycentric governance and an active Marine Stewardship Council (MSC) certification, persistent overexploitation of Chilean Southern hake ( Merluccius australis ) raises fundamental questions about how institutional arrangements embedding participatory management and science‐based decision‐making actually shape management outcomes. We systematically analyzed all 54 meeting minutes of Chile's Scientific Technical Committee for Demersal Resources in the Southern Austral Zone (STC‐DRSAZ) spanning its full operational period (December 2013—October 2025), covering 15 quota recommendations and 49 sessions addressing Southern hake. We reconstructed governance dynamics through a four‐category typology of decision‐making majorities and a thematic analysis of technical opinions during STC‐DRSAZ sessions. Stock status shows a slight but insufficient recovery trend (slope = 0.006/year, p ~0.02), with spawning biomass stabilized around SB t /SB 0 ~0.3—well below the MSY target of 0.4. The records reveal that management authorities exceeded STC quota recommendations in 2018 (+24%) and 2019 (+31%), and that in 20 of 36 meeting minutes, STC members expressed critical opinions on the effectiveness of the Decision Control Rules (DCRs)—distilled into seven recurring premises—ultimately leading the STC to informally abandon their application in 2024–2026. We conceptualize these dynamics as an overexploitation trap sustained by rather static DCRs that function as a political artifact rather than a science‐based management tool, entrench a short‐term management perspective, and structurally constrain the effectiveness of independent scientific advice. This trap is not a single‐stock phenomenon: the absence of legally mandated recovery programs affects six other major Patagonian demersal fisheries. Finally, we find no evidence that MSC certification has prompted meaningful improvements in stock status, lending support to growing concerns that premature market recognition may discourage rather than incentivize genuine sustainability gains.

Pandemic disruptions and post-COVID patterns of antimicrobial resistance-associated notifications in Sweden - January G. Msemakweli; Grace Adwoa Nima Abeam; Carlos Etornam Adabe; Fabrice T. Nyambod; Adriana E. Hernani Rodrigo; Ocholi Gideon Adaji; Victor Okpanachi (Next Research, 2026)

Genotoxicity and oral tissue damage associated with tooth bleaching agents: A scoping review - Patrick Wesley Marques de Boa; Mariana Silva de Bessa; Flávio Pereira dos Santos Filho; Lara Beatriz Nascimento Diniz; Rodrigo Othávio de Assunção e Souza; Laércio Almeida de Melo; Arthur Cesar de Medeiros Alves; Boniek Castillo Dutra Borges (Mutation Research - Reviews in Mutation Research, 2026)

Soot propensity of Eucalyptus globulus laminar flames at different coflow indices - Pablo E. Pinto; Ignacio Verdugo; Mijail Littin; Gonzalo Severino; Juan J. Cruz; Felipe Escudero; Rodrigo Demarco; Andrés Fuentes (Fuel, 2026)

Effect of supplementation with different trace minerals sources and fibrolytic enzyme on the productive and reproductive performance of Nellore cows on pasture - Keuven S. Nascimento; Amanda C. M. Queiroz; Aline N. Rodrigues; Luiz F. Costa e Silva; Carlos R. Zilioti; James E. Pettigrew; Rodrigo S. Marques; Flávio D. Resende; Gustavo R. Siqueira (Tropical Animal Health and Production, 2026)

Trace element accumulation and ecological risk in agricultural and recreational pond sediments near a coal-fired power plant - Charles Bills; Varun G. Paul; Prashan M. Rodrigo; Todd E. Mlsna (Environmental Geochemistry and Health, 2026)

Time‐calibrated relationships of a rare cave catfish ( Trichomycterus rubbioli ): Shedding light on troglobitic lifestyle origin in the Brazilian caatinga - Wilson J. E. M. Costa; Paulo J. Vilardo; José Leonardo O. Mattos; Axel M. Katz; Valter M. Azevedo‐Santos; Pedro L. C. Uzeda; Rodrigo L. Ferreira (Journal of Fish Biology, 2026)
Catfishes of the subfamily Trichomycterinae comprise the most diverse fish group with species adapted to live in Neotropical caves, but past evolutionary scenarios that have driven the origin of these troglobitic species remain unknown. We herein investigate the phylogenetic position of the cave‐restricted Trichomycterus rubbioli , endemic to the semi‐arid Caatinga of northeastern Brazil, through a time‐calibrated molecular phylogenetic analysis of a broad sample of trichomycterine taxa (84 spp), using two nuclear and two mitochondrial genes (3030 bp). The analysis supported T. rubbioli as a member of the Trichomycterus s.s. clade endemic to eastern South America and an early Miocene origin for the T. rubbioli lineage. The combination of available data suggests that the T. rubbioli lineage adapted to the troglobitic lifestyle between the Middle and Late Miocene, a period when the semi‐arid conditions of the Caatinga biome became established and consequently streams of the region became seasonal. This past scenario would be responsible for extinction of epigean trichomycterines while preserving the lineage within the cave system. Morphological characters of the troglobitic ‘Trichomycterus’ itacarambiensis from the transition area between the Cerrado and the Caatinga indicate distant relationships with T. rubbioli , suggesting an independent evolutionary event of cave colonization.

Climate Vulnerability of Australian Seafood Systems: A National Assessment of Exposure and Adaptive Capacity - Stephanie Brodie; Laura K. Blamey; Ana Bugnot; Rodrigo H. Bustamante; Julia L. Blanchard; Lara Buhagiar; Elizabeth A. Fulton; Alistair J. Hobday; Éva E. Plagányi; Anthony J. Richardson; Richard Matear; Skipton N. C. Woolley; et al. (Fisheries Oceanography, 2026)
Marine waters are becoming warmer and acidified and experiencing more intense and longer heatwaves under climate change. These changes are already impacting marine ecosystems and seafood production, which are vital for supporting food security and economic productivity. For Australia, a national‐scale assessment of exposure to climate hazards is needed to support climate‐resilient ecosystem management across one of the world's largest exclusive economic zones. Commercial fishing relies on healthy ecosystems and is one of Australia's most important sectors in terms of cultural identity and regional value. However, Australian fisheries and aquaculture are increasingly exposed to climate‐driven changes in ocean conditions, creating substantial risks for marine ecosystems, seafood production and coastal economies. We assess the exposure of Australia's seafood sector to climate change using high‐resolution climate projections and ecosystem model outputs under three global warming levels (1.5°C, 2°C and 3°C futures). Our findings reveal that the entire Australian exclusive economic zone is exposed, with cumulative exposure highest for regions with a large continental shelf. The biomass available to fisheries is projected to decline. Negative impacts from climate change are generally expected for fisheries and aquaculture production. Despite some evidence of adaptation, uneven adaptive capacity across sectors and jurisdictions presents challenges for climate resilience. This study underscores the urgency of global mitigation efforts to reduce risk, coordinated adaptation strategies, improved coastal hazard modelling and ecological risk assessments to safeguard the future of fisheries and aquaculture industries under climate change.

Peripheral oxytocin administration decreases the food intake and compulsive-like behavior in male rats in an animal model of binge-type eating - Yeimi J. Cuellar-Salazar; Josué O. Suárez-Ortiz; Juan M. Mancilla-Díaz; Rodrigo E. Escartín-Pérez; Verónica E. López-Alonso; Daniel Díaz-Urbina (Psychopharmacology, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

The role of different organs in the hydroxylation of pumiliotoxin (+)-251D to allopumiliotoxin (+)-267A in the poison frog Adelphobates galactonotus - Basil Minder; Andrés E. Brunetti; Jacqueline N. Mendonça; Rodrigo Moreira da Silva; Ralph A. Saporito; Noberto P. Lopes; Taran Grant (Toxicon, 2026)

The presence of an atavistic caniniform alveolus in Nothrotherium maquinense (Xenarthra, Folivora, Nothrotheriidae) - Daniel M. Casali; Claudia G. Costa; Fernando H. S. de Barbosa; Fellipe P. Muniz; Gabriel Mestriner; Rodrigo Parisi Dutra; Rachel E. Narducci; H. Gregory McDonald; Camille Fonseca Tostes; Izabella Lucas de Abreu Lima; Flávio Ricardo Manzi; Luciano Vilaboim Santos (Journal of Mammalian Evolution, 2026)
Sloths (Folivora) display remarkable morphological diversity yet share a highly conserved dental formula, whose occasional deviations offer key insights into their evolutionary history. Among nothrotheriids, Neogene species retained upper and lower caniniforms, whereas these teeth were lost in Pleistocene genera. Here we describe, for the first time, a poorly developed alveolus interpreted as an atavistic upper caniniform alveolus in an individual of Nothrotherium maquinense from the Late Pleistocene of Bahia, Brazil. Computed tomography and X-ray imaging confirm its internal anatomy and rule out taphonomic or pathological origins. The alveolus occupies the precise position of the caniniform in Neogene nothrotheriids and exhibits similar morphology, suggesting a partial re-expression of a lost ancestral trait. Beyond its developmental implications, this observation may offer additional context for interpreting the taxonomy of Nothropus , traditionally defined based on the presence of a lower caniniform alveolus. The occurrence of similar atavistic structures in related taxa indicates that this feature alone may be insufficient for diagnosis and warrants reevaluation within a broader evolutionary framework.

Hyperdominance and Rarity in Amazonian Secondary Forests - Fernando Elias; Joice Ferreira; Erika Berenguer; Rodrigo Oliveira do Nascimento; Leonardo Miranda; Divino Vicente Silvério; Ima Célia Guimarães Vieira; Luiz E. O. Aragão; Gustavo Schwartz; Jos Barlow (Global Change Biology, 2026)
Recent studies have shown that a few tree species dominate abundance and carbon storage in undisturbed Amazonian forests. However, this pattern remains poorly understood in forests regrowing after deforestation. Understanding dominance patterns in secondary forests is important as it could improve insights into their functioning and guide management and restoration efforts. We used unweighted and novel plot‐weighted approaches to assess hyperdominance in abundance and carbon storage of trees and palms during secondary forest recovery, using data from 102 plots across four regions in the eastern Amazon, separated by an average distance of 600 km (range: 150–1000 km). Secondary forests show high levels of hyperdominance in all approaches, with just 15–25 species (3%–6%) accounting for over 50% of abundance and carbon storage. A small subset of species (~9%) were found across all regions and successional stages, highlighting their key role in ecosystem structure and function during forest regrowth. Annona exsucca , Cecropia palmata , Tapirira guianensis , and Inga alba formed a consistent core of hyperdominant species across stem size classes, metrics, and approaches, jointly accounting for roughly 16%–27% of total abundance and carbon storage. For larger stems ≥ 10 cm DBH, hyperdominant species exhibited lower wood density compared to non‐hyperdominant species across all successional stages, suggesting these specialist pioneers have distinct ecological strategies from the rest of the community. Our findings indicate that secondary forest functioning may be largely predicted by a relatively limited set of species, providing a framework for future research ranging from ecophysiology to remote sensing of canopy traits and restoration planning.

Risk Is Not Equal to Impact: The Challenges of Developing a Traffic Light System to Regulate Farmed Salmon Production on an Ecosystem Scale - Doris Soto; Rodrigo M. Montes; Renato A. Quiñones; Jorge León‐Muñoz; Marcelo E. Fuentes; Ruben Avendaño‐Herrera; Elias Pinilla; Jessica Fuentes; Carlos Chávez (Reviews in Aquaculture, 2026)
We review information on salmon farming production, environmental and climatic variables covering all salmon farming areas in the Patagonia marine ecosystems over a 10‐year period in Chile. With this information, we develop a semi‐quantitative Environmental and Productive Risk Assessment (RA) model as a guide for the design of a Traffic Light System (TLS) for salmon farming in Chile that ensures the minimizing impacts to ecosystems and to farmed salmon themselves. This interdisciplinary study is based on the compilation and integration of historical databases from multiple public and private institutions. These databases contain information on production, fish health, oceanographic and climatic information from 79 Salmon Farming Concessions Groupings (ACS) from 2012 to 2022. The model reveals that the highest Environmental and Productive Risks occur where high cumulative production pressure (Hazard) coincides with high Environmental Sensitivity, primarily in the fjords of the Los Lagos and Aysén regions. The study provides a risk‐based approach to prioritize monitoring and promote precautionary management in high‐risk areas while there is not enough information on ecosystem‐level tipping point indicators. Further development of a robust TLS requires the collaborative validation of ecosystem‐scale data and involving all relevant stakeholders in a participatory process to establish agreed‐upon risk thresholds and governance mechanisms for its implementation.

Zinc deficiency and sarcopenia define a metabolic frailty phenotype predicting hepatic encephalopathy and early mortality in cirrhosis - Osvely Méndez-Guerrero; Anaisa Carranza-Carrasco; Rodrigo Guerrero-Guerrero; Lilia Castillo-Martínez; Fabiola M. Del Razo-Olvera; Liliana Juárez-Martínez; Rodrigo Otero-Otero; Alma Estanes-Hernández; Patricia Clark; Carlos A. Aguilar-Salinas; Aldo Torre; Graciela E. Castro-Narro; et al. (Metabolic Brain Disease, 2026)

Warming winters and cultivar resilience in sweet cherry: agroclimatic requirements and future suitability under Mediterranean-continental conditions - N. Santolaria; L. Castel; J. Rodrigo; E. Fadón (Agricultural and Forest Meteorology, 2026)

Reproductive efficiency of Nelore (Bos indicus) cows submitted to conventional resynchronization or ReBreed21 programs - Mirela Balistrieri; Tainá L.P. Azevedo; Paula R. Cortat; Marcos H.A. Colli; Lucas O. e Silva; Carlos E.C. Consentini; Rodrigo L.O.R. Alves; José R. Gonçalves; Alexandre B. Prata; Roberto Sartori (Theriogenology, 2026)

Oxidative technologies for olive grove soils: Impacts of electrogenerated H2O2 and O3 on pesticide degradation and ecosystem health - C. Navas-Higuero; B.A. Tiban; V. Valenzuela-Polo; M.I. Reyes-Alcalde; A.J. Manzaneda; A.J. Rascón; J.F. García-Reyes; R. Salazar-García; J.E. Palomares-Rius; E. Lacasa; M.A. Rodrigo; C. Saez (Journal of Environmental Chemical Engineering, 2026)

Integration of electrochemical technologies to produce chlorine dioxide: A solution for disinfection processes - Sergio E. Correia; Engracia Lacasa; Pablo Cañizares; Manuel A. Rodrigo; Cristina Sáez (Journal of Environmental Chemical Engineering, 2026)

Towards sustainable chlorine dioxide production via HClO3 generation using bipolar membrane electrodialysis - Sergio E. Correia; Engracia Lacasa; Pablo Cañizares; Manuel A. Rodrigo; Cristina Sáez (Journal of Environmental Chemical Engineering, 2026)

Hydrodynamic and water quality modelling of a free water surface constructed wetland for urban runoff mitigation - A. Martínez-Biosca; C. Hernández-Crespo; E. Asensi; I. Andrés-Doménech; M.Eugenia Rodrigo-Santamalia; V. Benedito-Durá; M. Martín (Ecological Modelling, 2026)

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

Stereotactic ablative radiotherapy: an effective alternative for pancreatic metastases originating from renal cell carcinoma—experience from two European institutions - Maria Ausilia Teriaca; Deesje Doppenberg; Tiziana Comito; Rodrigo Cartes; Lorenzo Lo Faro; Enrico Pozzo; Veronica Vernier; Ciro Franzese; Anna M. E. Bruynzeel; Marta Scorsetti (Clinical & Experimental Metastasis, 2026)

Magnetic Fabrics and Provenance Directions of Mid-Late Jurassic Pyroclastic Flows from the Northern Antarctic Peninsula - Florencia N. Milanese; Laila Iacono; Pablo R. Franceschinis; Florencia Boedo; Miguel Gumina; Carla Puigdomenech Negre; Rodrigo Feo; Joaquín Gil; Jorge Lozano; Julián Agostini; Matías Naselli; Manuel Montes; et al. (Studia Geophysica et Geodaetica, 2026)

Navigating Narratives: An Exploratory Scoping Review on the Framing of the Illegal, Unreported and Unregulated Fishing Research - Brittany Bartlett; Rodrigo Oyanedel; Hollie Booth; Stefanía Ásta Karlsdóttir; Amaël Dupaix; Ariel Greiner; M. Isidora Ávila‐Thieme; Juan Andrés Silva; Shathuki Perera; Mayuri Chopra; E. J. Milner‐Gulland (Fish and Fisheries, 2026)
Sustainable fisheries are often undermined by illegal, unreported and, in some cases, unregulated fishing (collectively, IUU fishing). As such, it is critical to ensure that current research effectively informs practical fisheries management interventions. We conducted an exploratory scoping review of 509 scholarly articles to assess general trends related to how IUU fishing is framed and distributed in the literature, identifying prevailing narratives that may influence governance. Research on the topic of IUU fishing has increased over time, although geographic distributions in terms of study locations and lead authorship do not necessarily align with global hotspots and priorities. While most location‐specific studies include at least one author affiliated with an institution from the region being studied, a bias remains towards first authors from high‐income countries. Moreover, while there is a justified focus on the Western Pacific Ocean, other vulnerable regions, such as the West Indian Ocean, remain comparatively underrepresented. Contrary to the assumption of a social science deficit in marine conservation, over half of the articles categorised applied a primarily social science lens; however, coverage from the behavioural sciences was limited. A subset analysis revealed a strong emphasis on large‐scale illegal fishing, with frequent conceptual blurring across fishery scales and IUU components. These patterns suggest a high‐level and often ambiguous framing of IUU fishing, which may risk oversimplifying complex issues and diluting context‐specific nuances. We recommend a shift towards more grounded and solutions‐oriented research, with more focus on unreported and unregulated fishing, particularly in small‐scale contexts and underrepresented locations.

Screening of Brazilian cowpea cultivars for resistance to Meloidogyne incognita and M. javanica - Gerson Luís dos Santos Rodrigues Júnior; Micheline do Amaral Dias; Gabriele Stefanello Manfio; Kaesel Jackson Damasceno e Silva; Juvenil Enrique Cares; Robert Neil Gerard Miller; Jansen Rodrigo Pereira Santos (Crop Protection, 2026)

Red light–mediated enhancement of the antifungal activity of Physalis angulata against Candida species - Bianca Borges de Alencar; Maria Laura Faleiros Ribeiro de Melo; Wanderson Zuza Cosme; Matheus Henrique Francisco Dias; Camila Cristina Baccetti Medeiros; Rodrigo Sorrechia; Rosemeire Cristina Linhari Rodrigues Pietro; Fabiano Guimarães Silva; Marcio Luís Andrade e Silva; Wilson Roberto Cunha; Patrícia Mendonça Pauletti; Regina Helena Pires; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Computational assessment of adsorption mechanisms between nanoplastics and arsenic in the atmosphere - Diego Cortés-Arriagada; Daniela E. Ortega; Rodrigo Araya-Hermosilla; Esteban Araya-Hermosilla (Journal of Environmental Chemical Engineering, 2026)

Mercury concentration: A new window into ancient diets and trophic levels in vertebrate paleontology - Felipe M.S. Cardia; José Vicente E. Bernardi; Carlos Eduardo M. Oliveira; Marco B. Andrade; Max C. Langer; Sandra A.S. Tavares; Fabiano V. Iori; William R. Nava; Thiago S. Marinho; Luiz Carlos B. Ribeiro; Jurandir R. Souza; Rodrigo M. Santucci (Chemical Geology, 2026)

Effects of soil nutrient enrichment on biomass, herbivores, and their predators differ between tree species in the Brazilian Cerrado - Carla Faleiro Tinoco; Sílvia Castro; Rodrigo Damasco Daud; Vanessa Leonel Falchi; Júlia Almeida Reis; Stefany Ribeiro Constantino; Carlos de Melo e Silva-Neto; Luísa Gigante Carvalheiro (Oecologia, 2026)
Human-induced changes in nitrogen (N) and phosphorus (P) global cycles and availability significantly impact plant growth and nutritional composition, thereby affecting ecosystem dynamics. However, research on the effects of increased nutrient availability often focuses on plant community-level effects, overlooking interspecific variability and neglecting impacts on higher trophic levels. Using a controlled fertilization experiment with six tree species that naturally occur in the Cerrado biome (Brazilian savannas), we showed that there is substantial interspecific variation in how plants respond to nutrient changes. This reflects the existence of competitive advantage for certain native species under a scenario of increased soil nutrient availability. Such effects propagated to higher trophic levels (herbivores and their predators), also varying between plant host species. The strength and direction of N input effect depended on P levels and the type of herbivores. Large invertebrate leaf herbivores were less affected than phytophagous mites. Impacts on higher trophic levels (predatory mites) were less pronounced than on phytophagous mites. Overall, we show that ongoing soil nutrient enrichment has the potential to alter interspecific competition dynamics in plant communities with consequences for ecological interaction partners. These findings have important implications for conservation and ecosystem management, especially in areas highly exposed to soil nutrient enrichment due to farming and industrial activities.

Metabolic and productive responses to heat stress in transition dairy cows: Interactions with calving stage, season, and farm management - E. N. Martínez; C. Castillo; L. Avendaño Reyes; Rodrigo Muiño; L. Díaz-González; J. L. Benedito; J. Hernández (International Journal of Biometeorology, 2026)
This study investigated the effects of heat stress (HS), calving period, and farm-level management on the metabolic and productive responses of transition dairy cows. Conducted on three commercial farms in northwestern Spain, the study employed a multifactorial design across two seasons (winter and summer) and four peripartum time points. Biochemical parameters, including non-esterified fatty acid (NEFA), β-hydroxybutyrate (BHB), urea, total protein, albumin, glucose, gamma-glutamyltransferase (GGT), and aspartate aminotransferase (ASAT) were analyzed using repeated-measures MANOVA. No significant three-way interactions were found, but several two-way interactions emerged. Notably, NEFA and urea levels varied significantly between farms, while total protein and albumin were influenced by both partum stage and season. Elevated NEFA and BHB concentrations postpartum indicated intensified lipid mobilization and negative energy balance, exacerbated under HS. Reduced albumin and increased urea levels suggested hepatic stress and altered protein metabolism. Farm-specific differences in ASAT during summer highlighted the role of local environmental and management conditions. These findings underscore the complex interplay between physiological stage, environmental stressors, and farm practices. Tailored intervention (such as nutritional adjustments, cooling systems, and precision monitoring) are essential to mitigate the metabolic burden of HS and safeguard cow health and productivity. Future research should explore long-term impacts and adaptive strategies across diverse production systems.

Replacing Conventional Fertilization with Organomineral Fertilizer in ‘Hass’ Avocado Trees Improves Chlorophyll Indices and Fruit Size: A Bootstrap Simulation Approach - Marllon F. S. dos Santos; Rodrigo J. Milan; Bruna M. Costa; Tatiana E. Cantuarias-Avilés; Idemauro A. R. de Lara; Simone R. da Silva (Applied Fruit Science, 2026)
Modern agriculture faces significant challenges related to the depletion of finite resources used in fertilizer production. In response to this situation, the market has been adapting by developing biofertilizers or organomineral fertilizers, which incorporate an organic fraction into their composition. These fertilizers provide nutrients more gradually, reducing leaching. Studies on this topic are scarce for avocado trees, whose global production has been increasing. For this reason, the present research aimed to compare conventional fertilization with organomineral fertilization in ‘Hass’ avocado trees. A total of 20 plants per treatment were used in a commercial orchard, with treatments providing the same amount of nutrients. Variables related to vegetative growth, gas exchange, and productive data were evaluated. Data analysis was performed using bootstrap simulations, a resampling technique with 10,000 simulations, which enabled the construction of confidence intervals for the variables being assessed, resulting in an experimental optimization. Although no significant differences were detected in overall yield, the organomineral treatment showed increases of up to 10% in chlorophyll levels, 17.69% in fruit weight, and 8.35% and 9.18% in fruit length and diameter, respectively, compared to the conventional treatment. The bootstrap technique proved effective for analyzing this type of experiment, confirming the benefits of replacing conventional fertilization with organomineral fertilization, which provides nutrients more efficiently and sustainably.

Deep Learning-Based Classification of Temporal Stages of AT8-Labeled Tau Pathology After Experimental Traumatic Brain Injury - Guilherme José de Antunes e Sousa; Rodrigo Afonso Sá; Marcos António Spínola Monteiro Gomes; George A. Edwards; Ines Moreno-González; Ricardo José Alves de Sousa (Neuroinformatics, 2026)
Tauopathies are characterised by a progressive accumulation of hyperphosphorylated tau. However, early and intermediate stages remain challenging to quantify due to subtle and heterogeneous morphological characteristics. This study evaluates a deep learning framework for classifying multiple temporal stages of tauopathy progression using AT8 (anti-phospho-tau antibody)-stained cortical micrographs in a controlled traumatic brain injury mouse model – an underexplored application. Three convolutional neural network (CNN) architectures were examined: a custom CNN and two transfer-learning models (InceptionV3 and DenseNet). Images were grouped into four post-injury stages: 1 day, 1 week, 1 month and 3 months. Preprocessing included normalisation, augmentation and oversampling to address imbalance. Performance was assessed using stratified k-fold cross-validation with accuracy, macro-F1, per-class F1, and one-vs-rest area under the receiver operating characteristic curve (AUC). DenseNet achieved the best overall performance (accuracy = 70.9%, macro-F1 = 0.68) with strong discrimination for the 1-week stage (F1 = 0.95). All models showed limited separability in the earliest post-injury stage (1 day), while intermediate to late stages (1–3 months) exhibited partial overlap, consistent with the progressive nature of tau accumulation. These results indicate that deep learning, particularly transfer learning, offers a scalable approach for automated temporal staging of tauopathy in preclinical histology. Although the results are based on internal cross-validation without independent animal-level identifiers or external cohorts, the proposed framework provides a reliable foundation for incorporating CNN-based analysis into digital neuropathology workflows. Larger multi-centre datasets and slide-level modelling will be required to assess generalisation and support applications in early detection, longitudinal tracking, and treatment evaluation of tau-related neurodegeneration.

Chemical arsenal of sea anemones: antifouling effects on bryozoan larvae and interspecific interactions - Javier Pinochet; Rodrigo Placencia; Antonio Brante; Marcelo E. Lagos (Biofouling, 2026)

Humic substances and Eisenia bicyclis bioactive extract modulate water, biofilter, and seabass (Dicentrarchus labrax) skin mucus bacterial communities - Davide A. Machado e Silva; Antonio Louvado; Rodrigo O.A. Ozorio; Thais Cavalheri; Daniel F.R. Cleary; Newton C.M. Gomes (Aquaculture, 2026)

Controls of sea–air O2 and CO2 exchanges along the Patagonian shelf-break: the role of temperature and phytoplankton communities - Luísa M. Garcia; Iole Beatriz M. Orselli; Virginia Maria Tavano; Carlos Rafael B. Mendes; Carlos Alberto E. Garcia; Rosane G. Ito; Catherine Goyet; Rodrigo Kerr (Progress in Oceanography, 2026)

Intrinsic responses to nitrogen deficiency of Antarctic ecotypes of Colobanthus quitensis (Kunth) Bartl. and Deschampsia antarctica Desv. - Nicolás Peña-Heyboer; Marisol Pizarro; Gustavo E. Zúñiga; Rodrigo A. Contreras (Plant Science, 2026)

Conservation of an endangered amazonian primate: priority areas for the pied tamarin (Saguinus bicolor) in Manaus, Brazil - Ana Luisa Albernaz; Marcelo Cordeiro Thalês; Marcelo Gordo; Diogo Lagroteria; Tainara V. Sobroza; William E. Magnusson; Philip M. Fearnside; Leandro Jerusalinsky; Renata Bocorny de Azevedo; Rodrigo Baia Castro; Dayse Campista; Wilson Roberto Spironello; et al. (Journal for Nature Conservation, 2026)

Edible oils as bio-plasticisers for sustainable additive manufacturing: comparative electrochemical performance and sensing of ascorbic acid in juices - Ana C.M. Oliveira; Elena Bernalte; Zakari Moumen; Karen K.L. Augusto; Muhzamil A. Khan; Rodrigo A.A. Muñoz; Robert D. Crapnell; Craig E. Banks (Food Chemistry, 2026)

Synergistic Experimental and Theoretical Studies on Pesticide Detection in River samples Using Faujasite-CTAB Modified Carbon Paste Electrode - Cybelle C. C. M. Barbosa; Barbara L. Ramos; Elivelton A. Ferreira; Rodrigo G. Amorim; Ramon S. da Silva; Rodrigo Della Noce; Adriana E. de Carvalho; Mendelssolm K. de Pietre (Water, Air, & Soil Pollution, 2026)

Dopaminergic Modulation of Striatal Somatostatin Interneurons Shapes Motor Learning and L-DOPA-Induced Dyskinesia - Agostina Mónica Stahl; Rodrigo Manuel Paz; Cecilia Tubert; Gimena Gomez; Juan Emilio Belforte; Irene R. E. Taravini; Lorena Rela; Mario Gustavo Murer (Molecular Neurobiology, 2026)

Invasive species in the aquarium trade: survey of attitudes, behaviors, and knowledge among US participants - Joseph V. Brown; William E. Kelso; Rodrigo Diaz; Wesley M. Daniel; Haley M. Brassard; Michael D. Kaller (Hydrobiologia, 2026)
Although the aquarium trade is an important pathway for direct and indirect non-native species introductions into freshwater systems, knowledge and attitudes of participants in the trade regarding alien species issues is largely undocumented. Therefore, we administered a survey to investigate attitudes and behaviors of aquarists and non-aquarists regarding the aquarium trade as a pathway for invasive species introductions. We hypothesized aquarists would be better educated on potential introductions than non-aquarists. Due to their engagement with organisms and replication of natural habitats, we also expected aquarists would exhibit more positive attitudes and behaviors toward the environment than non-aquarists. Most respondents seemingly understood the severity of invasive species problems, regardless of status as an aquarist. Aquarists thought the aquarium trade was less responsible for species introductions than non-aquarists and also felt more aware of laws regarding invasive species. However, over half of aquarists disposed of aquarium water down a drain in their house or directly into a nearby water body, which is a known mode of invasion. This information can inform further efforts to provide educational opportunities for participants in the non-native pet/aquarium trade, with the goal of enhancing protection efforts for native biodiversity.

Impacts of rotation, tillage, cover cropping, and drainage on soil health in soybean-based cropping systems: Evidence from 4–50-year trials across the US - Tatiane Severo Silva; Lindsay Chamberlain Malone; Matthew D. Ruark; Chad D. Lee; David Jordan; Hanna J. Poffenbarger; Herman J. Kandel; Jeremy Ross; John M. Gaska; Joseph G. Lauer; Laura E. Lindsey; Maninder Pal Singh; et al. (Agriculture, Ecosystems & Environment, 2026)

First At‐Sea Identifications of Ginkgo‐Toothed Beaked Whale ( Mesoplodon ginkgodens ): Acoustics, Genetics, and Biological Observations Off Baja California, México - E. Elizabeth Henderson; Lisa T. Ballance; Gustavo Cárdenas‐Hinojosa; Jay Barlow; Annamaria I. DeAngelis; Sergio Martínez‐Aguilar; Craig Hayslip; L. Todd Pusser; Mario Márquez Segovia; C. Scott Baker; Debbie Steel; Rodrigo Huerta‐Patiño; et al. (Marine Mammal Science, 2026)
In 2024, an expedition was conducted off northwestern Baja California, México, to find and identify the beaked whale species that produced the BW43 echolocation pulse previously recorded in this area and elsewhere in the North Pacific. There were five Mesoplodon sightings and 21 BW43 acoustic detections on both a towed array and drifting pole buoy recorders over the course of the survey. Three of the sightings had concurrent acoustic detections, and a biopsy sample and environmental DNA were also collected from one of the sightings. The genetic identification confirms that the Mesoplodon sighted and acoustically recorded was the ginkgo‐toothed beaked whale ( Mesoplodon ginkgodens ), and the co‐occurrence of these sightings with the BW43 acoustic detections definitively links the species and its echolocation pulse. This is the first time that genetically confirmed ginkgo‐toothed beaked whales have been observed at sea and definitively linked to the BW43 pulse. This paper details the encounters, acoustic behavior, genetics, coloration, and external morphology of this species, including a comprehensive review of its distribution using historical sightings, strandings, and acoustic detection data from the North Pacific Ocean.

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Behavior of anthropogenic particles on coastal seawater and intertidal sediment of a gulf in Patagonia Argentina - Ayelén Costa; Juan P. Pisoni; Juan P. Tomba; E. Camila F. Tavano-Formigo; Rodrigo D. Hernández-Moresino (Environmental Monitoring and Assessment, 2025)

In vitro and in silico schistosomicidal activity of hexane fraction from Copaifera oblongifolia leaves - Rafael Corrêa Ramos; Lizandra G. Magalhães; Rodrigo C. S. Veneziani; Sérgio R. Ambrósio; Híllary Ozorio Gobeti Caprini; Cibelle Ramos Da Silva; Jairo K. Bastos; Márcio L. Andrade e Silva; Erdi Can Aytar; Mario F. C. Santos; Wilson R. Cunha (In Silico Pharmacology, 2025)

Reproductive indicators highlight the need to revise the biological closure of southern hake (Merluccius australis Hutton, 1872) in Chilean Patagonia - Andrés Flores; Rodrigo Wiff; Renato Céspedes; Manuel E. Martínez González (Fisheries Research, 2025)

Unveiling the inflammatory response in macrophages induced by Micrurus lemniscatus venom - Sulamita da S. Setúbal; Larissa Faustina Cruz; Valdison P. Dos Reis; Mauro V. Paloschi; Rodrigo Maia-Marques; Catarina Teixeira; Juliana P. Zuliani; Luciana Casais-e-Silva (Toxicon, 2025)

Cumulative ductility and fatigue life of Buckling-Restrained Braces under severe seismic loading conditions: An experimental study - Héctor Guerrero Bobadilla; Rodrigo E. Alva Bañuelos; Luis Iván Velasco Enriquez; Amador Terán Gilmore; Danny Arroyo Espinoza; Javer Humberto Vargas Ortiz; Edgar Tapia Hernández (Soil Dynamics and Earthquake Engineering, 2025)

Phytochemistry of crustose lichens from Mount Rossman, Ellsworth Land, Antarctica - Rodrigo A. Contreras; Marisol Pizarro; Pablo Zamora; Gustavo E. Zúñiga (Phytochemistry Letters, 2025)

Growth rate and finishing system alter beef color and early postmortem metabolism in Bos indicus crossbred cattle - Juan F. Morales Gómez; Patricia M. Ramos; Mariane Beline; Daniel S. Antonelo; Bruna Pavan; Rodrigo S. Goulart; Laila T. Kirkpatrick; David E. Gerrard; Saulo L. Silva (Meat Science, 2025)

Breast cancer immunophenotypes are associated with exposure to mixtures of organochlorine pesticides and trace elements among Northern Mexican women - Ángel Mérida-Ortega; Rodrigo Ugalde-Resano; Mariano E. Cebrián; Lizbeth López-Carrillo (Journal of Trace Elements in Medicine and Biology, 2025)

Degradation of polyethylene geomembranes exposed to different mine tailings pore waters - Rodrigo A. e Silva; R. Kerry Rowe; Fady B. Abdelaal (Geotextiles and Geomembranes, 2025)

Highlighting the marine fungi Cunninghamella echinulata-9A5 as bioemulsifier for treating tannery leather residue - Mariana Bueno do Nascimento; Wanderson Zuza Cosme; Heber Eduardo Andrada; Kátia Roberta Prieto de Oliveira; Maria Isabela da Silva Figueiredo; Vanessa Mendes Rego; Marcos Antonio Soares; Rodrigo Sorrechia; Sarah Santana Sanchez; Rosemeire Cristina Linhari Rodrigue Pietro; Gustavo Muniz Dias; Marcio Luís Andrade e Silva; et al. (Brazilian Journal of Microbiology, 2025)

Proximity to Natural Habitat Is Not Consistently Associated With Pollination Services in Tropical Smallholder Farms: A Systematic Review and Meta‐Analysis - Ennia Bosshard; Mark E. Harrison; Frank van Veen; Chris J. Kettle; Nagaraja Badenahally Chikkarangappa; John E. Banks; Parthiba Basu; Quebin Bosbely Casiá‐Ajché; Bo Dalsgaard; Aditi Dutta; Eunice Enríquez; Natalia Escobedo‐Kenefic; et al. (Ecology Letters, 2025)
Proximity to natural habitat is known to enhance pollination services in large‐scale agriculture, but it remains unclear whether this holds in tropical smallholder farms. These systems are embedded in ecologically complex landscapes, central to global food security, and depend heavily on biodiversity‐derived ecosystem services. We conducted a systematic review and meta‐analysis of 35 studies assessing the relationship between distance to natural habitat and pollinator abundance, species richness, and crop fruit set in tropical smallholder farms. We found no consistent patterns in pollinator abundance and crop fruit set with increasing distance, with relationships highly variable across studies. Similarly variable, yet slightly negative, was the relationship between distance and pollinator species richness. Our findings suggest limited support for the ‘proximity to natural habitat’ hypothesis in tropical smallholder farms, indicating that the inherent complexity of these landscapes may buffer negative effects of distance on pollination. This underscores the importance of maintaining and restoring landscape complexity to sustain biodiversity and ecosystem services such as crop pollination. We also highlight the need for greater methodological consistency and publicly available raw data in future studies to strengthen the evidence base and support management strategies for safeguarding pollination services in tropical smallholder farms.

Delayed embryonic attachment, circulating pregnancy-associated glycoproteins, and pregnancy loss in heifer embryo recipients - João Paulo N. Andrade; Rafael R. Domingues; Victor E. Gomez-León; Guilherme Madureira; Luma C. Sartori; Gustavo F. Grillo; Meliton Fosado; Rodrigo V. Sala; Milo C. Wiltbank (Theriogenology, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Reproductive outcomes of prepubertal Bos indicus beef heifers raised in a feedlot system submitted or not to ovulation induction strategies prior to a timed-artificial insemination treatment regimen - Rodrigo L.O.R. Alves; Lucas O. e Silva; Carlos E.C. Consentini; Oseias P. Santos; Andrés A.C. Narváez; Leandro D. da Cunha; Rafael A. Braz; Maria E.R. e Silva; Rodrigo Brüner; Leonardo F. Melo; Roberto Sartori (Theriogenology, 2025)

Energy-efficient electro-ozonizers: A solution for antibiotic-resistant bacteria (ARB) in wastewater - Sergio E. Correia; Engracia Lacasa; Pablo Cañizares; Manuel A. Rodrigo; Cristina Sáez (Process Safety and Environmental Protection, 2025)

Niche-conserved bacterial consortia enhanced maize agro-physiological performance and soil biological P-related traits under low-P conditions - Dounia Nkir; Yassine Aallam; Mohamed Idbella; Rodrigo Alegria-Terrazas; Brahim Benbrik; Ammar Ibnyasser; Meryem Haddine; Tessa E. Reid; George Lund; Tim H. Mauchline; Jim Harris; Mark Pawlett; et al. (Applied Soil Ecology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

UV-B radiation responses in Antarctic plants - Rodrigo A. Contreras; Gustavo E. Zúñiga (Theoretical and Experimental Plant Physiology, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Ocean acidification and elevated temperatures alter the behavior of a sub-Antarctic fish - María E. Lattuca; María E. Barrantes; Eloísa M. Giménez; Patricio H. Manríquez; Rodrigo Torres; Paolo Domenici; Myron A. Peck; Daniel A. Fernández (Marine Pollution Bulletin, 2025)

Photobiomodulation presents an anti-inflammatory effect, reflecting on the expression of receptors related to the pain process in a collagenase-induced tendinitis experimental model - Yose Marie Elizabeth e Silva; Patrícia de Viveiros Tavares Alves; Rachel Bharbara Maccheronio Dalmaso; Ana Paula Ligeiro de Oliveira; Cinthya Cosme Gutierrez Duran; José Antônio Silva Júnior; Stella Regina Zamuner; Maria Fernanda de Souza Setubal Destro; Rebeca Boltes Cecatto; Rodrigo Álvaro Brandão Lopes Martins; Richard Eloin Liebano; Rodrigo Labat Marcos (Journal of Photochemistry and Photobiology B: Biology, 2025)

Reproductive performance of yearling Bos indicus heifers submitted to programs for induction of ovulation prior to a timed-artificial insemination protocol - Ana Luíza M. Lopes; Giselly B. Kolling; Lucas O. e Silva; Rodrigo L.O.R. Alves; Fabiana M. de Assumpção; Suzane K.M. Leite; Akyra Terra; Roger de M. M. Wutke; Antonio C.S. Rezende; José R.S. Rezende; Lainer Leite; Roberto Sartori (Theriogenology, 2025)

Effect of the follicular stage and circulating progesterone concentrations at the beginning of an estradiol/progesterone-based synchronization protocol on profile of gonadotropins and follicle dynamics in beef heifers - Lucas O. e Silva; Patrícia R. Cavalcanti; Rodrigo L.O.R. Alves; Natália P. Folchini; Natália N. Teixeira; Pedro J.L. Monteiro; Milo C. Wiltbank; Roberto Sartori (Theriogenology, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Harpagifer bispinis, but not Patagonotothen tessellata, appears robust to interactive effects of ocean warming and acidification in southern Patagonia - Eloísa M. Giménez; Fabián A. Vanella; Laura I. Wolinski; Rodrigo Torres; María E. Lattuca (Marine Environmental Research, 2025)

Effect of long-term retrogradation on the crystallinity, vibrational and rheological properties of potato, corn, and rice starches - Gonzalo Velazquez; Cristian Felipe Ramirez-Gutierrez; Guadalupe Mendez-Montealvo; Rodrigo Velazquez-Castillo; Luis Fernando Morelos-Medina; Eduardo Morales-Sánchez; Marcela Gaytán-Martínez; Mario E. Rodríguez-García; Brenda Contreras-Jiménez (Food Chemistry, 2025)

Soybean yield response to management practices (4–40 years) and soil health parameters - Tatiane Severo Silva; Lindsay Chamberlain Malone; Matthew D. Ruark; Spyridon Mourtzinis; Chad D. Lee; David Jordan; Herman J. Kandel; Jeremy Ross; John M. Gaska; Joseph G. Lauer; Laura E. Lindsey; Maninder Pal Singh; et al. (Field Crops Research, 2025)

Anthropogenic intensification on plant-pollinator interactions over four decades in Chile: a spatiotemporal assessment - Bárbara Matos da Cunha Guimarães; Rafaela Cabral Marinho; Gastón O. Carvallo; Pietro K. Maruyama; Maureen M. Murúa; André Rodrigo Rech; Lorena Vieli; Paulo E. Oliveira; Francisco E. Fontúrbel (Regional Environmental Change, 2025)

Abrupt greening observed since 2020 at Admiralty Bay, King George Island, Antarctica - Cesar Amaral; Heitor Evangelista; Dafne Anjos; Rodrigo Goldenberg-Barbosa; Anna Donato; Victor Cordeiro de Moura; Antônio Carlos de Freitas; Paulo E. A. S. Câmara; Luiz Henrique Rosa (Polar Biology, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Navigating the space between empirics and theory – Empirically stylized modelling for theorising social-ecological phenomena - Maja Schlüter; Nanda Wijermans; Blanca González-Mon; Emilie Lindkvist; Kirill Orach; Hannah Prawitz; Romina Martin; Rodrigo Martínez-Peña; Kara E. Pellowe; Udita Sanga (Environmental Modelling & Software, 2025)

Unique gastropods dominate the fauna on inactive vent sulfide features in the eastern Pacific - Lauren S. Mullineaux; Stace E. Beaulieu; Susan W. Mills; Rose Jones; Johanna N. J. Weston; Ayinde C. Best; Rodrigo Zúñiga Mouret; Michael J. Meneses; Margaret K. Tivey; Mikayla J. Harris; Amanda M. Achberger; Jason B. Sylvan (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Dietary-Based Diabetes Risk Score and breast cancer: a prospective evaluation in the SUN project - Inmaculada Aguilera-Buenosvinos; Miguel A. Martínez-González; Andrea Romanos-Nanclares; Rodrigo Sánchez-Bayona; Carlos E. de Andrea; Ligia J. Domínguez; Estefania Toledo (Journal of Physiology and Biochemistry, 2025)
An association between type 2 diabetes (T2D) and breast cancer risk has been reported. This association can be potentially explained by alteration of the insulin/IGF system. Therefore, we aimed to prospectively investigate whether a previously reported Dietary-Based Diabetes Risk Score (DDS) inversely associated with T2D was also associated with breast cancer risk in the SUN (“Seguimiento Universidad de Navarra”) cohort. We followed up 10,810 women (mean age = 35 years, SD = 11 years) for an average of 12.5 years during which 147 new cases of invasive breast cancer were diagnosed. A validated 136-item FFQ was administered at baseline and after 10 years of follow-up. The DDS (range: 11 to 55 points) positively weighted vegetables, fruit, whole cereals, nuts, coffee, low-fat dairy, fiber, PUFA; while it negatively weighted red meat, processed meats, and sugar-sweetened beverages. The DDS was categorized into tertiles. Self-reported medically diagnosed breast cancer cases were confirmed through medical records. We found a significant inverse association between the intermediate tertile of the DDS score and overall breast cancer risk (Hazard ratio, HR T2 vs. T1 = 0.55; 95% CI: 0.36–0.82) and premenopausal breast cancer risk (HR T2 = 0.26; 95% CI: 0.13–0.53), but not for the highest tertile. This association was stronger among women with a BMI < 25 kg/m 2 (p interaction : 0.029). In conclusion, moderate adherence to the DDS score was associated with a lower risk of breast cancer, especially among premenopausal women and women with a lower BMI. These findings underscore the importance of antidiabetic diet in reducing the risk of breast cancer.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Toxicity of essential oils on Callosobruchus maculatus (Fabr., 1775) in grains of Vigna unguiculata - Ozael David Valério da Silva; Paulo Roberto Ramalho Silva; Leticia Rodrigues da Silva; Rodrigo de Carvalho Brito; Kamilla de Andrade Dutra; Daniela Maria do Amaral Ferraz Navarro; Douglas Rafael e Silva Barbosa; Solange Maria de França (Journal of Plant Diseases and Protection, 2025)

Long‐haul flights and migratory routes of a nectar‐feeding bat - Theresa M. Laverty; Debbie C. Buecher; David C. Dalton; Mallory L. Davies; Fernando Gual‐Suárez; Paul A. Heady; Rodrigo A. Medellín; Mayra C. Ordóñez‐García; Samara Pérez‐Harp; A. Nayelli Rivera‐Villanueva; Brandi D. Stevenson; Kathryn E. Stoner; et al. (Ecology, 2025)

Assessment of potential ecological risk by metals in Ilha Grande Bay (Southeast Brazil) - Fabrício Leandro Damasceno; Maria Virgínia Alves Martins; Luiz Guilherme Costa Santos; João Graciano Mendonça Filho; Johann Hohenegger; Graziele Arantes Reis; Rodrigo dos Santos Diaz; Renata Cardia Rebouças; Thaise M. Senez-Mello; Sheila Arruda; Caroline Adolphsson do Nascimento; Murilo Barros Saibro; et al. (Marine Pollution Bulletin, 2025)

ReBreed21-ET: Evaluation of a rapid resynchronization program that allows timed embryo transfer every 21 days - João Paulo N. Andrade; Victor E. Gomez-León; Guilherme Madureira; Luma C. Sartori; Gustavo F. Grillo; Rafael R. Domingues; Meliton Fosado; Rodrigo V. Sala; Milo C. Wiltbank (Theriogenology, 2025)

A 9-year study of the degradation of a HDPE geomembrane liner used in different high pH mining applications - Rodrigo A. e Silva; Fady B. Abdelaal; R. Kerry Rowe (Geotextiles and Geomembranes, 2025)

Palaehoplophorini glyptodonts (Xenarthra, Glyptodontidae) from the Puerto Madryn Formation (Late Miocene), Argentine Patagonia: Diversity and biochronological implications in southern South America - Daniel Barasoain; María T. Dozo; Laureano R. González Ruiz; José I. Cuitiño; Rodrigo L. Tomassini; Alfredo E. Zurita (Geobios, 2025)

Mapping soil thickness using a mechanistic model and machine learning approaches - Nícolas Augusto Rosin; Danilo César de Mello; Benito R. Bonfatti; Alfred E. Hartemink; Tiago O. Ferreira; Nelida E.Q. Silvero; Raul Roberto Poppiel; Wanderson de S. Mendes; Gustavo Vieira Veloso; Márcio Rocha Francelino; Marcelo Rodrigo Alves; Renan Falcioni; et al. (CATENA, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Research advances and conservation needs for the protection of the Salas y Gómez and Nazca ridges: A natural and cultural heritage hotspot in the southeastern Pacific ocean - C.F. Gaymer; D. Wagner; R. Álvarez-Varas; B. Boteler; L. Bravo; C.M. Brooks; V. Chavez-Molina; D. Currie; J. Delgado; B. Dewitte; E.E. Easton; A.M. Friedlander; et al. (Marine Policy, 2025)

Current status of toxicological research on stingless bees (Apidae, Meliponini): Important pollinators neglected by pesticides' regulations - Gherardo Bogo; Martín P. Porrini; Ingrid Aguilar-Monge; Patricia Aldea-Sánchez; Grecia S. de Groot; Rodrigo A. Velarde; Aurora Xolalpa-Aroche; Diego E. Vázquez (Science of The Total Environment, 2025)

Identifying changes in the drivers of ecosystem services: Socioeconomic changes underlie reduced provision of pollination service - Pedro Joaquim Bergamo; Kátia F. Rito; Kayna Agostini; Felipe Deodato da Silva e Silva; Márcia M. Maués; André R. Rech; Lucas A. Garibaldi; Eimear Nic Lughadha; Antonio M. Saraiva; Rodrigo Y. Tsukahara; Blandina F. Viana; Grasiela Casas; et al. (Journal of Environmental Management, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

A Natural Disaster Exacerbates and Redistributes Disease Risk Among Free‐Ranging Macaques by Altering Social Structure - Alba Motes‐Rodrigo; Gregory F. Albery; Josue E. Negron‐Del Valle; Daniel Philips; Michael L. Platt; Lauren J. N. Brent; Camille Testard (Ecology Letters, 2025)
Climate change is intensifying extreme weather events, with severe implications for ecosystem dynamics. A key behavioural mechanism whereby animals may cope with such events is by altering their social structure, which in turn could influence epidemic risk. However, how and to what extent natural disasters affect disease risk via changes in sociality remains unexplored in animal populations. By simulating disease spread in free‐living rhesus macaques ( Macaca mulatta ) before and after a hurricane, we demonstrate doubled pathogen transmission rates up to 5 years following the disaster, equivalent to an increase in pathogen infectivity from 10% to 20%. Moreover, the hurricane redistributed the risk of infection across the population by exacerbating sex‐related differences. Overall, we demonstrate that natural disasters can amplify and redistribute epidemic risk in animals via changes in sociality. These observations provide unexpected further mechanisms by which extreme weather events can threaten wildlife health, population viability and spillover to humans.

Assessments of expected MPA outcomes can inform and improve biodiversity conservation: Case studies using The MPA Guide - Jenna Sullivan-Stack; Gabby N. Ahmadia; Dominic A. Andradi-Brown; Alexandra Barron; Cassandra M. Brooks; Joachim Claudet; Barbara Horta e Costa; Estradivari; Laurel C. Field; Sylvaine Giakoumi; Emanuel Gonçalves; Natalie Groulx; et al. (Marine Policy, 2024)

Reproductive outcomes of prepubertal Bos indicus beef heifers raised in a pasture-based feeding system submitted to ovulation induction strategies prior to a timed-artificial insemination protocol - Rodrigo L.O.R. Alves; Lucas O. e Silva; Carlos E.C. Consentini; Patrícia R. Cavalcanti; Mirela Balistrieri; Gustavo V. Barros; Edgar Nagle; Roberto Sartori (Theriogenology, 2024)

Realized genetic gain with reciprocal recurrent selection in a Eucalyptus breeding program - Saulo F. S. Chaves; Luiz A. S. Dias; Rodrigo S. Alves; Filipe M. Ferreira; Maurício S. Araújo; Marcos D. V. Resende; Elizabete K. Takahashi; João E. Souza; Fernando P. Leite; Samuel B. Fernandes; Kaio Olimpio G. Dias (Tree Genetics & Genomes, 2024)

Mixtures of serum concentrations of organochlorine pesticides and breastfeeding duration - Alma Rincón-Rubio; Ángel Mérida-Ortega; Rodrigo Ugalde-Resano; Mariano E. Cebrián; Lizbeth López-Carrillo (Environmental Monitoring and Assessment, 2024)

Climatic seasonality and dominant species drive the temporal dynamics in a lizard assemblage in the Arid Chaco - Monte ecotone - Rodrigo Gómez Alés; Franco Valdez Ovallez; Oscar A. Stellatelli; Ana E. Victorica Erostarbe; Rodrigo Nieva Cocilio; Ana P. Galdeano; Graciela M. Blanco; Juan Carlos Acosta (Acta Oecologica, 2024)

Visual and chemical stimuli from live prey affect feed intake, weight gain, and growth of juvenile Florida pompano (Trachinotus carolinus) - Caio A. Miyai; Tânia M. Costa; Rodrigo E. Barreto; Fernanda P. Corrêa; Alex Squadrito; Michael H. Schwarz (Aquaculture International, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Corrigendum to “Lead exposure and source attribution for a mammalian scavenger before and after a culling program” [Sci. Total Environ. 940 (2024) 173686] - Evie M. Jones; Myra E. Finkelstein; Amelia J. Koch; James M. Pay; Menna E. Jones; Rodrigo K. Hamede; Jordan O. Hampton (Science of The Total Environment, 2024)

Water level regime variation is a crucial driver for taxonomic, functional, and phylogenetic diversity in seasonally flooded tropical forests - Fernanda Moreira Gianasi; Vinícius de Andrade Maia; Aline Meyer Oliveira; Patrícia Vieira Pompeu; Cléber Rodrigo de Souza; Camila Laís Farrapo; André Maciel da Silva-Sene; Fernanda de Oliveira; Thiago Magalhães Meireles; Ana Lívia de Carvalho Rodrigues; Denise Moura Madeira; Felipe Carvalho Araújo; et al. (Science of The Total Environment, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Strategic use of 4 % deltamethrin impregnated-collar in seropositive dogs reduces the incidence of seroreactivity to visceral leishmaniasis in dogs from endemic areas - Luiz Ricardo Paes de Barros Cortez; José Eduardo Tolezano; Roberto Mitsuyoshi Hiramoto; Mário Ramos de Paula e Silva; José Eduardo Fogolin Passos; Sérgio Henrique Antônio; Valéria Medina Camprigher; Murilo José Vendramini Cuoghi; Geovanna Vioti; Fernando Ferreira; Rodrigo Martins Soares (Research in Veterinary Science, 2024)

Phonolite rock powder promotes adequate K and Na nutrition and cycling in eucalypt stands even during drought - Fábio Henrique Silva Floriano de Toledo; Yesid Alejandro Mariño Macana; Alexandre de Vicente Ferraz; Eric Victor de Oliveira Ferreira; Patrícia Andressa de Ávila; Liamara Santos Masullo; Gabriela Gonçalves Moreira; Rodrigo E. Hakamada; Cindy E. Prescott; José Leonardo de Moraes Gonçalves (New Forests, 2024)

A comprehensive characterization of the spectrum of MUTYH germline pathogenic variants in Latin America - Patricia Esperon; Florencia Neffa; Walter Pavicic; Florencia Spirandelli; Karin Alvarez; María José Mullins; Benedito Mauro Rossi; Rodrigo Felipe Góngora e Silva; Carlos Vaccaro; Francisco Lopéz-Köstner; Jorge Rugeles; Adriana Della Valle; et al. (Familial Cancer, 2024)

Adaptive potential in the face of a transmissible cancer in Tasmanian devils - Kasha Strickland; Menna E. Jones; Andrew Storfer; Rodrigo K. Hamede; Paul A. Hohenlohe; Mark J. Margres; Hamish I. McCallum; Sebastien Comte; Shelly Lachish; Loeske E. B. Kruuk (Molecular Ecology, 2024)
Emerging infectious diseases (EIDs) not only cause catastrophic declines in wildlife populations but also generate selective pressures that may result in rapid evolutionary responses. One such EID is devil facial tumour disease (DFTD) in the Tasmanian devil. DFTD is almost always fatal and has reduced the average lifespan of individuals by around 2 years, likely causing strong selection for traits that reduce susceptibility to the disease, but population decline has also left Tasmanian devils vulnerable to inbreeding depression. We analysed 22 years of data from an ongoing study of a population of Tasmanian devils on Freycinet Peninsula, Tasmania, to (1) identify whether DFTD may be causing selection on body size, by estimating phenotypic and genetic correlations between DFTD and size traits, (2) estimate the additive genetic variance of susceptibility to DFTD, and (3) investigate whether size traits or susceptibility to DFTD were under inbreeding depression. We found a positive phenotypic relationship between head width and susceptibility to DFTD, but this was not underpinned by a genetic correlation. Conversely, we found a negative phenotypic relationship between body weight and susceptibility to DFTD, and there was evidence for a negative genetic correlation between susceptibility to DFTD and body weight. There was additive genetic variance in susceptibility to DFTD, head width and body weight, but there was no evidence for inbreeding depression in any of these traits. These results suggest that Tasmanian devils have the potential to respond adaptively to DFTD, although the realised evolutionary response will critically further depend on the evolution of DFTD itself.

Comparative Population Genomic Diversity and Differentiation in Trapdoor Spiders and Relatives (Araneae, Mygalomorphae) - Rodrigo Monjaraz‐Ruedas; James Starrett; Lacie Newton; Jason E. Bond; Marshal Hedin (Molecular Ecology, 2024)
Although patterns of population genomic variation are well‐studied in animals, there remains room for studies that focus on non‐model taxa with unique biologies. Here we characterise and attempt to explain such patterns in mygalomorph spiders, which are generally sedentary, often occur as spatially clustered demes and show remarkable longevity. Genome‐wide single nucleotide polymorphism (SNP) data were collected for 500 individuals across a phylogenetically representative sample of taxa. We inferred genetic populations within focal taxa using a phylogenetically informed clustering approach, and characterised patterns of diversity and differentiation within‐ and among these genetic populations, respectively. Using phylogenetic comparative methods we asked whether geographical range sizes and ecomorphological variables (behavioural niche and body size) significantly explain patterns of diversity and differentiation. Specifically, we predicted higher genetic diversity in genetic populations with larger geographical ranges, and in small‐bodied taxa. We also predicted greater genetic differentiation in small‐bodied taxa, and in burrowing taxa. We recovered several significant predictors of genetic diversity, but not genetic differentiation. However, we found generally high differentiation across genetic populations for all focal taxa, and a consistent signal for isolation‐by‐distance irrespective of behavioural niche or body size. We hypothesise that high population genetic structuring, likely reflecting combined dispersal limitation and microhabitat specificity, is a shared trait for all mygalomorphs. Few studies have found ubiquitous genetic structuring for an entire ancient and species‐rich animal clade.

A Late-Pleistocene confined volcanic debris avalanche promoted by hydrothermal alteration at the Tinguiririca volcano (Andes of Central Chile) - Jorge E. Romero; Tania Villaseñor; Rodrigo Arcos; Edmundo Polanco; Laura Becerril; Edgar Pio; Domingo Jullian (Journal of Volcanology and Geothermal Research, 2024)

Breast cancer immunophenotypes and serum organochlorine pesticides in Mexican women: Mixture exposure approach - Rodrigo Ugalde-Resano; Ángel Mérida-Ortega; Mariano E. Cebrián; Lizbeth López-Carrillo (Environmental Pollution, 2024)

Relation between ice nuclei particles concentration and aerosol counting at different sizes - María Laura López; Gustavo G. Palancar; Rodrigo E. Bürgesser (Atmospheric Research, 2024)

A Cluster of Diutina catenulata Funguria in Patients with Coronavirus Disease 2019 (COVID-19) Hospitalized in a Tertiary Reference Hospital from Rio de Janeiro, Brazil - Rodrigo Almeida-Paes; Marcus de Melo Teixeira; Fernanda Alves de Oliveira; Marcos de Abreu Almeida; Fernando Almeida-Silva; Kim Mattos Geraldo; Estevão Portela Nunes; Bridget M. Baker; Jason E. Stajich; Beatriz Grinsztejn; Valdilea Gonçalves Veloso; Andrea d’Avila Freitas; et al. (Current Microbiology, 2024)

Socially Acceptable Feed Formulations May Impact the Voluntary Feed Intake and Growth, but Not Robustness of Nile Tilapia (Oreochromis niloticus) - Rodrigo Mendes; Paulo Rema; Jorge Dias; Ana Teresa Gonçalves; Rita Teodósio; Sofia Engrola; Francisco J. Sánchez-Vázquez; Luís E. C. Conceição (Fishes, 2024)
Society is becoming more demanding with aquaculture’s environmental footprint and animal wellbeing. In order to potentially mitigate these concerns, feed formulations could be based on eco-efficient (circular economy-driven) or organic ingredients. This study aimed to investigate the growth performance, feed utilization, and health status of juvenile Nile tilapia (Oreochromis niloticus) when fed with such feeds. The growth trial lasted for 8 weeks, and fish had an initial weight of 31.0 ± 0.5 g (mean ± SD). Fish were fed until visual satiation, in quadruplicate, with one of three isonitrogenous and isoenergetic experimental feeds: a commercial-like feed without fishmeal (PD), a diet based on ingredients compatible with organic certification (ORG), or a feed formulated using circular economy-driven subproducts and emergent ingredients (ECO). Fish fed ECO showed a tendency for decreased feed intake, while ORG fish significantly reduced their intake compared to those fed PD. Consequently, fish fed ECO (62.7 ± 5.4 g) exhibited almost half the growth than those fed PD (107.8 ± 6.1 g), while ORG fish almost did not increase their weight (32.7 ± 1.3 g). ECO and ORG diets had a lower digestibility for protein, lipid, and energy when compared to PD. Feed utilization of fish fed ECO or ORG was also lower than those fed PD. From the health-related genes analyzed, only glutathione reductase (gsr) showed statistically significant differences, being more expressed in fish-fed ECO than those fed PD. Thus, even when such novel formulations induced extreme effects on voluntary feed intake, their impact was noted only in fish growth, but not in robustness.

P01-64 Approaches to mitigate known safety liabilities of immunomodulatory (IMiDs) drugs used in heterobifunctional degraders - M. Rodrigo; J. Komen; S. Regan; G. Hamza; A. Andres; E. Leonard; I. Michaelides; K. Moreau (Toxicology Letters, 2024)

Contamination risk by heavy metals and enzymatic stoichiometry in agricultural soils under intense use of pesticides - Thais da Silva Martins; Kaio Gráculo Vieira Garcia; Yuri Jacques Agra Bezerra da Silva; Mateus Guimarães da Silva; Sheilla Silva e Serpa; Rodrigo Alves Bezerra; Crisanto Dias Teixeira Filho; Rivelino Martins Cavalcante; Cácio Luiz Boechat; Arthur Prudêncio de Araujo Pereira; Maria Eugenia Ortiz Escobar (Environmental Monitoring and Assessment, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Lead exposure and source attribution for a mammalian scavenger before and after a culling program - Evie M. Jones; Amelia J. Koch; James M. Pay; Menna E. Jones; Rodrigo K. Hamede; Jordan O. Hampton (Science of The Total Environment, 2024)

Light-activated conjugated polymer nanoparticles to defeat pathogens associated with bovine mastitis - Sol R. Martínez; Matías Caverzan; Luis E. Ibarra; Virginia Aiassa; Luciana Bohl; Carina Porporatto; María L. Gómez; Carlos A. Chesta; Rodrigo E. Palacios (Journal of Photochemistry and Photobiology B: Biology, 2024)

Conservation opportunities for rare and endemic tropical mistletoes - Rodrigo F. Fadini; Claudenir S. Caires; Greta A. Dettke; Marcelo O.T. Menezes; Francisco E. Fontúrbel (Flora, 2024)

Song amplitude variation in Masked Gnatcatcher (Polioptila dumicola) as response to traffic noise - Evelina J. León; Rodrigo E. Lorenzón; Lorena V. Sovrano; Adolfo H. Beltzer; Paola M. Peltzer (Urban Ecosystems, 2024)

Nile tilapia and gilthead seabream dietary self-selection of alternative feeds - Rodrigo Mendes; Luís E. C. Conceição; Jorge Dias; Sofia Engrola; Francisco J. Sánchez-Vázquez (Fish Physiology and Biochemistry, 2024)
Classical assessments of new fish feeds are anthropocentric, focusing mainly on growth. Although this methodology is accurate, it does not consider the fish’ perspective. This study aimed to investigate the behavioural responses and feed preferences of Nile tilapia ( Oreochromis niloticus ) and gilthead seabream ( Sparus aurata ) through a self-selection trial using self-feeders. Both species were offered three feeds: a control (PD) commercial-like feed and two diets (ORG1 and ORG2) formulated with different inclusions of alternative ingredients to address some of the current environmental concerns and/or ethical issues often associated with commercial formulations. Three groups of tilapia with an average weight of 163.0 g ± 4.3 g (mean ± SD) and four groups of seabreams with 174.7 g ± 27.0 g were tested. Tilapia exhibited a preference for ORG2 (46.5%), influenced by the sensory properties of the feed and post-ingestion signals. Seabream did not show a preference for any feed. These findings highlight the effectiveness of self-selection experiments in allowing fish to express their feeding behaviour and preferences. Therefore, this approach should be considered in the initial screening and design of new aquaculture feeds and ingredients.

Timed-artificial insemination protocols for Bos indicus beef heifers: Evaluation of protocol length and variations in prostaglandin F2α treatments - Rodrigo L.O.R. Alves; Lucas O.e Silva; Mateus A.da Silva; Carlos E.C. Consentini; José R.S. Gonçalves; Leonardo de F. e Melo; Marcelo B. Rodrigues; Roberto Sartori (Theriogenology, 2024)

Fast horizontal radial plume mapping of N2O using open-path absorption spectroscopy with a quantum-cascade laser - Peter John Rodrigo; Henning E. Larsen; A.S. Ashik; Nathalia Thygsen Vechi; Konstantinos Kissas; Anders Michael Fredenslund; Charlotte Scheutz; Christian Pedersen (Atmospheric Environment, 2024)

Influence of the Super El Niño event during 2015/2016 on the aerosol properties and lightning activity in subtropical South America - Verónica M. Tur; Rodrigo E. Bürgesser; Diego Gaiero; María Laura López (Atmospheric Research, 2024)

Conversion of microalgae into renewable hydrocarbons through catalytic pyrolysis: A bibliometric analysis - Joemil Oliveira de Deus Junior; José Luiz Francisco Alves; Vitor Rodrigo de Melo e Melo; Ângelo Anderson Silva de Oliveira; Karine Fonseca Soares de Oliveira; Dulce Maria de Araújo Melo; Renata Martins Braga (Algal Research, 2024)

Tree demographic strategies largely overlap across succession in Neotropical wet and dry forest communities - Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Dylan Craven; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Bruno Hérault; Catarina C. Jakovac; et al. (Ecology, 2024)
Secondary tropical forests play an increasingly important role in carbon budgets and biodiversity conservation. Understanding successional trajectories is therefore imperative for guiding forest restoration and climate change mitigation efforts. Forest succession is driven by the demographic strategies—combinations of growth, mortality and recruitment rates—of the tree species in the community. However, our understanding of demographic diversity in tropical tree species stems almost exclusively from old‐growth forests. Here, we assembled demographic information from repeated forest inventories along chronosequences in two wet (Costa Rica, Panama) and two dry (Mexico) Neotropical forests to assess whether the ranges of demographic strategies present in a community shift across succession. We calculated demographic rates for >500 tree species while controlling for canopy status to compare demographic diversity (i.e., the ranges of demographic strategies) in early successional (0–30 years), late successional (30–120 years) and old‐growth forests using two‐dimensional hypervolumes of pairs of demographic rates. Ranges of demographic strategies largely overlapped across successional stages, and early successional stages already covered the full spectrum of demographic strategies found in old‐growth forests. An exception was a group of species characterized by exceptionally high mortality rates that was confined to early successional stages in the two wet forests. The range of demographic strategies did not expand with succession. Our results suggest that studies of long‐term forest monitoring plots in old‐growth forests, from which most of our current understanding of demographic strategies of tropical tree species is derived, are surprisingly representative of demographic diversity in general, but do not replace the need for further studies in secondary forests.

Ecological niche modeling analysis (Cx. pipiens), potential risk and projection of Dirofilaria spp. infection in Greece - Iván Rodríguez-Escolar; Ricardo E. Hernández-Lambraño; José Ángel Sánchez-Agudo; Manuel Collado-Cuadrado; Georgios Sioutas; Elias Papadopoulos; Rodrigo Morchón (Veterinary Parasitology, 2024)

Environmental impact assessment of the electrokinetic adsorption barriers to remove different herbicides from agricultural soils - C.M. Fernández-Marchante; E. Vieira dos Santos; F.L. Souza; C.A. Martínez-Huitle; A. Rodríguez-Gómez; J. Lobato; M.A. Rodrigo (Science of The Total Environment, 2024)

Determinants of biogeographical distribution of grasses in grasslands of South America - Helena Streit; Rodrigo S. Bergamin; Bianca O. Andrade; Alice Altesor; Felipe Lezama; Susana Perelman; Sandra C. Müller; Gerhard E. Overbeck (Perspectives in Plant Ecology, Evolution and Systematics, 2024)

Relative Performance of Volume of Distribution Prediction Methods for Lipophilic Drugs with Uncertainty in LogP Value - Ana L. Coutinho; Rodrigo Cristofoletti; Fang Wu; Abdullah Al Shoyaib; Jennifer Dressman; James E. Polli (Pharmaceutical Research, 2024)
Purpose The goal was to assess, for lipophilic drugs, the impact of logP on human volume of distribution at steady-state (VD ss ) predictions, including intermediate fut and Kp values, from six methods: Oie-Tozer, Rodgers-Rowland (tissue-specific Kp and only muscle Kp), GastroPlus, Korzekwa-Nagar, and TCM-New. Method A sensitivity analysis with focus on logP was conducted by keeping pKa and fup constant for each of four drugs, while varying logP. VD ss was also calculated for the specific literature logP values. Error prediction analysis was conducted by analyzing prediction errors by source of logP values, drug, and overall values. Results The Rodgers-Rowland methods were highly sensitive to logP values, followed by GastroPlus and Korzekwa-Nagar. The Oie-Tozer and TCM-New methods were only modestly sensitive to logP. Hence, the relative performance of these methods depended upon the source of logP value. As logP values increased, TCM-New and Oie-Tozer were the most accurate methods. TCM-New was the only method that was accurate regardless of logP value source. Oie-Tozer provided accurate predictions for griseofulvin, posaconazole, and isavuconazole; GastroPlus for itraconazole and isavuconazole; Korzekwa-Nagar for posaconazole; and TCM-New for griseofulvin, posaconazole, and isavuconazole. Both Rodgers-Rowland methods provided inaccurate predictions due to the overprediction of VD ss . Conclusions TCM-New was the most accurate prediction of human VD ss across four drugs and three logP sources, followed by Oie-Tozer. TCM-New showed to be the best method for VD ss prediction of highly lipophilic drugs, suggesting BPR as a favorable surrogate for drug partitioning in the tissues, and which avoids the use of fup.

Heavy rains and hydrogeological disasters on February 18th–19th, 2023, in the city of São Sebastião, São Paulo, Brazil: from meteorological causes to early warnings - Jose A. Marengo; Ana P. Cunha; Marcelo E. Seluchi; Pedro I. Camarinha; Giovanni Dolif; Vinicius B. Sperling; Enner H. Alcântara; Andrea M. Ramos; Marcio M. Andrade; Rodrigo A. Stabile; José Mantovani; Edward Park; et al. (Natural Hazards, 2024)

On the reproduction of the solitary cold-water coral Fungiacyathus fragilis Sars, 1872 (Cnidaria: Scleractinia), and a new record in the SW Atlantic Ocean deep sea - Rodrigo N. Calderón; Pablo E. Penchaszadeh; Daniel Lauretta (Coral Reefs, 2024)

Looking for non-hermaphrodite cacti: multidisciplinary studies in Gymnocalycium bruchii endemic to central Argentina - Natalia E. Delbón; Nayla L. Aliscioni; Marina Lorenzati; Sergio García; Rodrigo B. Singer; Diego E. Gurvich (Plant Reproduction, 2024)

Ants (Hymenoptera: Formicidae) in subterranean natural cavities of Minas Gerais, Brazil - Natalia Ladino; Rodrigo M. Feitosa; Robson de Almeida Zampaulo; John E. Lattke (Biologia, 2024)

Reply to the comment on Sanz-Pérez et al., “Paleoenvironment and paleoecology associated with the early phases of the Great American Biotic Interchange based on stable isotope analysis of fossil mammals and new U Pb ages from the Pampas of Argentina” [Palaeogeography, Palaeoclimatology, Palaeoecology 634 (2024), 111917] - Dánae Sanz-Pérez; Claudia I. Montalvo; Adriana E. Mehl; Rodrigo L. Tomassini; Manuel Hernández Fernández; Laura Domingo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Aqueous arsenic(V) remediation and redox transformation of arsenic(III) to arsenic(V) using Fe3O4/Douglas fir biochar - Prashan M. Rodrigo; Chanaka M. Navarathna; Bailey N. Bullard; Brooke R. Hoffman; Beverly L. Venson; Holden Honigfort; Garrett L. Timmons; Maria L. Montes; Rooban V.K.G. Thirumalai; Sean L. Stokes; Charles U. Pittman; Todd E. Mlsna (Journal of Cleaner Production, 2024)

Carcinogenic, non-carcinogenic risk, and attributable cases to organochlorine pesticide exposure in women from Northern Mexico - Alma Rincón-Rubio; Ángel Mérida-Ortega; Rodrigo Ugalde-Resano; Brenda Gamboa-Loira; Stephen J. Rothenberg; Fernando Bejarano González; Mariano E. Cebrián; Lizbeth López-Carrillo (Environmental Monitoring and Assessment, 2024)

Predicting and reducing potential parasite infection between migratory livestock and resident Asiatic ibex of Pin valley, India - Munib Khanyari; Rodrigo Oyanedel; Abhirup Khara; Manvi Sharma; E J Milner-Gulland; Kulbhushansingh R Suryawanshi; Hannah Rose Vineer; Eric R Morgan (Journal of Biosciences, 2024)

Human habitat modification, not apex scavenger decline, drives isotopic niche variation in a carnivore community - Olivia Bell; Menna E. Jones; Manuel Ruiz-Aravena; David G. Hamilton; Sebastien Comte; Rowena Hamer; Rodrigo K. Hamede; Jason Newton; Stuart Bearhop; Robbie A. McDonald (Oecologia, 2024)
Top carnivores can influence the structure of ecological communities, primarily through competition and predation; however, communities are also influenced by bottom-up forces such as anthropogenic habitat disturbance. Top carnivore declines will likely alter competitive dynamics within and amongst sympatric carnivore species. Increasing intraspecific competition is generally predicted to drive niche expansion and/or individual specialisation, while interspecific competition tends to constrain niches. Using stable isotope analysis of whiskers, we studied the effects of Tasmanian devil Sarcophilus harrisii declines upon the population- and individual-level isotopic niches of Tasmanian devils and sympatric spotted-tailed quolls Dasyurus maculatus subsp. maculatus. We investigated whether time since the onset of devil decline (a proxy for severity of decline) and landscape characteristics affected the isotopic niche breadth and overlap of devil and quoll populations. We quantified individual isotopic niche breadth for a subset of Tasmanian devils and spotted-tailed quolls and assessed whether between-site population niche variation was driven by individual-level specialisation. Tasmanian devils and spotted-tailed quolls demonstrated smaller population-level isotopic niche breadths with increasing human-modified habitat, while time since the onset of devil decline had no effect on population-level niche breadth or interspecific niche overlap. Individual isotopic niche breadths of Tasmanian devils and spotted-tailed quolls were narrower in human-modified landscapes, likely driving population isotopic niche contraction, however, the degree of individuals’ specialisation relative to one another remained constant. Our results suggest that across varied landscapes, mammalian carnivore niches can be more sensitive to the bottom-up forces of anthropogenic habitat disturbance than to the top-down effects of top carnivore decline.

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

An assessment of dip-slip versus strike-slip faulting modes along the Patagonian Andes (39°-50° S) and their related orogenic models - Rodrigo J. Suárez; Miguel E. Ramos; Christian Sue; Matías Ghiglione; Vanesa Barberón; Paulo Quezada; Sandrine Roy (International Geology Review, 2024)

Protecting human health and the environment against siloxanes: The role and effectiveness of wastewater treatment technologies - Andres E. Ortiz-Ardila; Juan D. Restrepo; Largus T. Angenent; Joseph G. Usack; Rodrigo A. Labatut (Critical Reviews in Environmental Science and Technology, 2024)

Lean-circular maturity model (LCMM) for companies' self-assessment in terms of process, product and life cycle thinking - Marina Hernandes de Paula e Silva; Ricardo Coser Mergulhão; José Geraldo Vidal Vieira; Andrea Brasco Pampanelli; Rodrigo Salvador; Diogo Aparecido Lopes Silva (Waste Management, 2024)

Influence of GnRH analog and dose on LH release and ovulatory response in Bos indicus heifers and cows on day seven of the estrous cycle - Lucas O. e Silva; Jessica C.L. Motta; Abraham L. Oliva; Guilherme Madureira; Rodrigo L.O.R. Alves; Natália P. Folchini; Mateus A. da Silva; Taynara J.B. da Silva; Carlos E.C. Consentini; Milo C. Wiltbank; Roberto Sartori (Theriogenology, 2024)

Paleoenvironment and paleoecology associated with the early phases of the Great American Biotic Interchange based on stable isotope analysis of fossil mammals and new U–Pb ages from the Pampas of Argentina - Dánae Sanz-Pérez; Claudia I. Montalvo; Adriana E. Mehl; Rodrigo L. Tomassini; Manuel Hernández Fernández; Laura Domingo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Inactivation of waterborne Klebsiella pneumoniae with ozone to diminish the risk of hospital effluents using an absorption-based process - Sergio E. Correia; Víctor Pertegal; Miguel Herraiz-Carboné; Engracia Lacasa; Pablo Cañizares; Manuel A. Rodrigo; Cristina Sáez (Journal of Water Process Engineering, 2024)

Early development of the Patagonian fold and thrust belt and the onset of foreland sedimentation in the Austral-Magallanes basin - Maximiliano Naipauer; Matías C. Ghiglione; Martín H. Senger; Juan Albano; Inés Aramendía; Gonzalo Ronda; Rodrigo Suárez; Miguel E. Ramos; Victor A. Valencia (Journal of South American Earth Sciences, 2024)

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

Determination of organic contaminants in L'Albufera Natural Park using microporous polyethylene tube passive samplers: An environmental risk assessment - Yolanda Soriano; Rodrigo Alvarez-Ruiz; Joseph E. Clokey; Sara Ghorbani Gorji; Sarit L. Kaserzon; Yolanda Picó (Science of The Total Environment, 2023)

Light use efficiency declines with water deficit and age in Eucalyptus plantations across Brazil - Rodrigo E. Hakamada; Dan Binkley; Eduardo Moré Mattos (Forest Ecology and Management, 2023)

Establishing morphological and molecular evidences to support the identification of “yerba buena” (Mentha × villosa Huds.) in the Philippines - Kristine Joyce O. Quiñones; Renerio P. Gentallan; Michael Cedric B. Bartolome; Roselle E. Madayag; Emmanuel Bonifacio S. Timog; Juan Rodrigo A. Vera Cruz; Nadine B. Coronado; Leah E. Endonela; Teresita H. Borromeo; Nestor C. Altoveros; Bartimeus Buiene S. Alvaran; Reneliza D. Cejalvo (Journal of Crop Science and Biotechnology, 2023)

An extension of the characteristic curve model of plant species behavior in heavy metal soils - Elizabeth J. Lam; Brian F. Keith; Jaume Bech; María E. Gálvez; Rodrigo Rojas; Fernando A. Alvarez; Vicente Zetola; Ítalo L. Montofré (Environmental Geochemistry and Health, 2023)

Impact of grasslands grazed by cattle on taxonomic and functional aspects of bird assemblages in floodplain wetlands of the Paraná River - Rodrigo E. Lorenzón; Lorena V. Sovrano; Evelina J. León; Adolfo H. Beltzer; Ana L. Ronchi-Virgolini (Biodiversity and Conservation, 2023)

Development of healthy synbiotic corn-based snack: Nutritional composition and effect of agave fructan-alginate coating on survival of Lactobacillus acidophilus - Valeria Castillo-Escandón; Gabriela Ramos-Clamont Montfort; Alma Rosa Islas Rubio; Jolanta E. Marszalek; Rodrigo Subiría-Cueto; Silvia Fernández Michel (Journal of Cereal Science, 2023)

A novel strategy to predict clonal composites by jointly modeling spatial variation and genetic competition - Filipe M. Ferreira; Saulo F.S. Chaves; Leonardo L. Bhering; Rodrigo S. Alves; Elizabete K. Takahashi; João E. Sousa; Marcos D.V. Resende; Fernando P. Leite; Salvador A. Gezan; José M.S. Viana; Samuel B. Fernandes; Kaio O.G. Dias (Forest Ecology and Management, 2023)

Facing the treatment of polymedicated effluents using gaseous ozone electrochemically generated - Ángela Moratalla; Sergio E. Correia; Engracia Lacasa; Pablo Murillo; Pablo Cañizares; Manuel A. Rodrigo; Cristina Sáez (Journal of Water Process Engineering, 2023)

Metagenomic and isotopic signatures of the Amazon River plume into the southern red snapper fish (Lutjanus purpureus) - Luciane de C. Nogueira; Nils E. Asp; Carlos E. Rezende; Rodrigo Petry C. Sousa; Breno Barros; Raphael Paixão; Pedro V. Gatts; Cristiane C. Thompson; Ronaldo B. Francini-Filho; Marcelo Vallinoto; Fabiano L. Thompson (Estuarine, Coastal and Shelf Science, 2023)

Indolealkylamines in the venom of the scorpion Thorellius intrepidus - Rodrigo Ibarra-Vega; Juana María Jiménez-Vargas; Armando Pineda-Contreras; Francisco Javier Martínez-Martínez; Carlos Eduardo Barajas-Saucedo; Héctor García-Ortega; Nancy E. Magaña-Vergara; Lourival D. Possani; Gerardo Corzo; Mario Alberto Gaitan-Hinojosa; Oscar Fernando Vázquez-Vuelvas; Fernando Zamudio; et al. (Toxicon, 2023)

Earliest Acheulian paleolandscape reveals a 1.7 million-year-old megasite at Olduvai Gorge (Tanzania) - M. Domínguez-Rodrigo; D. Uribelarrea; F. Diez-Martín; Mabulla A; A. Gidna; L. Cobo-Sánchez; D.M. Martín-Perea; E. Organista; R. Barba; E. Baquedano (Quaternary Science Reviews, 2023)

Factors affecting invasion process of a megadiverse country by two exotic bird species - Adrián Ceja-Madrigal; Rodrigo Pacheco-Muñoz; Adolfo G. Navarro-Sigüenza; Pilar Rodríguez; Margarita Jiménez-Cruz; Jorge E. Schondube (Anthropocene, 2023)

Heterospecific pollen deposition in understory plants of a forest in central Amazon - Rodrigo Taveira; William E. Magnusson; Juliana Hipólito (Flora, 2023)

Amber and the Cretaceous Resinous Interval - Xavier Delclòs; Enrique Peñalver; Eduardo Barrón; David Peris; David A. Grimaldi; Michael Holz; Conrad C. Labandeira; Erin E. Saupe; Christopher R. Scotese; Mónica M. Solórzano-Kraemer; Sergio Álvarez-Parra; Antonio Arillo; et al. (Earth-Science Reviews, 2023)

Amazonian ichthyoplankton assessment via DNA metabarcoding: A baseline for detecting spawning sites of migratory fishes - Lara E. Silva; Rodrigo R. Domingues; Naiara G. Sales; Priscila M.S. Villela; Camila Barbosa Silva; Alexandre W.S. Hilsdorf (Biological Conservation, 2023)

Glutamine supplementation accelerates functional recovery of EDL muscles after injury by modulating the expression of S100 calcium-binding proteins - Audrei R. Santos; Tatiana E. Koike; Alana M. Santana; Natalya C. Miranda; Rodrigo A. Dell Aquila; Thiago C. Silva; Marcelo S. Aoki; Elen H. Miyabara (Histochemistry and Cell Biology, 2023)

Metabolomic Evenness Underlies Intraspecific Differences Among Lineages of a Wetland Grass - Ana L. Salgado; Andrea E. Glassmire; Brian E. Sedio; Rodrigo Diaz; Michael J. Stout; Jan Čuda; Petr Pyšek; Laura A. Meyerson; James T. Cronin (Journal of Chemical Ecology, 2023)

Failure to predict amikacin elimination in critically ill patients with cancer based on the estimated glomerular filtration rate: applying PBPK approach in a therapeutic drug monitoring study - João Paulo Telles; Mariana Suelotto Diegues; Karen Cristina Migotto; Olivia de Souza Borges; Rodrigo Reghini; Brenda Vianna Gavazza; Leonardo Pinto; Pedro Caruso; Ivan Leonardo França e Silva; Stephan Schmidt; Fernanda de Lima Moreira (European Journal of Clinical Pharmacology, 2023)

Rhomb-I, a P–I metalloproteinase from Lachesis muta rhombeata venom degrades vessel extra cellular matrix components and impairs platelet aggregation - Valéria Gonçalves de Alvarenga; Luciana S. Oliveira; Gustavo O. Santos; Dan E. Vivas-Ruiz; Márcia Helena Borges; Rodrigo C.G. de Souza; Johannes A. Eble; Ana Maria Moura-da-Silva; Eladio F. Sanchez (Toxicon, 2023)

Iron and silicic acid addition effects on early spring macronutrient drawdown and biogenic silica production of Patagonia estuarine waters - Rodrigo Torres; Rob Sherrell; Brian Reid; Gemita Pizarro; Máximo Frangópulos; Emilio Alarcón; Magdalena Márquez; Francisco Díaz-Rosas; Eduardo Menschel; Humberto E. González; Paulo Moreno-Meynard; Paulina Montero; et al. (Progress in Oceanography, 2023)

Metabolomics profile of equine seminal plasma - Veronica LC Bueno; Henrique BA Bastos; Gustavo R Larentis; Gustavo HZ Winter; Rodrigo C Mattos; Sandra Mara E Rechsteiner (Journal of Equine Veterinary Science, 2023)

The impact of inosine on hippocampal synaptic transmission and plasticity involves the release of adenosine through equilibrative nucleoside transporters rather than the direct activation of adenosine receptors - Pedro Valada; Sonja Hinz; Christin Vielmuth; Cátia R. Lopes; Rodrigo A. Cunha; Christa E. Müller; João Pedro Lopes (Purinergic Signalling, 2023)

Responses of ground-dwelling birds and mammals to local environmental variables and human pressure in an Amazonian protected area - Carlos R. Brocardo; Dian C. P. Rosa; Arlison B. Castro; Clarissa Rosa; Kelly Torralvo; Pedro Pequeno; William E. Magnusson; Rodrigo F. Fadini (European Journal of Wildlife Research, 2023)

Argentine Navy Icebreaker Ship “Almirante Irizar” Sludge Microbial Composition Analysis for Biohydrogen Production - Rodrigo E. García; Natalia Pin Viso; Fernando A. Gerosa; Verónica Nishinakamasu; Andrea F. Puebla; Marisa D. Farber; María J. Lavorante (BioEnergy Research, 2023)

Successional shifts in tree demographic strategies in wet and dry Neotropical forests - Nadja Rüger; Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Dylan Craven; Bruno Hérault; et al. (Global Ecology and Biogeography, 2023)
Aim Tropical forest succession and associated changes in community composition are driven by species demographic rates, but how demographic strategies shift during succession remains unclear. Our goal was to identify generalities in demographic trade‐offs and successional shifts in demographic strategies across Neotropical forests that cover a large rainfall gradient and to test whether the current conceptual model of tropical forest succession applies to wet and dry forests. Location Mexico and Central America. Time period 1985–2018. Major taxa studied Trees. Methods We used repeated forest inventory data from two wet and two dry forests to quantify demographic rates of 781 tree species. For each forest, we explored the main demographic trade‐offs and assigned tree species to five demographic groups by performing a weighted principal components analysis to account for differences in sample size. We aggregated the basal area and abundance across demographic groups to identify successional shifts in demographic strategies over the entire successional gradient from very young ( Results Across all forests, we found two demographic trade‐offs, namely the growth–survival trade‐off and the stature–recruitment trade‐off, enabling the data‐driven assignment of species to five demographic strategies. Fast species dominated early in succession and were then replaced by long‐lived pioneers in three forests. Intermediate and slow species increased in basal area over succession in all forests, but, in contrast to the current conceptual model, long‐lived pioneers continued to dominate until the old‐growth stage in all forests. The basal area of short‐lived breeders was low across all successional stages. Main conclusions The current conceptual model of Neotropical forest succession should be revised to incorporate the dominance of long‐lived pioneers in late‐successional and old‐growth forests. Moreover, the definition of consistent demographic strategies that show clear dominance shifts across succession substantially improves the mechanistic understanding and predictability of Neotropical forest succession.

Facing climate change and improving emergency responses in Southern America by analysing urban cyclonic wind events - Raúl Pérez-Arévalo; José Luis Serrano-Montes; Juan E. Jiménez-Caldera; Jesús Rodrigo-Comino; Pete Smith; Andrés Caballero-Calvo (Urban Climate, 2023)

Description of two cultivated and two uncultivated new Salinibacter species, one named following the rules of the bacteriological code: Salinibacter grassmerensis sp. nov.; and three named following the rules of the SeqCode: Salinibacter pepae sp. nov., Salinibacter abyssi sp. nov., and Salinibacter pampae sp. nov. - Tomeu Viver; Roth E. Conrad; Marianna Lucio; Mourad Harir; Mercedes Urdiain; Juan F. Gago; Ana Suárez-Suárez; Esteban Bustos-Caparros; Rodrigo Sanchez-Martinez; Eva Mayol; Federico Fassetta; Jinfeng Pang; et al. (Systematic and Applied Microbiology, 2023)

Selection of indicator contaminants of emerging concern when reusing reclaimed water for irrigation — A proposed methodology - P. Verlicchi; V. Grillini; E. Lacasa; E. Archer; P. Krzeminski; A.I. Gomes; V.J.P. Vilar; M.A. Rodrigo; J. Gäbler; L. Schäfer (Science of The Total Environment, 2023)

Dynamic load allowance of long-span modular steel bridges - J. Chordà-Monsonís; E. Moliner; P. Galvín; M.D. Martínez-Rodrigo; E. Zacchei; A. Tadeu; I. Ferraz; A. Romero (Engineering Structures, 2023)

New and revised paleomagnetic data from the southern central andes: Testing tectonic rotations - Florencia N. Milanese; Augusto E. Rapalini; Lucía Sagripanti; Silvana Geuna; Mark J. Dekkers; Rodrigo Feo; Pablo Franceschinis; Donaldo Bran; Andrés Folguera (Journal of South American Earth Sciences, 2023)

Antimicrobial activity of ceftibuten-avibactam against a global collection of Enterobacterales from patients with urinary tract infections (2021) - Helio S. Sader; Cecilia G. Carvalhaes; Michael D. Huband; Rodrigo E. Mendes; Mariana Castanheira (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
We evaluated the in vitro activity of ceftibuten-avibactam against Enterobacterales causing urinary tract infection (UTI). A total of 3216 isolates (1/patient) were consecutively collected from patients with UTI in 72 hospitals from 25 countries in 2021 then susceptibility tested by CLSI broth microdilution. Ceftibuten-susceptible breakpoints currently published by EUCAST (≤ 1 mg/L) and CLSI (≤ 8 mg/L) were applied to ceftibuten-avibactam for comparison. The most active agents were ceftibuten-avibactam (98.4%/99.6% inhibited at ≤ 1/ ≤ 8 mg/L), ceftazidime-avibactam (99.6% susceptible [S]), amikacin (99.1%S), and meropenem (98.2%S). Ceftibuten-avibactam (MIC 50/90 , 0.03/0.06 mg/L) was fourfold more potent than ceftazidime-avibactam (MIC 50/90 , 0.12/0.25 mg/L) based on MIC 50/90 values. The most active oral agents were ceftibuten (89.3%S; 79.5% inhibited at ≤ 1 mg/L), levofloxacin (75.4%S), and trimethoprim-sulfamethoxazole (TMP-SMX; 73.4%S). Ceftibuten-avibactam inhibited 97.6% of isolates with an extended-spectrum β-lactamase phenotype, 92.1% of multidrug-resistant isolates, and 73.7% of carbapenem-resistant Enterobacterales (CRE) at ≤ 1 mg/L. The second most active oral agent against CRE was TMP-SMX (24.6%S). Ceftazidime-avibactam was active against 77.2% of CRE isolates. In conclusion, ceftibuten-avibactam was highly active against a large collection of contemporary Enterobacterales isolated from patients with UTI and exhibited a similar spectrum to ceftazidime-avibactam. Ceftibuten-avibactam may represent a valuable option for oral treatment of UTI caused by multidrug-resistant Enterobacterales.

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Amazon raw clay as a precursor of a clay-based adsorbent: experimental study and DFT analysis for the adsorption of Basic Yellow 2 dye - Emanuele D. V. Duarte; Wedja T. Vieira; Rodrigo O. Góes; Luiz E. C. de Azevedo; Melissa G. A. Vieira; Meuris G. C. da Silva; Samira M. L. de Carvalho (Environmental Science and Pollution Research, 2023)

The oldest Andean synorogenic fossiliferous deposits of the Miocene Cerro Azul Formation, central Argentina - Claudia I. Montalvo; Alicia Folguera; Esperanza Cerdeño; Diego H. Verzi; María E. Pérez; Renata Sostillo; Rodrigo L. Tomassini (Journal of South American Earth Sciences, 2023)

3D analysis of railway induced vibrations on skew girder bridges including ballast track–bridge interaction effects - J.C. Sánchez-Quesada; A. Romero; P. Galvín; E. Moliner; M.D. Martínez-Rodrigo (Engineering Structures, 2023)

Alunite supergroup minerals from advanced argillic alteration assemblage in the southern Atacama Desert as indicators of paleo-hydrothermal and supergene environments - Jorge E. Morales-Leal; Eduardo Campos; Kalin Kouzmanov; Rodrigo Riquelme (Mineralium Deposita, 2023)

Species movements within biogeographic regions: exploring the distribution of transplanted mollusc species in South America - Gustavo Darrigran; Ignacio Agudo-Padrón; Pedro Baez; Carlos Belz; Franz Cardoso; Gonzalo A. Collado; Modesto Correoso; María Gabriela Cuezzo; Cristina Damborenea; Alejandra A. Fabres; Monica A. Fernandez; Suzete R. Gomes; et al. (Biological Invasions, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Development and Application of a Mechanistic Nutrient-Based Model for Precision Fish Farming - Filipe M. R. C. Soares; Ana M. D. Nobre; Andreia I. G. Raposo; Rodrigo C. P. Mendes; Sofia A. D. Engrola; Paulo J. A. P. Rema; Luís E. C. Conceição; Tomé S. Silva (Journal of Marine Science and Engineering, 2023)
This manuscript describes and evaluates the FEEDNETICS model, a detailed mechanistic nutrient-based model that has been developed to be used as a data interpretation and decision-support tool by fish farmers, aquafeed producers, aquaculture consultants and researchers. The modelling framework comprises two main components: (i) fish model, that simulates at the individual level the fish growth, composition, and nutrient utilization, following basic physical principles and prior information on the organization and control of biochemical/metabolic processes; and (ii) farm model, that upscales all information to the population level. The model was calibrated and validated for five commercially relevant farmed fish species, i.e., gilthead seabream (Sparus aurata), European seabass (Dicentrarchus labrax), Atlantic salmon (Salmo salar), rainbow trout (Oncorhynchus mykiss), and Nile tilapia (Oreochromis niloticus), using data sets covering a wide range of rearing and feeding conditions. The results of the validation of the model for fish growth are consistent between species, presenting a mean absolute percentage error (MAPE) between 11.7 and 13.8%. Several uses cases are presented, illustrating how this tool can be used to complement experimental trial design and interpretation, and to evaluate nutritional and environmental effects at the farm level. FEEDNETICS provides a means of transforming data into useful information, thus contributing to more efficient fish farming.

Socio-environmental impacts of non-native and transplanted aquatic mollusc species in South America: What do we really know? - Alvar Carranza; Ignacio Agudo-Padrón; Gonzalo A. Collado; Cristina Damborenea; Alejandra Fabres; Diego E. Gutiérrez Gregoric; Cesar Lodeiros; Sandra Ludwig; Guido Pastorino; Pablo Penchaszadeh; Rodrigo B. Salvador; Paula Spotorno; et al. (Hydrobiologia, 2023)

What drives the abundance of marsupial carnivores in production forest landscapes? - Evie M. Jones; Amelia J. Koch; Dydee F. Mann; Rodrigo K. Hamede; Menna E. Jones (Forest Ecology and Management, 2023)

A new method based on machine learning to forecast fruit yield using spectrometric data: analysis in a fruit supply chain context - Javier E. Gómez-Lagos; Marcela C. González-Araya; Rodrigo Ortega Blu; Luis G. Acosta Espejo (Precision Agriculture, 2023)

Marine debris ingestion by odontocete species from the Southwest Atlantic Ocean: Absence also matter - Antonella Daira Padula; Rodrigo Machado; Lucas Milmann; M. Carolina de León; Joaquín C.M. Gana; Janaína C. Wickert; María Eugenia Argañaraz; Ricardo O. Bastida; Diego H. Rodríguez; Pablo E. Denuncio (Marine Pollution Bulletin, 2023)

Ocean acidification and seasonal temperature extremes combine to impair the thermal physiology of a sub-Antarctic fish - María E. Lattuca; Fabián A. Vanella; Gabriela Malanga; Maximiliano D. Rubel; Patricio H. Manríquez; Rodrigo Torres; Katharina Alter; Stefano Marras; Myron A. Peck; Paolo Domenici; Daniel A. Fernández (Science of The Total Environment, 2023)

Comparative life cycle assessment of conventional and novel microalgae production systems and environmental impact mitigation in urban-industrial symbiosis - Joseph Santhi Pechsiri; Jean-Baptiste E. Thomas; Naoufel El Bahraoui; Francisco Gabriel Acien Fernandez; Jamal Chaouki; Saad Chidami; Rodrigo Rivera Tinoco; Jose Pena Martin; Cintia Gomez; Michel Combe; Fredrik Gröndahl (Science of The Total Environment, 2023)

New records of continental vertebrates from the Triassic of the Atacama Desert, northern Chile - Rodrigo A. Otero; David Rubilar-Rogers; Sergio Soto-Acuña; Alexander Vargas M.; Gonzalo Mella Rojas; Raúl Ugalde; Osvaldo Rojas; Jennyfer Rojas; Fernando E. Novas (Journal of South American Earth Sciences, 2023)

Bioconversion of cellulose into bisabolene using Ruminococcus flavefaciens and Rhodosporidium toruloides - Laura E. Walls; Peter Otoupal; Rodrigo Ledesma-Amaro; Sharon B. Velasquez-Orta; John M. Gladden; Leonardo Rios-Solis (Bioresource Technology, 2023)

Birth and growth of the shortnose guitarfish Zapteryx brevirostris (Müller & Henle, 1841) (Chondrichthyes, Rhinobatidae) in captivity - Bruna Larissa Maganhe; Laura de Oliveira Camilo; Rodrigo E. Kurokawa; Hugo Gallo Neto; Eduardo Gomes Sanches (Journal of Fish Biology, 2023)
Endemic to the south‐west Atlantic Ocean, the shortnose guitarfish ( Zapteryx brevirostris ) is a small species, classified as endangered by the IUCN. Although reproduction in captivity has been successful for some species, a range of factors can limit the success of captive breeding programmes for elasmobranchs. In Brazil, the Ubatuba Aquarium was the first public aquarium to reproduce small‐sized elasmobranchs. Since 2018, at least five parturition events have been recorded for Z. brevirostris at the institution. From a total of 13 live neonates that rearing was attempted, the mean ± standard error of weight, total length (TL) and disc width at birth were 17.47 ± 1.6 g, 13.25 ± 0.7 cm and 6.53 ± 0.2 cm, respectively. The mean weight as well as mean TL were higher for females at all births, with 26.15 g and 15.07 cm for females in comparison with 17.09 g and 13.94 cm for males. Considering the increasing risk of extinction that the species is facing, age and growth studies are fundamental for the success of conservation, improving the knowledge of Z. brevirostris life cycle so that a more efficient and sustainable management can be carried out. This study provides important data, as well as directions for captive breeding of the species.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Triiodothyronine Treatment reverses Depression-Like Behavior in a triple-transgenic animal model of Alzheimer’s Disease - Andréa V. Maglione; Bruna P. P. do Nascimento; Miriam O. Ribeiro; Talytha J. L. de Souza; Renata E. C. da Silva; Monica A. Sato; Carlos A. A. Penatti; Luiz R. G. Britto; Janaina S. de Souza; Rui M.B. Maciel; Rodrigo Rodrigues da Conceição; Roberto Laureano-Melo; et al. (Metabolic Brain Disease, 2022)

Density, habitat use and activity patterns of the last giant armadillo population in the Brazilian Atlantic Forest - Juliana B. Pasa; Rodrigo L. Massara; Cynthia E. Widmer; Arnaud L. J. Desbiez; Gabriel F. Massocato; Lucas M. Barreto; Fernando C. C. Azevedo (Mammalian Biology, 2022)

Heat stress negatively affects physiology and morphology during germination of Ormosia coarctata (Fabaceae, Papilionoideae) - Luciane Pereira Reis; Eduardo Euclydes de Lima e Borges; Rodrigo Cupertino Bernardes; Genaina Aparecida de Souza; Renan dos Santos Araújo (Protoplasma, 2022)

Long-term survive of Aliarcobacter butzleri in two models symbiotic interaction with Acanthamoeba castellanii - Gustavo A. Medina; Sandra N. Flores-Martin; Wellison A. Pereira; Elías G. Figueroa; Neftalí H. Guzmán; Pablo J. Letelier; Marcela R. Andaur; Pilar I. Leyán; Rodrigo E. Boguen; Alfonso H. Hernández; Heriberto Fernández (Archives of Microbiology, 2022)

Hypoglycemic effect of rosmarinic acid-rich infusion (RosCE) from Origanum vulgare in alloxan-induced diabetic rats - Márcio L. A. e Silva; Rodrigo Lucarini; Fransergio F. dos Santos; Carlos H. G. Martins; Patricia M. Pauletti; Ana H. Januario; Mario Ferreira Conceição Santos; Wilson R. Cunha (Natural Product Research, 2022)

Modeling implications of climate induced streamflow changes on the fish species of the Soan River, Pakistan - Muhammad Usman; Christopher E. Ndehedehe; Burhan Ahmad; Rodrigo Manzanas (Modeling Earth Systems and Environment, 2022)

Performance of Sentinel-2 SAFER ET model for daily and seasonal estimation of grapevine water consumption - Anderson L. S. Safre; Ayman Nassar; Alfonso Torres-Rua; Mayhar Aboutalebi; João C. C. Saad; Rodrigo L. Manzione; Antonio Heriberto de Castro Teixeira; John H. Prueger; Lynn G. McKee; Joseph G. Alfieri; Lawrence E. Hipps; Hector Nieto; et al. (Irrigation Science, 2022)

Outbreak of canine distemper and coinfections in a maned wolf (Chrysocyon brachyurus) and in three giant anteaters (Myrmecophaga tridactyla) - Lucas R. Souza; Marcelo P. N. Carvalho; Carlos E. B. Lopes; Marcelo C. Lopes; Bruna H. Campos; Érika P. T. Teixeira; Ellen J. Mendes; Leidilene P. Santos; Eduardo A. Caixeta; Erica A. Costa; João L. R. Cunha; Ana L. S. Fraiha; et al. (Brazilian Journal of Microbiology, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

A sustainable approach in the management of Callosobruchus maculatus: essential oil of Protium heptaphyllum and its major compound d-limonene as biopesticides - Rosalba Maria Borges de Andrade Rodrigues; Lucia da Silva Fontes; Rodrigo de Carvalho Brito; Douglas Rafael e Silva Barbosa; Antonia Maria das Graças Lopes Citó; Iolanda Souza do Carmo; Emanoela Maria de Jesus Sousa; Gutierres Nelson Silva (Journal of Plant Diseases and Protection, 2022)

Immune phenotype of the CD4+ T cells in the aged lymphoid organs and lacrimal glands - Claudia M. Trujillo-Vargas; Kelsey E. Mauk; Humberto Hernandez; Rodrigo G. de Souza; Zhiyuan Yu; Jeremias G. Galletti; Jana Dietrich; Friedrich Paulsen; Cintia S. de Paiva (GeroScience, 2022)

Phytopythium chamaehyphon causing corm and root rot of uncultivated taro (Colocasia esculenta) - David Galo; Cesar Escalante; Rodrigo Diaz; John E. Hartgerink; Rodrigo A. Valverde (European Journal of Plant Pathology, 2022)

Richness, not evenness, varies across water availability gradients in grassy biomes on five continents - Melinda D. Smith; Sally E. Koerner; Meghan L. Avolio; Kimberly J. Komatsu; Stephanie Eby; Elisabeth J. Forrestel; Scott L. Collins; Kevin R. Wilcox; Rodrigo Ahumada; John W. Morgan; Gabriel Oliva; Gastón R. Oñatibia; et al. (Oecologia, 2022)

Understanding the Implications of Hydrographic Processes on the Dynamics of the Carbonate System in a Sub-Antarctic Marine-Terminating Glacier-Fjord (53°S) - Jurleys P. Vellojin; Gonzalo S. Saldías; Susan E. Allen; Rodrigo Torres; Maximiliano Vergara-Jara; Marcus Sobarzo; Michael D. DeGrandpre; José Luis Iriarte (Frontiers in Marine Science, 2022)
The biogeochemical dynamics of fjords in the southeastern Pacific Ocean are strongly influenced by hydrological and oceanographic processes occurring at a seasonal scale. In this study, we describe the role of hydrographic forcing on the seasonal variability of the carbonate system of the Sub-Antarctic glacial fjord, Seno Ballena, in the Strait of Magellan (53°S). Biogeochemical variables were measured in 2018 during three seasonal hydrographic cruises (fall, winter and spring) and from a high-frequency p CO 2 -pH mooring for 10 months at 10 ± 1 m depth in the fjord. The hydrographic data showed that freshwater input from the glacier influenced the adjacent surface layer of the fjord and forced the development of undersaturated CO 2 (< 400 μatm) and low aragonite saturation state (Ω Ar < 1) water. During spring, the surface water had relatively low p CO 2 (mean = 365, range: 167 - 471 μatm), high pH (mean = 8.1 on the total proton concentration scale, range: 8.0 - 8.3), and high Ω Ar (mean = 1.6, range: 1.3 - 4.0). Concurrent measurements of phytoplankton biomass and nutrient conditions during spring indicated that the periods of lower p CO 2 values corresponded to higher phytoplankton photosynthesis rates, resulting from autochthonous nutrient input and vertical mixing. In contrast, higher values of p CO 2 (range: 365 – 433 μatm) and relatively lower values of pH T (range: 8.0 – 8.1) and Ω Ar (range: 0.9 – 2.0) were recorded in cold surface waters during winter and fall. The naturally low freshwater carbonate ion concentrations diluted the carbonate ion concentrations in seawater and decreased the calcium carbonate saturation of the fjord. In spring, at 10 m depth, higher primary productivity caused a relative increase in Ω Ar and pH T . Assuming global climate change will bring further glacier retreat and ocean acidification, this study represents important advances in our understanding of glacier meltwater processes on CO 2 dynamics in glacier–fjord systems.

Modeling streamflow using multiple precipitation products in a topographically complex catchment - Muhammad Usman; Christopher E. Ndehedehe; Burhan Ahmad; Rodrigo Manzanas; Oluwafemi E. Adeyeri (Modeling Earth Systems and Environment, 2022)

A New Glyptodont (Xenarthra: Cingulata) from the Late Miocene of Argentina: New Clues About the Oldest Extra-Patagonian Radiation in Southern South America - Daniel Barasoain; Alfredo E. Zurita; Darin A. Croft; Claudia I. Montalvo; Víctor H. Contreras; Ángel R. Miño-Boilini; Rodrigo L. Tomassini (Journal of Mammalian Evolution, 2022)

Glutamine supplementation improves contractile function of regenerating soleus muscles from rats - Tatiana E. Koike; Rodrigo A. Dell Aquila; Kellana S. Silva; Marcelo S. Aoki; Elen H. Miyabara (Journal of Muscle Research and Cell Motility, 2022)

Fast simulation of railway bridge dynamics accounting for soil–structure interaction - P. Galvín; A. Romero; E. Moliner; D. P. Connolly; M. D. Martínez-Rodrigo (Bulletin of Earthquake Engineering, 2022)
A novel numerical methodology is presented to solve the dynamic response of railway bridges under the passage of running trains, considering soil–structure interaction. It is advantageous compared to alternative approaches because it permits, (i) consideration of complex geometries for the bridge and foundations, (ii) simulation of stratified soils, and, (iii) solving the train-bridge dynamic problem at minimal computational cost. The approach uses sub-structuring to split the problem into two coupled interaction problems: the soil–foundation, and the soil–foundation–bridge systems. In the former, the foundation and surrounding soil are discretized with Finite Elements (FE), and padded with Perfectly Match Layers to avoid boundary reflections. Considering this domain, the equivalent frequency dependent dynamic stiffness and damping characteristics of the soil–foundation system are computed. For the second sub-system, the dynamic response of the structure under railway traffic is computed using a FE model with spring and dashpot elements at the support locations, which have the equivalent properties determined using the first sub-system. This soil–foundation–bridge model is solved using complex modal superposition, considering the equivalent dynamic stiffness and damping of the soil–foundation corresponding to each natural frequency. The proposed approach is then validated using both experimental measurements and an alternative Finite Element–Boundary Element (FE–BE) methodology. A strong match is found and the results discussed.

A dynamic simulation model to support reduction in illegal trade within legal wildlife markets - Rodrigo Oyanedel; Stefan Gelcich; Emile Mathieu; E. J. Milner‐Gulland (Conservation Biology, 2022)
Sustainable wildlife trade is critical for biodiversity conservation, livelihoods, and food security. Regulatory frameworks are needed to secure these diverse benefits of sustainable wildlife trade. However, regulations limiting trade can backfire, sparking illegal trade if demand is not met by legal trade alone. Assessing how regulations affect wildlife market participants’ incentives is key to controlling illegal trade. Although much research has assessed how incentives at both the harvester and consumer ends of markets are affected by regulations, little has been done to understand the incentives of traders (i.e., intermediaries). We built a dynamic simulation model to support reduction in illegal wildlife trade within legal markets by focusing on incentives traders face to trade legal or illegal products. We used an Approximate Bayesian Computation approach to infer illegal trading dynamics and parameters that might be unknown (e.g., price of illegal products). We showcased the utility of the approach with a small‐scale fishery case study in Chile, where we disentangled within‐year dynamics of legal and illegal trading and found that the majority (∼77%) of traded fish is illegal. We utilized the model to assess the effect of policy interventions to improve the fishery's sustainability and explore the trade‐offs between ecological, economic, and social goals. Scenario simulations showed that even significant increases (over 200%) in parameters proxying for policy interventions enabled only moderate improvements in ecological and social sustainability of the fishery at substantial economic cost. These results expose how unbalanced trader incentives are toward trading illegal over legal products in this fishery. Our model provides a novel tool for promoting sustainable wildlife trade in data‐limited settings, which explicitly considers traders as critical players in wildlife markets. Sustainable wildlife trade requires incentivizing legal over illegal wildlife trade and consideration of the social, ecological, and economic impacts of interventions.

Correction to: Apathy and Depression as Predictors of Activities of Daily Living Following Stroke and Traumatic Brain Injuries in Adults: a Meta‑Analysis - Sarah L. Green; Gilles E. Gignac; Prue A. Watson; Nicky Brosnan; Rodrigo Becerra; Carmela Pestell; Michael Weinborn (Neuropsychology Review, 2022)

Apathy and Depression as Predictors of Activities of Daily Living Following Stroke and Traumatic Brain Injuries in Adults: A Meta-Analysis - Sarah L. Green; Gilles E. Gignac; Prue A. Watson; Nicky Brosnan; Rodrigo Becerra; Carmela Pestell; Michael Weinborn (Neuropsychology Review, 2022)

Antimicrobial activities of aztreonam-avibactam and comparator agents tested against Enterobacterales from European hospitals analysed by geographic region and infection type (2019–2020) - Helio S. Sader; Rodrigo E. Mendes; S. J. Ryan Arends; Cecilia G. Carvalhaes; Mariana Castanheira (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Essential oils from Betula lenta, Cinnamomum cassia, Citrus aurantium var. Amara and Acorus calamus as biopesticides against cowpea weevil - Rodrigo de Carvalho Brito; Lúcia da Silva Fontes; Paulo Henrique Soares da Silva; Carolina de Sousa Santana; Douglas Rafael e Silva Barbosa (International Journal of Tropical Insect Science, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Severity of SARS-CoV-2 infection is linked to double-negative (CD27− IgD−) B cell subset numbers - Rodrigo Cervantes-Díaz; Víctor Andrés Sosa-Hernández; Jiram Torres-Ruíz; Sandra Romero-Ramírez; Mariana Cañez-Hernández; Alfredo Pérez-Fragoso; José C. Páez-Franco; David E. Meza-Sánchez; Miriam Pescador-Rojas; Víctor Adrián Sosa-Hernández; Diana Gómez-Martín; José L. Maravillas-Montero (Inflammation Research, 2022)

Pyramiding dsRNAs increases phytonematode tolerance in cotton plants - Maria E. Lisei-de-Sá; Paolo L. Rodrigues-Silva; Carolina V. Morgante; Bruno Paes de Melo; Isabela T. Lourenço-Tessutti; Fabricio B. M. Arraes; João P. A. Sousa; Rafael Galbieri; Regina M. S. Amorim; Camila B. J. de Lins; Leonardo L. P. Macedo; Valdeir J. Moreira; et al. (Planta, 2021)

The Prevalence and Characteristics of Alexithymia in Adults Following Brain Injury: A Meta-Analysis - Danielle M. Fynn; Gilles E. Gignac; Rodrigo Becerra; Carmela F. Pestell; Michael Weinborn (Neuropsychology Review, 2021)

Escaping the fate of Sisyphus: assessing resistome hybridization baits for antimicrobial resistance gene capture - Megan S. Beaudry; Jesse C. Thomas; Rodrigo P. Baptista; Amanda H. Sullivan; William Norfolk; Alison Devault; Jacob Enk; Troy J. Kieran; Olin E. Rhodes; K. Allison Perry‐Dow; Laura J. Rose; Natalia J. Bayona‐Vásquez; et al. (Environmental Microbiology, 2021)
Summary Finding, characterizing and monitoring reservoirs for antimicrobial resistance (AMR) is vital to protecting public health. Hybridization capture baits are an accurate, sensitive and cost‐effective technique used to enrich and characterize DNA sequences of interest, including antimicrobial resistance genes (ARGs), in complex environmental samples. We demonstrate the continued utility of a set of 19 933 hybridization capture baits designed from the Comprehensive Antibiotic Resistance Database (CARD)v1.1.2 and Pathogenicity Island Database (PAIDB)v2.0, targeting 3565 unique nucleotide sequences that confer resistance. We demonstrate the efficiency of our bait set on a custom‐made resistance mock community and complex environmental samples to increase the proportion of on‐target reads as much as >200‐fold. However, keeping pace with newly discovered ARGs poses a challenge when studying AMR, because novel ARGs are continually being identified and would not be included in bait sets designed prior to discovery. We provide imperative information on how our bait set performs against CARDv3.3.1, as well as a generalizable approach for deciding when and how to update hybridization capture bait sets. This research encapsulates the full life cycle of baits for hybridization capture of the resistome from design and validation (both in silico and in vitro ) to utilization and forecasting updates and retirement.

Next-generation sequencing, isolation and characterization of 14 microsatellite loci of Canthon cyanellus (Coleoptera: Scarabaeidae) - Luis Rodrigo Arce-Valdés; Rosa Ana Sánchez-Guillén; Janet Nolasco-Soto; Mario E. Favila (Molecular Biology Reports, 2021)

Virulence Genes Profile and Antimicrobial Susceptibility of Community-Acquired Bacterial Urinary Tract Infections in a Brazilian Hospital - Fernanda Morcatti Coura; Vitoria Marra de Souza Savini; Rafael Gariglio Clark Xavier; Carolina Pantuzza Ramos; Rodrigo Otávio Silveira Silva; Marcos Bryan Heinemann; Andrea Micke Moreno; Terezinha Knöbl; Elaine Maria Seles Dorneles; Dirceia Aparecida da Costa Custódio; Carine Rodrigues Pereira; Pedro Felipe Rodrigues e Oliveira; et al. (Current Microbiology, 2021)

A Review of the Opportunities and Challenges for Using Remote Sensing for Management of Surface-Canopy Forming Kelps - Kyle C. Cavanaugh; Tom Bell; Maycira Costa; Norah E. Eddy; Lianna Gendall; Mary G. Gleason; Margot Hessing-Lewis; Rebecca Martone; Meredith McPherson; Ondine Pontier; Luba Reshitnyk; Rodrigo Beas-Luna; et al. (Frontiers in Marine Science, 2021)
Surface-canopy forming kelps provide the foundation for ecosystems that are ecologically, culturally, and economically important. However, these kelp forests are naturally dynamic systems that are also threatened by a range of global and local pressures. As a result, there is a need for tools that enable managers to reliably track changes in their distribution, abundance, and health in a timely manner. Remote sensing data availability has increased dramatically in recent years and this data represents a valuable tool for monitoring surface-canopy forming kelps. However, the choice of remote sensing data and analytic approach must be properly matched to management objectives and tailored to the physical and biological characteristics of the region of interest. This review identifies remote sensing datasets and analyses best suited to address different management needs and environmental settings using case studies from the west coast of North America. We highlight the importance of integrating different datasets and approaches to facilitate comparisons across regions and promote coordination of management strategies.

Sedimentary stratigraphy of Lake Chalco (Central Mexico) during its formative stages - Rodrigo Martínez-Abarca; Beatriz Ortega-Guerrero; Socorro Lozano-García; Margarita Caballero; Blas Valero-Garcés; David McGee; Erik T. Brown; Mona Stockhecke; Alastair G. E. Hodgetts (International Journal of Earth Sciences, 2021)

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

Readily dispersible clay in soils from different Brazilian regions by visible, near, and mid-infrared spectral data - Isabela Mello Silva; Danilo Jefferson Romero; Clécia Cristina Barbosa Guimarães; Marcelo Rodrigo Alves; Lucas Prado Osco; Arnaldo Barros e Souza; Alvaro Pires da Silva; José A.M. Demattê (International Journal of Remote Sensing, 2021)

Nitrous oxide emissions from red clover and winter wheat residues depend on interacting effects of distribution, soil N availability and moisture level - Arezoo Taghizadeh-Toosi; Baldur Janz; Rodrigo Labouriau; Jørgen E. Olesen; Klaus Butterbach-Bahl; Søren O. Petersen (Plant and Soil, 2021)

Heat stress-mediated effects on the morphophysiological, biochemical, and ultrastructural parameters of germinating Melanoxylon brauna Schott. seeds - Luciane Pereira Reis; Eduardo Euclydes de Lima e Borges; Danielle S. Brito; Rodrigo Cupertino Bernardes; Renan dos Santos Araújo (Plant Cell Reports, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Genomic analysis reveals the potential for hydrocarbon degradation of Rhodopirellula sp. MGV isolated from a polluted Brazilian mangrove - Juliana Eschholz de Araujo; Rodrigo Gouvêa Taketani; Victor Satler Pylro; Laura Rabelo Leite; Michele de Cássia Pereira e Silva; Leandro Nascimento Lemos; Marcus Venícius de Mello Lourenço; Fernando Dini Andreote (Brazilian Journal of Microbiology, 2021)

Essential and Potentially Toxic Elements from Brazilian Geopropolis Produced by the Stingless Bee Melipona quadrifasciata anthidioides Using ICP OES - Rodrigo da Cruz Ferreira; Fernanda de Souza Dias; Caroline de Aragão Tannus; Filipe Barbosa Santana; Daniele Cristina Muniz Batista dos Santos; Fábio de Souza Dias; Marina Siqueira de Castro; Hugo Neves Brandão; Aníbal de Freitas Santos Júnior; Lidércia Cavalcanti Ribeiro Cerqueira e Silva; Fábio Alexandre Chinalia (Biological Trace Element Research, 2021)

Using Compounds Derived from the Glycerol Fermentation as a Carbon Source for Denitrification and Biological Phosphorus Removal - Maria E. S. Dias; Jéssica C. Lopes; Rodrigo B. Carneiro; Márcia H. R. Z. Damianovic; Eugenio Foresti (Water, Air, & Soil Pollution, 2021)

Fifteen days of moderate normobaric hypoxia does not affect mitochondrial function, and related genes and proteins, in healthy men - Alessandra Ferri; Xu Yan; Jujiao Kuang; Cesare Granata; Rodrigo S. F. Oliveira; Christopher P. Hedges; Adriano E. Lima-Silva; Francois Billaut; David J. Bishop (European Journal of Applied Physiology, 2021)

Synergetic antimicrobial effect of chlorin e6 and hydrogen peroxide on multi-species biofilms - Min Nie; Rodrigo Costa e Silva; Kleber Thiago de Oliveira; Vanderlei Salvador Bagnato; Alessandra Nara de Souza Rastelli; Wim Crielaard; Jingmei Yang; Dong Mei Deng (Biofouling, 2021)

Introgression of the sesquiterpene biosynthesis from Solanum habrochaites to cultivated tomato offers insights into trichome morphology and arthropod resistance - Rodrigo Therezan; Ruy Kortbeek; Eloisa Vendemiatti; Saioa Legarrea; Severino M. de Alencar; Robert C. Schuurink; Petra Bleeker; Lázaro E. P. Peres (Planta, 2021)
Main conclusion Cultivated tomatoes harboring the plastid-derived sesquiterpenes from S. habrochaites have altered type-VI trichome morphology and unveil additional genetic components necessary for piercing-sucking pest resistance. Abstract Arthropod resistance in the tomato wild relative Solanum habrochaites LA1777 is linked to specific sesquiterpene biosynthesis. The Sesquiterpene synthase 2 ( SsT2 ) gene cluster on LA1777 chromosome 8 controls plastid-derived sesquiterpene synthesis. The main genes at SsT2 are Z-prenyltransferase (zFPS) and Santalene and Bergamotene Synthase ( SBS ), which produce α-santalene, β-bergamotene, and α-bergamotene in LA1777 round-shaped type-VI glandular trichomes. Cultivated tomatoes have mushroom-shaped type-VI trichomes with much smaller glands that contain low levels of monoterpenes and cytosolic-derived sesquiterpenes, not presenting the same pest resistance as in LA1777. We successfully transferred zFPS and SBS from LA1777 to cultivated tomato (cv. Micro-Tom, MT) by a backcrossing approach. The trichomes of the MT- Sst2 introgressed line produced high levels of the plastid-derived sesquiterpenes. The type-VI trichome internal storage-cavity size increased in MT- Sst2 , probably as an effect of the increased amount of sesquiterpenes, although it was not enough to mimic the round-shaped LA1777 trichomes. The presence of high amounts of plastid-derived sesquiterpenes was also not sufficient to confer resistance to various tomato piercing-sucking pests, indicating that the effect of the sesquiterpenes found in the wild S. habrochaites can be insect specific. Our results provide for a better understanding of the morphology of S. habrochaites type-VI trichomes and paves the way to obtain insect-resistant tomatoes.

Thermal effects in rainbow trout ( Oncorhynchus mykiss ) F1 embryos (farmed female × wild thermal‐resistant male) - Sonia A. Crichigno; Mabel Orellana; Rodrigo Larraza; Guillermo Mirenna; Víctor E. Cussac (Journal of Fish Biology, 2021)
The aim of this work was to investigate the response of rainbow trout embryos ( Oncorhynchus mykiss ) ( i.e ., survival, size at hatching, time to hatching, malformations) to four incubation temperatures (5.8, 8.9, 14.0 and 16.8°C), taking into account the origin of the male parental genome and comparing pure farmed and F1 embryos (farmed female × wild thermal‐resistant male). Several consequences of thermal stress were observed: lower accumulated thermal units (ATU) at hatching at high temperatures, and lower survival, shorter hatched free embryos and less‐consumed yolk sac at extreme temperatures. The effect of the thermal‐adapted male parental genome was shown only in the lower percentage of incompletely hatched free embryos in the F1 families. It appears that to obtain greater modification of thermal performance during early development, the adapted genome of the wild thermal‐resistant population has to be included through maternal inheritance, thus producing a stabilized strain selected for domesticity, growth and thermal adaptation.

Antidepressant-like effect of guanosine involves activation of AMPA receptor and BDNF/TrkB signaling - Priscila B. Rosa; Luis E. B. Bettio; Vivian B. Neis; Morgana Moretti; Fernanda N. Kaufmann; Mauren K. Tavares; Isabel Werle; Yasmim Dalsenter; Nicolle Platt; Axel F. Rosado; Daiane B. Fraga; Isabella A. Heinrich; et al. (Purinergic Signalling, 2021)

Deep learning for lithological classification of carbonate rock micro-CT images - Carlos E. M. dos Anjos; Manuel R. V. Avila; Adna G. P. Vasconcelos; Aurea M. Pereira Neta; Lizianne C. Medeiros; Alexandre G. Evsukoff; Rodrigo Surmas; Luiz Landau (Computational Geosciences, 2021)

Influence of Silver Nanoparticle–Based Coating on Calcareous Rock Surfaces on Microbial Biofilm Colonization in Intertidal Environments in Campeche, Mexico - Juan Carlos Camacho-Chab; Benjamín O. Ortega-Morales; Christine Gaylarde; Juan E. Pereañez-Sacarías; Hilda P. León-Tejera; Rodrigo E. Tun-Che; Radames J. Álvarez-Zapata; Augusto I. Almeyda-Cen; William Talavera-Pech; Juan F. Illescas-Salinas (Water, Air, & Soil Pollution, 2021)

Biphasic growth modelling in elasmobranchs based on asymmetric and heavy-tailed errors - Javier E. Contreras-Reyes; Rodrigo Wiff; Javier Soto; Carl R. Donovan; Miguel Araya (Environmental Biology of Fishes, 2021)

Quantifying 25 years of disease‐caused declines in Tasmanian devil populations: host density drives spatial pathogen spread - Calum X. Cunningham; Sebastien Comte; Hamish McCallum; David G. Hamilton; Rodrigo Hamede; Andrew Storfer; Tracey Hollings; Manuel Ruiz‐Aravena; Douglas H. Kerlin; Barry W. Brook; Greg Hocking; Manna E. Jones (Ecology Letters, 2021)
Infectious diseases are strong drivers of wildlife population dynamics, however, empirical analyses from the early stages of pathogen emergence are rare. Tasmanian devil facial tumour disease (DFTD), discovered in 1996, provides the opportunity to study an epizootic from its inception. We use a pattern‐oriented diffusion simulation to model the spatial spread of DFTD across the species' range and quantify population effects by jointly modelling multiple streams of data spanning 35 years. We estimate the wild devil population peaked at 53 000 in 1996, less than half of previous estimates. DFTD spread rapidly through high‐density areas, with spread velocity slowing in areas of low host densities. By 2020, DFTD occupied >90% of the species' range, causing 82% declines in local densities and reducing the total population to 16 900. Encouragingly, our model forecasts the population decline should level‐off within the next decade, supporting conservation management focused on facilitating evolution of resistance and tolerance.

Neuronal activity regulated pentraxin (narp) and GluA4 subunit of AMPA receptor may be targets for fluoxetine modulation - Isabella A. Heinrich; Andiara E. Freitas; Ingrid A. V. Wolin; Ana Paula M. Nascimento; Roger Walz; Ana Lúcia S. Rodrigues; Rodrigo B. Leal (Metabolic Brain Disease, 2021)

In vitro and in vivo anti-inflammatory activity and chemical composition of Renealmia petasites Gagnep - Aline Keller Couto Soares; Antônio Domingos de Sousa Júnior; Mariane Fioroti Lorençoni; Júlia Araujo de Castro; Flávia Vitorino de Araujo Porto; Iana Soares Pessoa; Marcos Vinicius Toledo e Silva; Ana Claudia Hertel Pereira; Flavia de Souza Andrade Moraes; Tadeu Uggere de Andrade; Denise Coutinho Endringer; Rodrigo Scherer; et al. (Inflammopharmacology, 2021)

Treatment with a DC-SIGN ligand reduces macrophage polarization and diastolic dysfunction in the aging female but not male mouse hearts - JoAnn Trial; Rodrigo Diaz Lankenau; Aude Angelini; Jorge E. Tovar Perez; George E. Taffet; Mark L. Entman; Katarzyna A. Cieslik (GeroScience, 2021)
Cardiac diastolic dysfunction in aging arises from increased ventricular stiffness caused by inflammation and interstitial fibrosis. The diastolic dysfunction contributes to heart failure with preserved ejection fraction (HFpEF), which in the aging population is more common in women. This report examines its progression over 12 weeks in aging C57BL/6J mice and correlates its development with changes in macrophage polarization and collagen deposition. Aged C57BL/6J mice were injected with dendritic cell–specific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN) ligand 1 (DCSL1, an anti-inflammatory agent) or saline for 12 weeks. Echo and Doppler measurements were performed before and after 4 and 12 weeks of treatment. DCSL1 prevented the worsening of diastolic dysfunction over time in females but not in males. Cardiac single cell suspensions analyzed by flow cytometry revealed changes in the inflammatory infiltrate: (1) in males, there was an increased total number of leukocytes with an increased pro-inflammatory profile compared with females and they did not respond to DCSL1; (2) by contrast, DCSL1 treatment resulted in a shift in macrophage polarization to an anti-inflammatory phenotype in females. Notably, DCSL1 preferentially targeted tumor necrosis factor-α (TNFα + ) pro-inflammatory macrophages. The reduction in pro-inflammatory macrophage polarization was accompanied by a decrease in collagen content in the heart. Age-associated diastolic dysfunction in mice is more severe in females and is associated with unique changes in macrophage polarization in cardiac tissue. Treatment with DCSL1 mitigates the changes in inflammation, cardiac function, and fibrosis. The characteristics of diastolic dysfunction in aging female mice mimic similar changes in aging women.

Effects of stocking density on survival, growth and stress resistance of juvenile tambaqui (Colossoma macropomum) reared in a recirculating aquaculture system (RAS) - Walisson de Souza e Silva; Andre Lima Ferreira; Luanna do Carmo Neves; Nathália Soares Ferreira; Glauber David Almeida Palheta; Rodrigo Takata; Ronald Kennedy Luz (Aquaculture International, 2021)

Neonatal Serotonin Depletion Induces Hyperactivity and Anxiolytic-like Sex-Dependent Effects in Adult Rats - Verónica Trujillo; Evandro Valentim-Lima; Rodrigo Mencalha; Quézia S. R. Carbalan; Raoni C. Dos-Santos; Viviane Felintro; Carlos E. N. Girardi; Rodrigo Rorato; Danilo Lustrino; Luis C. Reis; André S. Mecawi (Molecular Neurobiology, 2021)

Control of Zabrotes subfasciatus (Coleoptera: Chrysomelidae: Bruchinae) in Phaseolus lunatus treated with commercial essential oils - Carolina de Sousa Santana; Lúcia da Silva Fontes; Paulo Henrique Soares da Silva; Rodrigo de Carvalho Brito; Douglas Rafael e Silva Barbosa; Antônia Maria das Graças Lopes Citó (International Journal of Tropical Insect Science, 2021)

Correction to: Genome constellations of rotavirus A isolated from avian species in Brazil, 2008–2015 - Laila A. R. Beserra; Carla M. Barbosa; Mikael Berg; Paulo E. Brandão; Rodrigo M. Soares; Fabio Gregori (Brazilian Journal of Microbiology, 2021)

Accounting for relatedness and spatial structure to improve plant phenotypic selection in the wild - Francisco E. Fontúrbel; Pedro F. Ferrer; Caren Vega-Retter; Rodrigo Medel (Evolutionary Ecology, 2021)

New records of alien land gastropods in Argentina, with the description of a new species of Scolodontidae (Mollusca: Pulmonata: Stylommatophora) - Sergio E. Miquel; Rodrigo A. Santin (Molluscan Research, 2021)

Selection of cowpea cultivars for high temperature tolerance: physiological, biochemical and yield aspects - Juliane Rafaele Alves Barros; Miguel Julio Machado Guimarães; Rodrigo Moura e Silva; Maydara Thaylla Cavalcanti Rêgo; Natoniel Franklin de Melo; Agnaldo Rodrigues de Melo Chaves; Francislene Angelotti (Physiology and Molecular Biology of Plants, 2021)

Is there an association between a history of military service and cancer diagnosis? Results from a US national-level study of self-reported outcomes - Hanan Goldberg; Rodrigo Noorani; John Z. Benton; Atul Lodh; Alejandro Berlin; Thenappan Chandrasekar; Christopher J. D. Wallis; Ardalan E. Ahmad; Zachary Klaassen; Neil E. Fleshner (Cancer Causes & Control, 2021)

Drought Characteristics Assessment in Europe over the Past 50 Years - Panagiotis D. Oikonomou; Christos A. Karavitis; Demetrios E. Tsesmelis; Elpida Kolokytha; Rodrigo Maia (Water Resources Management, 2020)

Conservation assessment using the IUCN criterion B: A case study on palms of the Mexican portion of the Yucatán Peninsula Biotic Province - José E. Pérez-Sarabia; Rodrigo Duno de Stefano; William Cetzal-Ix; Arturo A. Alvarado-Segura; Saikat K. Basu (Kew Bulletin, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

The use of anthropogenic debris as nesting material by the greater thornbird, an inland–wetland-associated bird of South America - Martín C. M. Blettler; Lucía Gauna; Alex Andréault; Elie Abrial; Rodrigo E. Lorenzón; Luis A. Espinola; Karl M. Wantzen (Environmental Science and Pollution Research, 2020)

Informational content of cosine and other similarities calculated from high-dimensional Conceptual Property Norm data - Enrique Canessa; Sergio E. Chaigneau; Sebastián Moreno; Rodrigo Lagos (Cognitive Processing, 2020)

Undecane production by cold-adapted bacteria from Antarctica - Michel Rodrigo Zambrano Passarini; Tiago Rodrigues e Silva; Suzan Prado Fernandes Bernal; Nathália Luana Cecchet; Adilson Sartoratto; Marcela Boroski; Alysson Wagner Fernandes Duarte; Júlia Ronzella Ottoni; Luiz Henrique Rosa; Valéria Maia de Oliveira (Extremophiles, 2020)

Geographic variation in responses of kelp forest communities of the California Current to recent climatic changes - Rodrigo Beas‐Luna; Fiorenza Micheli; C. Brock Woodson; Mark Carr; Dan Malone; Jorge Torre; Charles Boch; Jennifer E. Caselle; Matt Edwards; Jan Freiwald; Scott L. Hamilton; Arturo Hernandez; et al. (Global Change Biology, 2020)
The changing global climate is having profound effects on coastal marine ecosystems around the world. Structure, functioning, and resilience, however, can vary geographically, depending on species composition, local oceanographic forcing, and other pressures from human activities and use. Understanding ecological responses to environmental change and predicting changes in the structure and functioning of whole ecosystems require large‐scale, long‐term studies, yet most studies trade spatial extent for temporal duration. We address this shortfall by integrating multiple long‐term kelp forest monitoring datasets to evaluate biogeographic patterns and rates of change of key functional groups (FG) along the west coast of North America. Analysis of data from 469 sites spanning Alaska, USA, to Baja California, Mexico, and 373 species (assigned to 18 FG) reveals regional variation in responses to both long‐term (2006–2016) change and a recent marine heatwave (2014–2016) associated with two atmospheric and oceanographic anomalies, the “Blob” and extreme El Niño Southern Oscillation (ENSO). Canopy‐forming kelps appeared most sensitive to warming throughout their range. Other FGs varied in their responses among trophic levels, ecoregions, and in their sensitivity to heatwaves. Changes in community structure were most evident within the southern and northern California ecoregions, while communities in the center of the range were more resilient. We report a poleward shift in abundance of some key FGs. These results reveal major, ongoing region‐wide changes in productive coastal marine ecosystems in response to large‐scale climate variability, and the potential loss of foundation species. In particular, our results suggest that coastal communities that are dependent on kelp forests will be more impacted in the southern portion of the California Current region, highlighting the urgency of implementing adaptive strategies to sustain livelihoods and ensure food security. The results also highlight the value of multiregional integration and coordination of monitoring programs for improving our understanding of marine ecosystems, with the goal of informing policy and resource management in the future.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Investigating Plant Phenotype, Salinity, and Infestation by the Roseau Cane Scale as Factors in the Die-Back of Phragmites australis in the Mississippi River Delta, USA - Ian A. Knight; James T. Cronin; Madeline Gill; John A. Nyman; Blake E. Wilson; Rodrigo Diaz (Wetlands, 2020)

Benzocaine and menthol as anesthetics for the African cichlid Aulonocara nyassae - Andre Lima Ferreira; Walisson de Souza e Silva; Luanna do Carmo Neves; Nathália Soares Ferreira; Rodrigo Takata; Ronald Kennedy Luz (Aquaculture International, 2020)

A synthesis of (non‐)compliance theories with applications to small‐scale fisheries research and practice - Rodrigo Oyanedel; Stefan Gelcich; E. J. Milner‐Gulland (Fish and Fisheries, 2020)
Non‐compliance in fisheries is a persistent challenge for the conservation and sustainable management of the oceans and has particularly acute impacts in small‐scale fisheries contexts. Small‐scale fisheries often suffer from chronic overexploitation, poor management, lack of enforcement and non‐compliance, but small‐scale fishers are highly dependent on the ocean as a source of employment and food. Improving our understanding of the determinants of non‐compliant behaviours in small‐scale fisheries can help develop strategies to prevent and reduce its consequences. Here, we review two main approaches for the study of non‐compliant behaviours and crimes more broadly, spanning criminology, economics and psychology. On the one hand, actor‐based approaches address the underlying motivations for people to comply or not with regulations. Opportunity‐based approaches, on the other hand, assume that non‐compliance is not distributed randomly across space and time and focuses on the role that the immediate environment plays in the performance of non‐compliant behaviours. We discuss potential applications of actor‐based and opportunity‐based approaches in guiding small‐scale fisheries non‐compliance research. Moreover, we provide guiding principles for integrating these approaches in a complementary way, highlighting opportunities and challenges for building a better non‐compliance research agenda for fisheries and beyond. Addressing non‐compliance is a common challenge for natural resource management in multiple ecosystems. Integrating these two perspectives has the potential to improve both research and practice.

Genome constellations of rotavirus a isolated from avian species in Brazil, 2008–2015 - Laila A. R. Beserra; Carla M. Barbosa; Mikael Berg; Paulo E. Brandão; Rodrigo M. Soares; Fabio Gregori (Brazilian Journal of Microbiology, 2020)

Comparative landscape genetics reveals differential effects of environment on host and pathogen genetic structure in Tasmanian devils ( Sarcophilus harrisii ) and their transmissible tumour - Christopher P. Kozakiewicz; Lauren Ricci; Austin H. Patton; Amanda R. Stahlke; Sarah A. Hendricks; Mark J. Margres; Manuel Ruiz‐Aravena; David G. Hamilton; Rodrigo Hamede; Hamish McCallum; Menna E. Jones; Paul A. Hohenlohe; et al. (Molecular Ecology, 2020)
Genetic structure in host species is often used to predict disease spread. However, host and pathogen genetic variation may be incongruent. Understanding landscape factors that have either concordant or divergent influence on host and pathogen genetic structure is crucial for wildlife disease management. Devil facial tumour disease (DFTD) was first observed in 1996 and has spread throughout almost the entire Tasmanian devil geographic range, causing dramatic population declines. Whereas DFTD is predominantly spread via biting among adults, devils typically disperse as juveniles, which experience low DFTD prevalence. Thus, we predicted little association between devil and tumour population structure and that environmental factors influencing gene flow differ between devils and tumours. We employed a comparative landscape genetics framework to test the influence of environmental factors on patterns of isolation by resistance (IBR) and isolation by environment (IBE) in devils and DFTD. Although we found evidence for broad‐scale costructuring between devils and tumours, we found no relationship between host and tumour individual genetic distances. Further, the factors driving the spatial distribution of genetic variation differed for each. Devils exhibited a strong IBR pattern driven by major roads, with no evidence of IBE. By contrast, tumours showed little evidence for IBR and a weak IBE pattern with respect to elevation in one of two tumour clusters we identify herein. Our results warrant caution when inferring pathogen spread using host population genetic structure and suggest that reliance on environmental barriers to host connectivity may be ineffective for managing the spread of wildlife diseases. Our findings demonstrate the utility of comparative landscape genetics for identifying differential factors driving host dispersal and pathogen transmission.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Chemical composition of essential oils from different parts of Protium heptaphyllum (Aubl.) Marchand and their in vitro antibacterial activity - Rodrigo S. C. Cabral; Cassia C. F. Alves; Hellen R. F. Batista; Wendel C. Sousa; Isabela S. Abrahão; Antônio E. M. Crotti; Mariana B. Santiago; Carlos H. G. Martins; Mayker L. D. Miranda (Natural Product Research, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Changing Biogeochemistry of the Southern Ocean and Its Ecosystem Implications - Sian F. Henley; Emma L. Cavan; Sarah E. Fawcett; Rodrigo Kerr; Thiago Monteiro; Robert M. Sherrell; Andrew R. Bowie; Philip W. Boyd; David K. A. Barnes; Irene R. Schloss; Tanya Marshall; Raquel Flynn; et al. (Frontiers in Marine Science, 2020)

Is Leaf Water-Repellency and Cuticle Roughness Linked to Flooding Regimes in Plants of Coastal Wetlands? - Luis E. Tellechea-Robles; Mario Salazar Ceseña; Stephen H. Bullock; Rubén D. Cadena-Nava; Rodrigo Méndez-Alonzo (Wetlands, 2020)

Process Monitoring of Moisture Content and Mass Transfer Rate in a Fluidised Bed with a Low Cost Inline MEMS NIR Sensor - Claudio R. Avila; Joan Ferré; Rodrigo Rocha de Oliveira; Anna de Juan; Wayne E. Sinclair; Faiz M. Mahdi; Ali Hassanpour; Timothy N. Hunter; Richard A. Bourne; Frans L. Muller (Pharmaceutical Research, 2020)
Purpose The current trend for continuous drug product manufacturing requires new, affordable process analytical techniques (PAT) to ensure control of processing. This work evaluates whether property models based on spectral data from recent Fabry–Pérot Interferometer based NIR sensors can generate a high-resolution moisture signal suitable for process control. Methods Spectral data and offline moisture content were recorded for 14 fluid bed dryer batches of pharmaceutical granules. A PLS moisture model was constructed resulting in a high resolution moisture signal, used to demonstrate (i) endpoint determination and (ii) evaluation of mass transfer performance. Results The sensors appear robust with respect to vibration and ambient temperature changes, and the accuracy of water content predictions (±13 % ) is similar to those reported for high specification NIR sensors. Fusion of temperature and moisture content signal allowed monitoring of water transport rates in the fluidised bed and highlighted the importance water transport within the solid phase at low moisture levels. The NIR data was also successfully used with PCA-based MSPC models for endpoint detection. Conclusions The spectral quality of the small form factor NIR sensor and its robustness is clearly sufficient for the construction and application of PLS models as well as PCA-based MSPC moisture models. The resulting high resolution moisture content signal was successfully used for endpoint detection and monitoring the mass transfer rate.

Optimization of Eucalyptus breeding through random regression models allowing for reaction norms in response to environmental gradients - Rodrigo Silva Alves; Marcos Deon Vilela de Resende; Camila Ferreira Azevedo; Fabyano Fonseca e Silva; João Romero do Amaral Santos de Car Rocha; Andrei Caíque Pires Nunes; Antônio Policarpo Souza Carneiro; Gleison Augusto dos Santos (Tree Genetics & Genomes, 2020)

Endogenous, Climate, and Fishing Influences on the Population Dynamics of Small Pelagic Fish in the Southern Humboldt Current Ecosystem - T. Mariella Canales; Mauricio Lima; Rodrigo Wiff; Javier E. Contreras-Reyes; Ursula Cifuentes; José Montero (Frontiers in Marine Science, 2020)

Effect of Tidal Cycles on Bacterial Biofilm Formation and Biocorrosion of Stainless Steel AISI 316L - Leslie K. Daille; Javiera Aguirre; Diego Fischer; Carlos Galarce; Francisco Armijo; Gonzalo E. Pizarro; Magdalena Walczak; Rodrigo De la Iglesia; Ignacio T. Vargas (Journal of Marine Science and Engineering, 2020)
The effects of tidal cycles associated with the water level on the biocorrosion of stainless steel AISI 316L were studied. Steel coupons were exposed to different conditions of immersion in mesocosms fed by fresh seawater either continuously or in accordance with the periodicity of natural tides. After 5 and 15 weeks, all coupons were found to have undergone ennoblement associated with the formation of a biofilm. Analysis of the composition of the bacterial community using denaturing gradient gel electrophoresis (DGGE) revealed differences in the biological succession. After 15 weeks, exposure to the simulated tidal conditions resulted in biofilms with lesser bacterial richness; the corresponding rate of corrosion, as determined by weight loss, was about 40 times lower compared to the case for the continuous exposure to seawater. Phylogenetic analysis of selected DGGE bands and the inspection of biofilm morphologies revealed that the faster rate of corrosion was associated with the presence of iron-oxidizing Zetaproteobacteria and eukaryotic photosynthetic microorganisms. On the other hand, intermittent exposure to seawater resulted in the succession of microorganisms resistant to the stress associated with sudden environmental changes, which was associated with a low rate of corrosion.

Starch accumulation does not lead to feedback photosynthetic downregulation in girdled coffee branches under varying source-to-sink ratios - Rodrigo T. Avila; Samuel C. V. Martins; Lílian M. V. P. Sanglard; Martielly S. dos Santos; Paulo E. Menezes-Silva; Kelly C. Detman; Matheus L. Sanglard; Amanda A. Cardoso; Leandro E. Morais; Camilo E. Vital; Wagner L. Araújo; Adriano Nunes-Nesi; et al. (Trees, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

How do coffee trees deal with severe natural droughts? An analysis of hydraulic, diffusive and biochemical components at the leaf level - Samuel C. V. Martins; Matheus L. Sanglard; Leandro E. Morais; Paulo E. Menezes-Silva; Rafael Mauri; Rodrigo T. Avila; Camilo E. Vital; Amanda A. Cardoso; Fábio M. DaMatta (Trees, 2019)

The antidepressant-like effect of guanosine is dependent on GSK-3β inhibition and activation of MAPK/ERK and Nrf2/heme oxygenase-1 signaling pathways - Priscila B. Rosa; Luis E. B. Bettio; Vivian B. Neis; Morgana Moretti; Isabel Werle; Rodrigo B. Leal; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2019)

Arsenic-induced neurotoxicity: a mechanistic appraisal - Carla Garza-Lombó; Aglaia Pappa; Mihalis I. Panayiotidis; María E. Gonsebatt; Rodrigo Franco (JBIC Journal of Biological Inorganic Chemistry, 2019)

Effect of alcohol use disorder on cellular aging - Luana Martins de Carvalho; Corinde E. Wiers; Peter Manza; Hui Sun; Melanie Schwandt; Gene-Jack Wang; Rodrigo Grassi-Oliveira; Ana Lúcia Brunialti Godard; Nora D. Volkow (Psychopharmacology, 2019)

Colletotrichum acutatum M11 can suppress the defence response in strawberry plants - Rodrigo H. Tomas-Grau; Pia Di Peto; Nadia R. Chalfoun; Carlos F. Grellet-Bournonville; Gustavo G. Martos; Mario Debes; Marta E. Arias; Juan C. Díaz-Ricci (Planta, 2019)

Corrigendum: Severe Continental-Scale Impacts of Climate Change Are Happening Now: Extreme Climate Events Impact Marine Habitat Forming Communities Along 45% of Australia's Coast - Russell C. Babcock; Rodrigo H. Bustamante; Elizabeth A. Fulton; Derek J. Fulton; Michael D. E. Haywood; Alistair James Hobday; Robert Kenyon; Richard James Matear; Eva E. Plagányi; Anthony J. Richardson; Mathew A. Vanderklift (Frontiers in Marine Science, 2019)

Increased DNA damage is not associated to polymorphisms in OGGI DNA repair gene, CYP2E1 detoxification gene, and biochemical and hematological findings in soybeans farmers from Central Brazil - Fernanda Ribeiro Godoy; Hugo Freire Nunes; Alessandro Arruda Alves; Wanessa Fernandes Carvalho; Fernanda Craveiro Franco; Rodrigo Roncato Pereira; Alex Silva da Cruz; Cláudio Carlos da Silva; Rogério Pereira Bastos; Daniela de Melo e Silva (Environmental Science and Pollution Research, 2019)

Severe Continental-Scale Impacts of Climate Change Are Happening Now: Extreme Climate Events Impact Marine Habitat Forming Communities Along 45% of Australia’s Coast - Russell C. Babcock; Rodrigo H. Bustamante; Elizabeth A. Fulton; Derek J. Fulton; Michael D. E. Haywood; Alistair James Hobday; Robert Kenyon; Richard James Matear; Eva E. Plagányi; Anthony J. Richardson; Mathew A. Vanderklift (Frontiers in Marine Science, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Citrus carotenoid isomerase gene characterization by complementation of the “Micro-Tom” tangerine mutant - Thaísa T. Pinheiro; Lázaro E. P. Peres; Eduardo Purgatto; Rodrigo R. Latado; Rodolfo A. Maniero; Mônica M. Martins; Antonio Figueira (Plant Cell Reports, 2019)

Treadmill Exercise Attenuates l-DOPA-Induced Dyskinesia and Increases Striatal Levels of Glial Cell-Derived Neurotrophic Factor (GDNF) in Hemiparkinsonian Mice - Ana E. Speck; Marissa G. Schamne; Aderbal S. Aguiar; Rodrigo A. Cunha; Rui D. Prediger (Molecular Neurobiology, 2019)

Forest cover drives leaf litter ant diversity in primary rainforest remnants within human-modified tropical landscapes - Diana A. Ahuatzin; Erick J. Corro; Armando Aguirre Jaimes; Jorge E. Valenzuela González; Rodrigo Machado Feitosa; Milton Cezar Ribeiro; Juan Carlos López Acosta; Rosamond Coates; Wesley Dáttilo (Biodiversity and Conservation, 2019)

Genotypic variation and relationships among traits for root morphology in a panel of tropical maize inbred lines under contrasting nitrogen levels - Lívia Gomes Torres; Diego Gonçalves Caixeta; Wemerson Mendonça Rezende; Andreia Schuster; Camila Ferreira Azevedo; Fabyano Fonseca e Silva; Rodrigo Oliveira DeLima (Euphytica, 2019)

Spatial and temporal distribution of metals in PM2.5 during 2013: assessment of wind patterns to the impacts of geogenic and anthropogenic sources - Rodrigo Garza-Galindo; Ofelia Morton-Bermea; Elizabeth Hernández-Álvarez; Sara L. Ordoñez-Godínez; Omar Amador-Muñoz; Laura E. Beramendi-Orosco; Armando Retama; Javier Miranda; Irma Rosas-Pérez (Environmental Monitoring and Assessment, 2019)

Individual and temporal variation in pathogen load predicts long‐term impacts of an emerging infectious disease - Konstans Wells; Rodrigo K. Hamede; Menna E. Jones; Paul A. Hohenlohe; Andrew Storfer; Hamish I. McCallum (Ecology, 2019)
Emerging infectious diseases increasingly threaten wildlife populations. Most studies focus on managing short‐term epidemic properties, such as controlling early outbreaks. Predicting long‐term endemic characteristics with limited retrospective data is more challenging. We used individual‐based modeling informed by individual variation in pathogen load and transmissibility to predict long‐term impacts of a lethal, transmissible cancer on Tasmanian devil ( Sarcophilus harrisii ) populations. For this, we employed approximate Bayesian computation to identify model scenarios that best matched known epidemiological and demographic system properties derived from 10 yr of data after disease emergence, enabling us to forecast future system dynamics. We show that the dramatic devil population declines observed thus far are likely attributable to transient dynamics (initial dynamics after disease emergence). Only 21% of matching scenarios led to devil extinction within 100 yr following devil facial tumor disease ( DFTD ) introduction, whereas DFTD faded out in 57% of simulations. In the remaining 22% of simulations, disease and host coexisted for at least 100 yr, usually with long‐period oscillations. Our findings show that pathogen extirpation or host–pathogen coexistence are much more likely than the DFTD ‐induced devil extinction, with crucial management ramifications. Accounting for individual‐level disease progression and the long‐term outcome of devil– DFTD interactions at the population‐level, our findings suggest that immediate management interventions are unlikely to be necessary to ensure the persistence of Tasmanian devil populations. This is because strong population declines of devils after disease emergence do not necessarily translate into long‐term population declines at equilibria. Our modeling approach is widely applicable to other host–pathogen systems to predict disease impact beyond transient dynamics.

Conserving adaptive potential: lessons from Tasmanian devils and their transmissible cancer - Paul A. Hohenlohe; Hamish I. McCallum; Menna E. Jones; Matthew F. Lawrance; Rodrigo K. Hamede; Andrew Storfer (Conservation Genetics, 2019)

Mild Exercise Differently Affects Proteostasis and Oxidative Stress on Motor Areas During Neurodegeneration: A Comparative Study of Three Treadmill Running Protocols - Karla P. Melo; Carolliny M. Silva; Michael F. Almeida; Rodrigo S. Chaves; Tania Marcourakis; Sandra M. Cardoso; Marilene Demasi; Luis E. S. Netto; Merari F. R. Ferrari (Neurotoxicity Research, 2019)

Carbon stocks and tree diversity in scattered tree silvopastoral systems in Chiapas, Mexico - Deb R. Aryal; Rogelio R. Gómez-González; Rodrigo Hernández-Nuriasmú; Danilo E. Morales-Ruiz (Agroforestry Systems, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Multi-temporal accumulation and risk assessment of available heavy metals in poultry litter fertilized soils from Rio de Janeiro upland region - Cláudio E. T. Parente; Adan S. Lino; Elias R. Arruda Junior; Everaldo Zonta; Paulo R. Dorneles; João Paulo M. Torres; Rodrigo O. Meire; Olaf Malm (Environmental Monitoring and Assessment, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Large‐effect loci affect survival in Tasmanian devils ( Sarcophilus harrisii ) infected with a transmissible cancer - Mark J. Margres; Menna E. Jones; Brendan Epstein; Douglas H. Kerlin; Sebastien Comte; Samantha Fox; Alexandra K. Fraik; Sarah A. Hendricks; Stewart Huxtable; Shelly Lachish; Billie Lazenby; Sean M. O'Rourke; et al. (Molecular Ecology, 2018)
Identifying the genetic architecture of complex phenotypes is a central goal of modern biology, particularly for disease‐related traits. Genome‐wide association methods are a classical approach for identifying the genomic basis of variation in disease phenotypes, but such analyses are particularly challenging in natural populations due to sample size difficulties. Extensive mark–recapture data, strong linkage disequilibrium and a lethal transmissible cancer make the Tasmanian devil ( Sarcophilus harrisii ) an ideal model for such an association study. We used a RAD ‐capture approach to genotype 624 devils at ~16,000 loci and then used association analyses to assess the heritability of three cancer‐related phenotypes: infection case–control (where cases were infected devils and controls were devils that were never infected), age of first infection and survival following infection. The SNP array explained much of the phenotypic variance for female survival (>80%) and female case–control (>61%). We found that a few large‐effect SNP s explained much of the variance for female survival (~5 SNP s explained >61% of the total variance), whereas more SNP s (~56) of smaller effect explained less of the variance for female case–control (~23% of the total variance). By contrast, these same SNP s did not account for a significant proportion of phenotypic variance in males, suggesting that the genetic bases of these traits and/or selection differ across sexes. Loci involved with cell adhesion and cell‐cycle regulation underlay trait variation, suggesting that the devil immune system is rapidly evolving to recognize and potentially suppress cancer growth through these pathways. Overall, our study provided necessary data for genomics‐based conservation and management in Tasmanian devils.

Invasion of Nipponaclerda biwakoensis (Hemiptera: Aclerdidae) and Phragmites australis die-back in southern Louisiana, USA - Ian A. Knight; Blake E. Wilson; Madeline Gill; Leslie Aviles; James T. Cronin; John A. Nyman; Scott A. Schneider; Rodrigo Diaz (Biological Invasions, 2018)

The Heritage Interest of the Cretaceous Amber Outcrops in the Iberian Peninsula, and Their Management and Protection - A. Rodrigo; E. Peñalver; R. López del Valle; E. Barrón; X. Delclòs (Geoheritage, 2018)

Willingness to Pay for Conservation of Transborder Migratory Species: A Case Study of the Mexican Free-Tailed Bat in the United States and Mexico - Michelle A. Haefele; John B. Loomis; Robert Merideth; Aaron Lien; Darius J. Semmens; James Dubovsky; Ruscena Wiederholt; Wayne E. Thogmartin; Ta-Ken Huang; Gary McCracken; Rodrigo A. Medellin; James E. Diffendorfer; et al. (Environmental Management, 2018)

Metabolic potential and in situ transcriptomic profiles of previously uncharacterized key microbial groups involved in coupled carbon, nitrogen and sulfur cycling in anoxic marine zones - Alvaro M. Plominsky; Nicole Trefault; Sheila Podell; Jessica M. Blanton; Rodrigo De la Iglesia; Eric E. Allen; Peter von Dassow; Osvaldo Ulloa (Environmental Microbiology, 2018)
Summary Anoxic marine zones (AMZs) impact biogeochemical cycles at the global scale, particularly the nitrogen cycle. Key microbial players from AMZs have been identified, but the majority remains unrecognized or uncharacterized. Thirty‐one single‐cell amplified genomes (SAGs) from the eastern tropical North and South Pacific AMZs were sequenced to gain insight into the distribution, metabolic potential and contribution to the community transcriptional profile of these uncharacterized bacterial and archaeal groups. Detailed analyses focused on SAG‐bins assigned to three of these groups that presented 79%–100% estimated genome completeness: the putative sulphur‐oxidizing Gamaproteobacteria EOSA II clade, a Marinimicrobia member of the recently recognized PN262000N21 clade found to be abundant in AMZ anoxic cores, and a representative of the Marine Benthic Group A Thaumarchaeota. Community‐based analyses revealed that these three groups are significantly more abundant and transcriptionally more active in the AMZ microbial communities than previously described phylogenetically related microbial groups. Collectively, these groups have the potential to link biogeochemically relevant processes by coupling the carbon, nitrogen and sulfur cycles. Together, these results increase our understanding of key microbial components inhabiting AMZs and other oxygen‐deficient marine environments, enhancing our capacity to predict the impact of the expansion of these ecosystems due to climate change.

Phylogenetic relationships in Bulbostylis (Abildgaardieae: Cyperaceae) inferred from nuclear and plastid DNA sequence data - Andrea G. Reutemann; Rodrigo E. Ardissone; María Gabriela López; Sebastián Elias Muchut; Ilsi Boldrini; Abelardo Carlos Vegetti; Liliana Mónica Giussani (Systematics and Biodiversity, 2018)

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Revisiting “Success” and “Failure” of Marine Protected Areas: A Conservation Scientist Perspective - Sylvaine Giakoumi; Jennifer McGowan; Morena Mills; Maria Beger; Rodrigo H. Bustamante; Anthony Charles; Patrick Christie; Matthew Fox; Pablo Garcia-Borboroglu; Stefan Gelcich; Paolo Guidetti; Peter Mackelworth; et al. (Frontiers in Marine Science, 2018)

The semi-synthetic molecule [4″,5″] dihydro-obovatin isolated from Tephrosia Toxicaria pers reduces zymosan-induced temporomandibular joint inflammatory hypernociception in rats - Danielle Rocha do Val; Hellíada Vasconcelos Chaves; Francisco Isaac Fernandes Gomes; Rodrigo da Silva Santos; Antonio Mateus Gomes Pereira; Igor Iuco Castro da Silva; Vicente de Paulo Teixeira Pinto; Lissiana Magna Vasconcelos Aguiar; Norma Maria Barros Benevides; Francisca Renata Lopes da Silva; Jair Mafezoli; Jackson Nunes e Vasconcelos; et al. (Medicinal Chemistry Research, 2018)

In search of a meaningful classification for Amazonian marmosets: Should dwarf marmosets be considered Mico congenerics? - Felipe E. Silva; Rodrigo Costa‐Araújo; Jean P. Boubli; Marcelo I. Santana; Caetano L. B. Franco; Fabrício Bertuol; Hermano Nunes; José de Souza Silva‐Júnior; Izeni Farias; Tomas Hrbek (Zoologica Scripta, 2018)
The criteria to classify the diversity of Neotropical Primates have recently taken the discussion boards due to the reappraisal on the phylogenetic relationship of some groups. Such controversial and arbitrary decisions, however, can hamper conservation actions in as much as it becomes difficult to prioritise and set meaningful targets. It is the case for dwarf marmosets from central Amazonia. Today, the classification of dwarf marmosets in Mico or Callibella genus has not been satisfactorily settled. Aiming to contribute to the taxonomic and conservation assessment of dwarf marmosets, we conducted new data collection during 3‐year fieldwork in the Aripuanã River, where the species was discovered. We present the first phylogenomic analysis of the evolutionary relationships between marmosets, new data from mitochondrial DNA and morphology, as well new records to clarify geographic distribution. With this new evidence, we support dwarf marmosets as the genus Callibella . We further discuss the implications for the conservation of this marmoset.

Networking our science to characterize the state, vulnerabilities, and management opportunities of soil organic matter - Jennifer W. Harden; Gustaf Hugelius; Anders Ahlström; Joseph C. Blankinship; Ben Bond‐Lamberty; Corey R. Lawrence; Julie Loisel; Avni Malhotra; Robert B. Jackson; Stephen Ogle; Claire Phillips; Rebecca Ryals; et al. (Global Change Biology, 2018)
Soil organic matter ( SOM ) supports the Earth's ability to sustain terrestrial ecosystems, provide food and fiber, and retains the largest pool of actively cycling carbon. Over 75% of the soil organic carbon ( SOC ) in the top meter of soil is directly affected by human land use. Large land areas have lost SOC as a result of land use practices, yet there are compensatory opportunities to enhance productivity and SOC storage in degraded lands through improved management practices. Large areas with and without intentional management are also being subjected to rapid changes in climate, making many SOC stocks vulnerable to losses by decomposition or disturbance. In order to quantify potential SOC losses or sequestration at field, regional, and global scales, measurements for detecting changes in SOC are needed. Such measurements and soil‐management best practices should be based on well established and emerging scientific understanding of processes of C stabilization and destabilization over various timescales, soil types, and spatial scales. As newly engaged members of the International Soil Carbon Network, we have identified gaps in data, modeling, and communication that underscore the need for an open, shared network to frame and guide the study of SOM and SOC and their management for sustained production and climate regulation.

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Phytochemistry and biological properties of Aristotelia chilensis a Chilean blackberry: a review - Gustavo E. Zúñiga; Andrea Tapia; Andrea Arenas; Rodrigo A. Contreras; Gustavo Zúñiga-Libano (Phytochemistry Reviews, 2017)

Implementing genomic selection in sour passion fruit population - Alexandre Pio Viana; Fernando Higino de Lima e Silva; Leonardo Siqueira Glória; Rodrigo Moreira Ribeiro; Willian Krause; Marcela Santana Bastos Boechat (Euphytica, 2017)

CO 2 exchange and evapotranspiration across dryland ecosystems of southwestern North America - Joel A. Biederman; Russell L. Scott; Tom W. Bell; David R. Bowling; Sabina Dore; Jaime Garatuza‐Payan; Thomas E. Kolb; Praveena Krishnan; Dan J. Krofcheck; Marcy E. Litvak; Gregory E. Maurer; Tilden P. Meyers; et al. (Global Change Biology, 2017)
Global‐scale studies suggest that dryland ecosystems dominate an increasing trend in the magnitude and interannual variability of the land CO 2 sink. However, such analyses are poorly constrained by measured CO 2 exchange in drylands. Here we address this observation gap with eddy covariance data from 25 sites in the water‐limited Southwest region of North America with observed ranges in annual precipitation of 100–1000 mm, annual temperatures of 2–25°C, and records of 3–10 years (150 site‐years in total). Annual fluxes were integrated using site‐specific ecohydrologic years to group precipitation with resulting ecosystem exchanges. We found a wide range of carbon sink/source function, with mean annual net ecosystem production ( NEP ) varying from ‐350 to +330 gC m −2 across sites with diverse vegetation types, contrasting with the more constant sink typically measured in mesic ecosystems. In this region, only forest‐dominated sites were consistent carbon sinks. Interannual variability of NEP , gross ecosystem production ( GEP ), and ecosystem respiration (R eco ) was larger than for mesic regions, and half the sites switched between functioning as C sinks/C sources in wet/dry years. The sites demonstrated coherent responses of GEP and NEP to anomalies in annual evapotranspiration ( ET ), used here as a proxy for annually available water after hydrologic losses. Notably, GEP and R eco were negatively related to temperature, both interannually within site and spatially across sites, in contrast to positive temperature effects commonly reported for mesic ecosystems. Models based on MODIS satellite observations matched the cross‐site spatial pattern in mean annual GEP but consistently underestimated mean annual ET by ~50%. Importantly, the MODIS ‐based models captured only 20–30% of interannual variation magnitude. These results suggest the contribution of this dryland region to variability of regional to global CO 2 exchange may be up to 3–5 times larger than current estimates.

Mice exposure to tannery effluents changes their olfactory capacity, and their response to predators and to the inhibitory avoidance test - Bruna de Oliveira Mendes; Letícia Martins Rabelo; Bianca Costa e Silva; Joyce Moreira de Souza; André Luis da Silva Castro; Anderson Rodrigo da Silva; Aline Sueli de Lima Rodrigues; Guilherme Malafaia (Environmental Science and Pollution Research, 2017)

Occupational and life-style factors-acquired mutagenicity in agric-workers of northeastern Brazil - Tatiana Vieira Souza Chaves; Muhammad Torequl Islam; Manoel Odoríco de Moraes; Marcus Vinícius Oliveira Barros de Alencar; Débora Cássia Vieira Gomes; Rodrigo Mendes de Carvalho; Sharbel Weider Maluf; Fabrício Pires de Moura do Amaral; Márcia Fernanda Correia Jardim Paz; Gilberto Santos Cerqueira; Hercília Maria Lins Rolim; João Marcelo de Castro e Sousa; et al. (Environmental Science and Pollution Research, 2017)

Infection of the fittest: devil facial tumour disease has greatest effect on individuals with highest reproductive output - Konstans Wells; Rodrigo K. Hamede; Douglas H. Kerlin; Andrew Storfer; Paul A. Hohenlohe; Menna E. Jones; Hamish I. McCallum (Ecology Letters, 2017)
Emerging infectious diseases rarely affect all members of a population equally and determining how individuals’ susceptibility to infection is related to other components of their fitness is critical to understanding disease impacts at a population level and for predicting evolutionary trajectories. We introduce a novel state‐space model framework to investigate survival and fecundity of Tasmanian devils ( Sarcophilus harrisii ) affected by a transmissible cancer, devil facial tumour disease. We show that those devils that become host to tumours have otherwise greater fitness, with higher survival and fecundity rates prior to disease‐induced death than non‐host individuals that do not become infected, although high tumour loads lead to high mortality. Our finding that individuals with the greatest reproductive value are those most affected by the cancer demonstrates the need to quantify both survival and fecundity in context of disease progression for understanding the impact of disease on wildlife populations.

Phosphorus and potassium cycling in a long-term no-till integrated soybean-beef cattle production system under different grazing intensities insubtropics - Joice Mari Assmann; Amanda Posselt Martins; Ibanor Anghinoni; Luiz Gustavo de Oliveira Denardin; Gabriela de Holanda Nichel; Sérgio Ely V. G. de Andrade Costa; Rodrigo André Pereira e Silva; Fabrício Balerini; Paulo César de Faccio Carvalho; Alan Joseph Franzluebbers (Nutrient Cycling in Agroecosystems, 2017)

Labeling of adipose-derived stem cells with quantum dots provides stable and long-term fluorescent signal for ex vivo cell tracking - Clautina R. M. Costa; Matheus L. T. Feitosa; Dayseanny O. Bezerra; Yulla K. P. Carvalho; Rodrigo F. G. Olivindo; Pablo B. Fernando; Gustavo C. Silva; Mirna L. G. Silva; Carlos E. Ambrósio; Airton M. Conde Júnior; Napoleão M. Argolo Neto; Laís M. Costa Silva; et al. (In Vitro Cellular & Developmental Biology - Animal, 2017)

Mutations in chromatin regulators functionally link Cornelia de Lange syndrome and clinically overlapping phenotypes - Ilaria Parenti; María E. Teresa-Rodrigo; Jelena Pozojevic; Sara Ruiz Gil; Ingrid Bader; Diana Braunholz; Nuria C. Bramswig; Cristina Gervasini; Lidia Larizza; Lutz Pfeiffer; Ferda Ozkinay; Feliciano Ramos; et al. (Human Genetics, 2017)

Anxiety and memory deficits induced by tannery effluent in C57BL/6J female mice - Abraão Tiago Batista Guimarães; Raissa de Oliveira Ferreira; Joyce Moreira de Souza; Wellington Alves Mizael da Silva; Anderson Rodrigo da Silva; Aline Sueli de LimaRodrigues; Daniela de Melo e Silva; Renata Mazaro e Costa; André Luis da Silva Castro; Guilherme Malafaia (Environmental Science and Pollution Research, 2016)

Copy number variations and genome-wide associations reveal putative genes and metabolic pathways involved with the feed conversion ratio in beef cattle - Miguel Henrique de Almeida Santana; Gerson Antônio Oliveira Junior; Aline Silva Mello Cesar; Mateus Castelani Freua; Rodrigo da Costa Gomes; Saulo da Luz e Silva; Paulo Roberto Leme; Heidge Fukumasu; Minos Esperândio Carvalho; Ricardo Vieira Ventura; Luiz Lehmann Coutinho; Haja N. Kadarmideen; et al. (Journal of Applied Genetics, 2016)

New compositions of the materials from cellulose industry wastes - Vsévolod Mymrin; Daniel F. Cusma; André Nagalli; Andréia Pichorim; Rodrigo E. Catai; Urivald Pawlowsky (Clean Technologies and Environmental Policy, 2016)

Invasive gorse (Ulex europaeus, Fabaceae) changes plant community structure in subtropical forest–grassland mosaics of southern Brazil - Rodrigo León Cordero; Fábio P. Torchelsen; Gerhard E. Overbeck; Madhur Anand (Biological Invasions, 2016)

Terrestrial carbon balance in a drier world: the effects of water availability in southwestern North America - Joel A. Biederman; Russell L. Scott; Michael L. Goulden; Rodrigo Vargas; Marcy E. Litvak; Thomas E. Kolb; Enrico A. Yepez; Walter C. Oechel; Peter D. Blanken; Tom W. Bell; Jaime Garatuza‐Payan; Gregory E. Maurer; et al. (Global Change Biology, 2016)
Global modeling efforts indicate semiarid regions dominate the increasing trend and interannual variation of net CO 2 exchange with the atmosphere, mainly driven by water availability. Many semiarid regions are expected to undergo climatic drying, but the impacts on net CO 2 exchange are poorly understood due to limited semiarid flux observations. Here we evaluated 121 site‐years of annual eddy covariance measurements of net and gross CO 2 exchange (photosynthesis and respiration), precipitation, and evapotranspiration ( ET ) in 21 semiarid North American ecosystems with an observed range of 100 – 1000 mm in annual precipitation and records of 4–9 years each. In addition to evaluating spatial relationships among CO 2 and water fluxes across sites, we separately quantified site‐level temporal relationships, representing sensitivity to interannual variation. Across the climatic and ecological gradient, photosynthesis showed a saturating spatial relationship to precipitation, whereas the photosynthesis– ET relationship was linear, suggesting ET was a better proxy for water available to drive CO 2 exchanges after hydrologic losses. Both photosynthesis and respiration showed similar site‐level sensitivity to interannual changes in ET among the 21 ecosystems. Furthermore, these temporal relationships were not different from the spatial relationships of long‐term mean CO 2 exchanges with climatic ET . Consequently, a hypothetical 100‐mm change in ET , whether short term or long term, was predicted to alter net ecosystem production ( NEP ) by 64 gC m −2 yr −1 . Most of the unexplained NEP variability was related to persistent, site‐specific function, suggesting prioritization of research on slow‐changing controls. Common temporal and spatial sensitivity to water availability increases our confidence that site‐level responses to interannual weather can be extrapolated for prediction of CO 2 exchanges over decadal and longer timescales relevant to societal response to climate change.

Impact of plant domestication on rhizosphere microbiome assembly and functions - Juan E. Pérez-Jaramillo; Rodrigo Mendes; Jos M. Raaijmakers (Plant Molecular Biology, 2016)

Genetic background of novel sequence types of CTX-M-8- and CTX-M-15-producing Escherichia coli and Klebsiella pneumoniae from public wastewater treatment plants in São Paulo, Brazil - Milena Dropa; Nilton Lincopan; Livia C. Balsalobre; Danielle E. Oliveira; Rodrigo A. Moura; Miriam Rodriguez Fernandes; Quézia Moura da Silva; Glavur R. Matté; Maria I. Z. Sato; Maria H. Matté (Environmental Science and Pollution Research, 2016)

Field Survey of the 2015 Chile Tsunami with Emphasis on Coastal Wetland and Conservation Areas - Manuel Contreras-López; Patricio Winckler; Ignacio Sepúlveda; Adolfo Andaur-Álvarez; Fernanda Cortés-Molina; Camila J. Guerrero; Cyntia E. Mizobe; Felipe Igualt; Wolfgang Breuer; José F. Beyá; Hernán Vergara; Rodrigo Figueroa-Sterquel (Pure and Applied Geophysics, 2016)

Silencing of Gonad-Inhibiting Hormone Transcripts in Litopenaeus vannamei Females by use of the RNA Interference Technology - Rubens G. Feijó; André L. Braga; Carlos F. C. Lanes; Márcio A. Figueiredo; Luis A. Romano; Marta C. Klosterhoff; Luis E. M. Nery; Rodrigo Maggioni; Wilson Wasielesky; Luis F. Marins (Marine Biotechnology, 2016)

Infrared thermography as a tool to evaluate body surface temperature and its relationship with feed efficiency in Bos indicus cattle in tropical conditions - Luciane Silva Martello; Saulo da Luz e Silva; Rodrigo da Costa Gomes; Rosana Ruegger Pereira da Silva Corte; Paulo Roberto Leme (International Journal of Biometeorology, 2016)

Long‐term elevated air [ CO 2 ] strengthens photosynthetic functioning and mitigates the impact of supra‐optimal temperatures in tropical Coffea arabica and C. canephora species - Weverton P. Rodrigues; Madlles Q. Martins; Ana S. Fortunato; Ana P. Rodrigues; José N. Semedo; Maria C. Simões‐Costa; Isabel P. Pais; António E. Leitão; Filipe Colwell; Luis Goulao; Cristina Máguas; Rodrigo Maia; et al. (Global Change Biology, 2016)
The tropical coffee crop has been predicted to be threatened by future climate changes and global warming. However, the real biological effects of such changes remain unknown. Therefore, this work aims to link the physiological and biochemical responses of photosynthesis to elevated air [ CO 2 ] and temperature in cultivated genotypes of C offea arabica L. (cv. Icatu and IPR 108) and Coffea canephora cv. Conilon CL 153. Plants were grown for ca. 10 months at 25/20 °C (day/night) and 380 or 700 μl CO 2 l −1 and then subjected to temperature increase (0.5 °C day −1 ) to 42/34 °C. Leaf impacts related to stomatal traits, gas exchanges, C isotope composition, fluorescence parameters, thylakoid electron transport and enzyme activities were assessed at 25/20, 31/25, 37/30 and 42/34 °C. The results showed that (1) both species were remarkably heat tolerant up to 37/30 °C, but at 42/34 °C a threshold for irreversible nonstomatal deleterious effects was reached. Impairments were greater in C. arabica (especially in Icatu) and under normal [ CO 2 ]. Photosystems and thylakoid electron transport were shown to be quite heat tolerant, contrasting to the enzymes related to energy metabolism, including RuBis CO , which were the most sensitive components. (2) Significant stomatal trait modifications were promoted almost exclusively by temperature and were species dependent. Elevated [ CO 2 ], (3) strongly mitigated the impact of temperature on both species, particularly at 42/34 °C, modifying the response to supra‐optimal temperatures, (4) promoted higher water‐use efficiency under moderately higher temperature (31/25 °C) and (5) did not provoke photosynthetic downregulation. Instead, enhancements in [ CO 2 ] strengthened photosynthetic photochemical efficiency, energy use and biochemical functioning at all temperatures. Our novel findings demonstrate a relevant heat resilience of coffee species and that elevated [ CO 2 ] remarkably mitigated the impact of heat on coffee physiology, therefore playing a key role in this crop sustainability under future climate change scenarios.

Wood density, but not leaf hydraulic architecture, is associated with drought tolerance in clones of Coffea canephora - Paulo E. Menezes-Silva; Paulo C. Cavatte; Samuel C. V. Martins; Josimar V. Reis; Lucas F. Pereira; Rodrigo T. Ávila; Andréa L. Almeida; Marília C. Ventrella; Fábio M. DaMatta (Trees, 2015)

Ozone, nitrogen oxides, and volatile organic compounds in a central zone of Chile - Richard Toro A.; Rodrigo J. Seguel; Raúl G. E. Morales S.; Manuel A. Leiva G. (Air Quality, Atmosphere & Health, 2015)

Meta‐analysis of anthropogenic habitat disturbance effects on animal‐mediated seed dispersal - Francisco E. Fontúrbel; Alina B. Candia; Javiera Malebrán; Daniela A. Salazar; Catalina González‐Browne; Rodrigo Medel (Global Change Biology, 2015)
Anthropogenic habitat disturbance is a strong biodiversity change driver that compromises not only the species persistence but also the ecological interactions in which they are involved. Even though seed dispersal is a key interaction involved in the recruitment of many tree species and in consequence critical for biodiversity maintenance, studies assessing the effect of different anthropogenic disturbance drivers on this interaction have not been performed under a meta‐analytical framework. We assessed the way habitat fragmentation and degradation processes affect species diversity (abundance and species richness) and interaction rates (i.e., fruit removal and visitation rates) of different groups of seed‐disperser species at a global scale. We obtained 163 case studies from 37 articles. Results indicate that habitat degradation had a negative effect on seed‐disperser animal diversity, whereas habitat fragmentation had a negative effect on interaction rates. Birds and insects were more sensitive in terms of their diversity, whereas mammals showed a negative effect on interaction rates. Regarding habitat, both fragmentation and degradation had a negative effect on seed‐disperser animal diversity only in temperate habitats, and negative effects on interaction rates in tropical and temperate habitats. Our results indicate that the impact of human disturbance on seed‐disperser species and interactions is not homogeneous. On the contrary, the magnitude of effects seems to be dependent on the type of disturbance, taxonomic group under assessment, and geographical region where the human impact occurs.

Microbial and sponge loops modify fish production in phase‐shifting coral reefs - Cynthia B. Silveira; Arthur W. Silva‐Lima; Ronaldo B. Francini‐Filho; Jomar S.M. Marques; Marcelo G. Almeida; Cristiane C. Thompson; Carlos E. Rezende; Rodolfo Paranhos; Rodrigo L. Moura; Paulo S. Salomon; Fabiano L. Thompson (Environmental Microbiology, 2015)
Summary Shifts from coral to algae dominance of corals reefs have been correlated to fish biomass loss and increased microbial metabolism. Here we investigated reef benthic and planktonic primary production, benthic dissolved organic carbon ( DOC ) release and bacterial growth efficiency in the A brolhos B ank, S outh A tlantic. Benthic DOC release rates are higher while water column bacterial growth efficiency is lower at impacted reefs. A trophic model based on the benthic and planktonic primary production was able to predict the observed relative fish biomass in healthy reefs. In contrast, in impacted reefs, the observed omnivorous fish biomass is higher, while that of the herbivorous/coralivorous fish is lower than predicted by the primary production‐based model. Incorporating recycling of benthic‐derived carbon in the model through microbial and sponge loops explains the difference and predicts the relative fish biomass in both reef types. Increased benthic carbon release rates and bacterial carbon metabolism, but decreased bacterial growth efficiency could lead to carbon losses through respiration and account for the uncoupling of benthic and fish production in phase‐shifting reefs. Carbon recycling by microbial and sponge loops seems to promote an increase of small‐bodied fish productivity in phase‐shifting coral reefs.

Exploring origins, invasion history and genetic diversity of Imperata cylindrica (L.) P. Beauv. (Cogongrass) in the United States using genotyping by sequencing - A. Millie Burrell; Alan E. Pepper; George Hodnett; John A. Goolsby; William A. Overholt; Alexis E. Racelis; Rodrigo Diaz; Patricia E. Klein (Molecular Ecology, 2015)
I mperata cylindrica (Cogongrass, Speargrass) is a diploid C4 grass that is a noxious weed in 73 countries and constitutes a significant threat to global biodiversity and sustainable agriculture. We used a cost‐effective genotyping‐by‐sequencing ( GBS ) approach to identify the reproductive system, genetic diversity and geographic origins of invasions in the south‐eastern United States. In this work, we demonstrated the advantage of employing the closely related, fully sequenced crop species S orghum bicolor (L.) Moench as a proxy reference genome to identify a set of 2320 informative single nucleotide and insertion–deletion polymorphisms. Genetic analyses identified four clonal lineages of cogongrass and one clonal lineage of I mperata brasiliensis Trin. in the United States. Each lineage was highly homogeneous, and we found no evidence of hybridization among the different lineages, despite geographical overlap. We found evidence that at least three of these lineages showed clonal reproduction prior to introduction to the United States. These results indicate that cogongrass has limited evolutionary potential to adapt to novel environments and further suggest that upon arrival to its invaded range, this species did not require local adaptation through hybridization/introgression or selection of favourable alleles from a broad genetic base. Thus, cogongrass presents a clear case of broad invasive success, across a diversity of environments, in a clonal organism with limited genetic diversity.

Facing the wave of change: stakeholder perspectives on climate adaptation for Australian seafood supply chains - Lilly Lim-Camacho; Alistair J. Hobday; Rodrigo H. Bustamante; Anna Farmery; Aysha Fleming; Stewart Frusher; Bridget S. Green; Ana Norman-López; Gretta T. Pecl; Éva E. Plagányi; Peggy Schrobback; Olivier Thebaud; et al. (Regional Environmental Change, 2015)

Early abstinence of crack-cocaine is effective to attenuate oxidative stress and to improve antioxidant defences - Aline Zaparte; Thiago W. Viola; Rodrigo Grassi-Oliveira; Maurilio da Silva Morrone; José C. Moreira; Moisés E. Bauer (Psychopharmacology, 2015)

D-serine plasma concentration is a potential biomarker of (R,S)-ketamine antidepressant response in subjects with treatment-resistant depression - Ruin Moaddel; David A. Luckenbaugh; Ying Xie; Alma Villaseñor; Nancy E. Brutsche; Rodrigo Machado-Vieira; Anuradha Ramamoorthy; Maria Paz Lorenzo; Antonia Garcia; Michel Bernier; Marc C. Torjman; Coral Barbas; et al. (Psychopharmacology, 2015)

Optimizing conservation strategies for Mexican free-tailed bats: a population viability and ecosystem services approach - Ruscena Wiederholt; Laura López-Hoffman; Colleen Svancara; Gary McCracken; Wayne Thogmartin; Jay E. Diffendorfer; Brady Mattson; Kenneth Bagstad; Paul Cryan; Amy Russell; Darius Semmens; Rodrigo A. Medellín (Biodiversity and Conservation, 2015)

Niche similarities among white‐eared opossums (Mammalia, Didelphidae): Is ecological niche modelling relevant to setting species limits? - Luana J. Tocchio; Rodrigo Gurgel‐Gonçalves; Luis E. Escobar; Andrew Townsend Peterson (Zoologica Scripta, 2015)
A complex of white‐eared opossums ( Didelphis spp.) is distributed across three distinct areas of South America, but recent taxonomic treatments have disagreed regarding species limits in the group. We used ecological niche modelling to test whether ecological niches have been conserved or have diverged among the three forms in this group. Differences in combinations of niche and range were clear; however, when hypotheses of accessible areas for each species were considered, coarse‐grained niche dimensions (i.e. climatic dimensions) were seen not to differ across the complex. We discuss implications of these results for taxonomic recognition of species based on geographic and ecological characteristics and the implications of using ENM approaches to setting species limits. We suggest that ENM should be used to explore speciation mechanisms, rather than being applied to questions of setting species limits.

Assessment of tolerance to bud rot in oil palm under field conditions - Edwin A. Navia; Rodrigo A. Ávila; Edison E. Daza; Edwin F. Restrepo; Hernán Mauricio Romero (European Journal of Plant Pathology, 2014)

Comparison of Commercial Methods and the CLSI Broth Microdilution to Determine the Antifungal Susceptibility of Candida parapsilosis Complex Bloodstream Isolates from Three Health Institutions in Rio de Janeiro, Brazil - Maria Helena G. Figueiredo-Carvalho; Leonardo S. Barbedo; Manoel M. E. Oliveira; Fábio Brito-Santos; Rodrigo Almeida-Paes; Rosely M. Zancopé-Oliveira (Mycopathologia, 2014)

Influence of tea tree oil (Melaleuca alternifolia) on the cattle tick Rhipicephalus microplus - Rafael Pazinato; Vanderlei Klauck; Andreia Volpato; Alexandre A. Tonin; Roberto C. Santos; Márcia E. de Souza; Rodrigo A. Vaucher; Renata Raffin; Patrícia Gomes; Candice C. Felippi; Lenita M. Stefani; Aleksandro S. Da Silva (Experimental and Applied Acarology, 2014)

Suitability of oil bioremediation in an Artic soil using surplus heating from an incineration facility - Nazaré Couto; Janne Fritt-Rasmussen; Pernille E. Jensen; Mads Højrup; Ana P. Rodrigo; Alexandra B. Ribeiro (Environmental Science and Pollution Research, 2014)

Lectin of Abelmoschus esculentus (okra) promotes selective antitumor effects in human breast cancer cells - Leonardo G. Monte; Tatiane Santi-Gadelha; Larissa B. Reis; Elizandra Braganhol; Rafael F. Prietsch; Odir A. Dellagostin; Rodrigo Rodrigues e Lacerda; Carlos A. A. Gadelha; Fabricio R. Conceição; Luciano S. Pinto (Biotechnology Letters, 2014)

Photochemical ozone pollution in the Valparaiso Region, Chile - Richard A. Toro; Camila S. Donoso; Rodrigo A. Seguel; Raúl G. E. S. Morales; Manuel A. G. Leiva (Air Quality, Atmosphere & Health, 2014)

Tadalafil-induced improvement in left ventricular diastolic function in resistant hypertension - Rodrigo C. Santos; Ana Paula C. de Faria; Natália R. Barbaro; Rodrigo Modolo; Silvia E. Ferreira-Melo; José R. Matos-Souza; Otávio R. Coelho; Juan C. Yugar-Toledo; Vanessa Fontana; David Calhoun; Heitor Moreno (European Journal of Clinical Pharmacology, 2014)

Effect of climatic variables and vine crops on the epigeic ant fauna (Hymenoptera: Formicidae) in the Campanha region, state of Rio Grande do Sul, Brazil - João Luis Osório Rosado; Michel Gonçalves de Gonçalves; William Dröse; Eduardo José Ely e Silva; Rodrigo Ferreira Krüger; Alci Enimar Loeck (Journal of Insect Conservation, 2013)

Reduced total genetic diversity following translocations? A metapopulation approach - A. H. Thrimawithana; L. Ortiz-Catedral; A. Rodrigo; M. E. Hauber (Conservation Genetics, 2013)

Response of Neotropical Bat Assemblages to Human Land Use - RODRIGO GARCÍA‐MORALES; ERNESTO I. BADANO; CLAUDIA E. MORENO (Conservation Biology, 2013)
Neotropical bats are sensitive to human‐induced habitat changes, and some authors believe bats can be used as bioindicators. In the literature, however, the results are disparate. Some results show bat diversity deceases as disturbance increases, whereas others indicate no effect. Determining the general response patterns of bats when they encounter different degrees of human‐induced disturbance across the Neotropics would help to determine their usefulness as bioindicators. In a series of meta‐analyses, we compared the occurrence frequency of bat species between well‐preserved forests and human‐use areas. We obtained data through an extensive review of published peer‐reviewed articles, theses, and reports. The overall effect size indicated that human‐use areas harbored more bat species than well‐preserved forests. Different response patterns emerged when meta‐analyses were conducted separately by family, feeding habit, vegetation stratum, and conservation status. Our results suggest that bat assemblages display strong responses to forest loss and land‐use change and that the direction and magnitude of these responses depends on the bat group under study and the type of disturbance. Our results are consistent with the idea that bats are useful for assessing the effects of habitat changes in the Neotropics. However, with our meta‐analyses we could not detect fine differences in bat feeding habits, especially within Phyllostomidae, or elucidate the effect of landscape configuration. Respuesta de Ensambles de Murciélagos Neotropicales al Uso de Suelo por Humanos

Leaf phenology is associated with soil water availability and xylem traits in a tropical dry forest - Rodrigo Méndez-Alonzo; Fernando Pineda-García; Horacio Paz; Julieta A. Rosell; Mark E. Olson (Trees, 2013)

Plant-derived essential oils affecting settlement and oviposition of Bemisia tabaci (Genn.) biotype B on tomato - Edson L. L. Baldin; Antônio E. M. Crotti; Kamila A. L. Wakabayashi; José P. G. F. Silva; Gabriela P. Aguiar; Efrain S. Souza; Rodrigo C. S. Veneziani; Milton Groppo (Journal of Pest Science, 2013)

Ixodid fauna and zoonotic agents in ticks from dogs: first report of Rickettsia rickettsii in Rhipicephalus sanguineus in the state of Mato Grosso do Sul, mid-western Brazil - Robson Ferreira Cavalcante de Almeida; Marcos Valério Garcia; Rodrigo Casquero Cunha; Jaqueline Matias; Elaine Araújo e Silva; Maria de Fatima Cepa Matos; Renato Andreotti (Experimental and Applied Acarology, 2013)

Testing for Natural Selection in Human Exonic Splicing Regulators Associated with Evolutionary Rate Shifts - Rodrigo F. Ramalho; Sahar Gelfman; Jorge E. de Souza; Gil Ast; Sandro J. de Souza; Diogo Meyer (Journal of Molecular Evolution, 2013)

Depression-like behavior is dependent on age in male SAMP8 mice - D. Pérez-Cáceres; A. Ciudad-Roberts; M. T. Rodrigo; D. Pubill; A. Camins; J. Camarasa; E. Escubedo; M. Pallàs (Biogerontology, 2013)

Coordinated evolution of leaf and stem economics in tropical dry forest trees - Rodrigo Méndez-Alonzo; Horacio Paz; Rossana Cruz Zuluaga; Julieta A. Rosell; Mark E. Olson (Ecology, 2012)
With data from 15 species in eight families of tropical dry forest trees, we provide evidence of coordination between the stem and leaf economic spectra. Species with low‐density, flexible, breakable, hydraulically efficient but cavitationally vulnerable wood shed their leaves rapidly in response to drought and had low leaf mass per area and dry mass content. In contrast, species with the opposite xylem syndrome shed their costlier but more drought‐resistant leaves late in the dry season. Our results explain variation in the timing of leaf shedding in tropical dry forests: selection eliminates combinations such as low‐productivity leaves atop highly vulnerable xylem or water‐greedy leaves supplied by xylem of low conductive efficiency. Across biomes, rather than a fundamental trade‐off underlying a single axis of trait covariation, the relationship between leaf and stem economics is likely to occupy a wide space in which multiple combinations are possible.

Evaluation of the Influence of Natural and Antrhopogenic Processes on Water Quality in Karstic Region - Maria Lúcia Calijuri; Eduardo de Aguiar do Couto; Aníbal da Fonseca Santiago; Rodrigo de Arruda Camargo; Marcos D. F. M. e Silva (Water, Air, & Soil Pollution, 2012)

Connectivity and population subdivision at the fringe of a large brown bear (Ursus arctos) population in North Western Europe - Alexander Kopatz; Hans Geir Eiken; Snorre B. Hagen; Minna Ruokonen; Rodrigo Esparza-Salas; Julia Schregel; Ilpo Kojola; Martin E. Smith; Ingvild Wartiainen; Paul E. Aspholm; Steinar Wikan; Alexander M. Rykov; et al. (Conservation Genetics, 2012)

Precipitation variability and fire influence the temporal dynamics of soil CO 2 efflux in an arid grassland - Rodrigo Vargas; Scott L. Collins; Michell L. Thomey; Jennifer E. Johnson; Renee F. Brown; Donald O. Natvig; Michael T. Friggens (Global Change Biology, 2012)
Climate models suggest that extreme rainfall events will become more common with increased atmospheric warming. Consequently, changes in the size and frequency of rainfall will influence biophysical drivers that regulate the strength and timing of soil CO 2 efflux – a major source of terrestrial carbon flux. We used a rainfall manipulation experiment during the summer monsoon season ( J uly– S eptember) to vary both the size and frequency of precipitation in an arid grassland 2 years before and 2 years after a lightning‐caused wildfire. Soil CO 2 efflux rates were always higher under increased rainfall event size than under increased rainfall event frequency, or ambient precipitation. Although fire reduced soil CO 2 efflux rates by nearly 70%, the overall responses to rainfall variability were consistent before and after the fire. The overall sensitivity of soil CO 2 efflux to temperature ( Q 10 ) converged to 1.4, but this value differed somewhat among treatments especially before the fire. Changes in rainfall patterns resulted in differences in the periodicity of soil CO 2 efflux with strong signals at 1, 8, and 30 days. Increased rainfall event size enhanced the synchrony between photosynthetically active radiation and soil CO 2 efflux over the growing season before and after fire, suggesting a change in the temporal availability of substrate pools that regulate the temporal dynamics and magnitude of soil CO 2 efflux. We conclude that arid grasslands are capable of rapidly increasing and maintaining high soil CO 2 efflux rates in response to increased rainfall event size more than increased rainfall event frequency both before and after a fire. Therefore, the amount and pattern of multiple rain pulses over the growing season are crucial for understanding CO 2 dynamics in burned and unburned water‐limited ecosystems.

Ventilation rates indicate stress-coping styles in Nile tilapia - Rodrigo E Barreto; Gilson L Volpato (Journal of Biosciences, 2011)

Field Survey of the 27 February 2010 Chile Tsunami - Hermann M. Fritz; Catherine M. Petroff; Patricio A. Catalán; Rodrigo Cienfuegos; Patricio Winckler; Nikos Kalligeris; Robert Weiss; Sergio E. Barrientos; Gianina Meneses; Carolina Valderas-Bermejo; Carl Ebeling; Athanassios Papadopoulos; et al. (Pure and Applied Geophysics, 2011)

GH overexpression causes muscle hypertrophy independent from local IGF-I in a zebrafish transgenic model - Rafael Y. Kuradomi; Márcio A. Figueiredo; Carlos F. C. Lanes; Carlos E. da Rosa; Daniela V. Almeida; Rodrigo Maggioni; Maeli D. P. Silva; Luis F. Marins (Transgenic Research, 2011)

Serological Evidence of Paracoccidioides brasiliensis Infection in Chickens from Paraná and Mato Grosso do Sul States, Brazil - Gabriela G. Oliveira; Luciane H. Silveira; Eiko N. Itano; Rodrigo M. Soares; Roberta L. Freire; Maria A. E. Watanabe; Zoilo P. Camargo; Mario A. Ono (Mycopathologia, 2011)

DTI-MR tractography of white matter damage in stroke patients with neglect - M. Urbanski; M. Thiebaut de Schotten; S. Rodrigo; C. Oppenheim; E. Touzé; J.-F. Méder; K. Moreau; C. Loeper-Jeny; B. Dubois; P. Bartolomeo (Experimental Brain Research, 2011)

El Niño, grazers and fisheries interact to greatly elevate extinction risk for Galapagos marine species - GRAHAM J. EDGAR; STUART A. BANKS; MARGARITA BRANDT; RODRIGO H. BUSTAMANTE; ANGEL CHIRIBOGA; SYLVIA A. EARLE; LAUREN E. GARSKE; PETER W. GLYNN; JACK S. GROVE; SCOTT HENDERSON; CLEVE P. HICKMAN; KATHY A. MILLER; et al. (Global Change Biology, 2010)
Comparisons between historical and recent ecological datasets indicate that shallow reef habitats across the central Galapagos Archipelago underwent major transformation at the time of the severe 1982/1983 El Niño warming event. Heavily grazed reefs with crustose coralline algae (‘urchin barrens’) replaced former macroalgal and coral habitats, resulting in large local and regional declines in biodiversity. Following recent threat assessment workshops, a total of five mammals, six birds, five reptiles, six fishes, one echinoderm, seven corals, six brown algae and nine red algae reported from coastal environments in Galapagos are now recognized as globally threatened. The 2008 International Union for the Conservation of Nature (IUCN) Red List includes 43 of these species, while two additional species (Galapagos damsel Azurina eupalama and 24‐rayed sunstar Heliaster solaris ) not seen for > 25 years also fulfil IUCN threatened species criteria. Two endemic species (Galapagos stringweed Bifurcaria galapagensis and the damselfish A. eupalama ) are now regarded as probably extinct, while an additional six macroalgal species ( Dictyota galapagensis, Spatoglossum schmittii, Desmarestia tropica, Phycodrina elegans, Gracilaria skottsbergii and Galaxaura barbata ) and the seastar H. solaris are possibly extinct. The removal of large lobster and fish predators by artisanal fishing probably magnified impacts of the 1982/1983 El Niño through a cascade of indirect effects involving population expansion of grazing sea urchins. Marine protected areas with adequate enforcement are predicted to ameliorate but not eliminate ecosystem impacts caused by increasing thermal anomalies associated with El Niño and global climate change.

Somatic embryogenesis and plant regeneration in oil palm using the thin cell layer technique - Jonny E. Scherwinski-Pereira; Rodrigo S. da Guedes; Paulo César P. Fermino; Tatiane L. Silva; Frederico Henrique S. Costa (In Vitro Cellular & Developmental Biology - Plant, 2010)

Growth factor production from fibrin-encapsulated human keratinocytes - Cristian A. Acevedo; Rodrigo A. Somoza; Caroline Weinstein-Oppenheimer; Donald I. Brown; Manuel E. Young (Biotechnology Letters, 2010)

Calculation of the permeability and apparent permeability of three-dimensional porous media - Rodrigo P. A. Rocha; Manuel E. Cruz (Transport in Porous Media, 2010)

Preliminary recordings of blue whale ( Balaenoptera musculus ) vocalizations in the Gulf of Corcovado, northern Patagonia, Chile - Susannah J. Buchan; Luke E. Rendell; Rodrigo Hucke-Gaete (Marine Mammal Science, 2010)

Vulnerable island carnivores: the endangered endemic dwarf procyonids from Cozumel Island - Katherine W. McFadden; Denise García-Vasco; Alfredo D. Cuarón; David Valenzuela-Galván; Rodrigo A. Medellín; Matthew E. Gompper (Biodiversity and Conservation, 2010)

Murine interferon-gamma inducible protein-10 (IP-10) secreted by Lactococcus lactis chemo-attracts human CD3+ lymphocytes - Julio Villatoro-Hernandez; Alma Yolanda Arce-Mendoza; Adrian G. Rosas-Taraco; Sandra Cecilia Esparza-González; Santos Guzmán-López; Rodrigo E. Elizondo-Omaña; Arturo Chávez-Reyes; Odila Saucedo-Cárdenas; Roberto Montes de Oca Luna (Biotechnology Letters, 2009)

Distribution of Anthocyanins Delivered from a Bioadhesive Black Raspberry Gel Following Topical Intraoral Application in Normal Healthy Volunteers - Carlos M. Ugalde; Zhongfa Liu; Chen Ren; Kenneth K. Chan; Kapila A. Rodrigo; Yhonghua Ling; Peter E. Larsen; Guillermo E. Chacon; Gary D. Stoner; Russell J. Mumper; Henry W. Fields; Susan R. Mallery (Pharmaceutical Research, 2009)

On the Diversity of the Laccase Gene: A Phylogenetic Perspective from Botryosphaeria rhodina (Ascomycota: Fungi) and Other Related Taxa - Flávio J. D. Castilho; Rodrigo A. Torres; Aneli M. Barbosa; Robert F. H. Dekker; José E. Garcia (Biochemical Genetics, 2009)

Net ion fluxes in the facultative air-breather Hoplosternum littorale (tamoata) and the obligate air-breather Arapaima gigas (pirarucu) exposed to different Amazonian waters - Bernardo Baldisserotto; Carlos E. Copatti; Levy C. Gomes; Edsandra C. Chagas; Richard P. Brinn; Rodrigo Roubach (Fish Physiology and Biochemistry, 2008)

Localization of myosin-Va in subpopulations of cells in rat endocrine organs - Foued S. Espindola; Silmara R. Banzi; Luciana K. Calabria; Rodrigo J. Custódio; Ricardo A. Oliveira; Leandro D. Procópio; Andreia B. P. Lima; Jair P. Cunha-Junior; Milton V. Coelho; Iêda M. L. Guedes; Cláudia H. Pellizzon; Roy E. Larson; et al. (Cell and Tissue Research, 2008)

Do Rapoport's rule, the mid‐domain effect or the source–sink hypotheses predict bathymetric patterns of polychaete richness on the Pacific coast of South America? - Rodrigo A. Moreno; Marcelo M. Rivadeneira; Cristián E. Hernández; Sandra Sampértegui; Nicolás Rozbaczylo (Global Ecology and Biogeography, 2008)
Aim We evaluated the bathymetric gradient of benthic polychaete species richness from the Chilean coast, as well as its possible underlying causes. We tested three possible hypotheses to explain the richness gradient: (1) Rapoport's effect; (2) the mid‐domain effect (MDE); and (c) the source–sink hypothesis. Location South‐eastern Pacific coast of Chile. Methods The bathymetric gradient in richness was evaluated using the reported ranges of bathymetric distribution of 498 polychaete species, from the intertidal to abyssal zone ( c. 4700 m). Rapoport's effect was evaluated by examining the relationship between bathymetric mid‐point and bathymetric range extent, and species richness and depth. The MDE was tested using the Monte Carlo simulation program. The source–sink hypothesis was tested through nestedness analysis. Results Species richness shows significant exponential decay across the bathymetric gradient. The pattern is characterized by a high presence of short‐ranged species on the continental shelf area; while only a few species reach abyssal depths, and they tend to show extremely wide bathymetric ranges. Our simulation analyses showed that, in general, the pattern is robust to sampling artefacts. This pattern cannot be reproduced by the MDE, which predicts a parabolic richness gradient. Rather, results agree with the predictions of Rapoport's effect. Additionally, the data set is significantly nested at species, genus and family levels, supporting the source–sink hypothesis. Main conclusions The sharp exponential decay in benthic polychaete richness across the bathymetric gradient supports the general idea that abyssal environments should harbour fewer species than shallower zones. This pattern may be the result of colonization–extinction dynamics, characterized by abyssal assemblages acting as ‘sinks’ maintained mainly by shallower ‘sources’. The source–sink hypothesis provides a conceptual and methodological framework that may shed light on the search for general patterns of diversity across large spatial scales.

Identification of new ABA- and MEJA-activated sugarcane bZIP genes by data mining in the SUCEST database - Paulo Sérgio Schlögl; Fábio Tebaldi S. Nogueira; Rodrigo Drummond; Juliana M. Felix; Vicente E. De Rosa; Renato Vicentini; Adilson Leite; Eugênio C. Ulian; Marcelo Menossi (Plant Cell Reports, 2008)

Guarana (Paullinia cupana var. sorbilis), an anciently consumed stimulant from the Amazon rain forest: the seeded-fruit transcriptome - Paula C. S. Ângelo; Carlos G. Nunes-Silva; Marcelo M. Brígido; Juliana S. N. Azevedo; Enedina N. Assunção; Alexandra R. B. Sousa; Fernando J. B. Patrício; Mailson M. Rego; Jean C. C. Peixoto; Waldesse P. Oliveira; Danival V. Freitas; Elionor R. P. Almeida; et al. (Plant Cell Reports, 2008)

Single Molecule Spectroscopy of Poly 3-octyl-thiophene (P3OT) - Rodrigo E. Palacios; Paul F. Barbara (Journal of Fluorescence, 2007)

The relative importance of microbial and classical food webs in a highly productive coastal upwelling area - Cristian A. Vargas; Rodrigo A. Martínez; L. Antonio Cuevas; Marcelo A. Pavez; Carolina Cartes; Humberto E. GonzÁlez; RubÉn Escribano; Giovanni Daneri (Limnology and Oceanography, 2007)
We present an analysis of seasonal variations in the trophic pathways of carbon in a highly productive coastal upwelling region in the Humboldt current system off Chile. Seasonal changes in phytoplankton, protozooplankton, and bacteria biomass, along with rates of primary production (PP), bacterial growth, secondary production, vertical particle fluxes, and feeding by protozooplankton, omnivorous mesozooplankton, and carnivorous gelatinous zooplankton were determined from July 2004 to June 2005. Phytoplankton biomass and PP were maximal during spring/summer months, associated with upwelling episodes. Heterotrophic nanoflagellates (HNF) were the principal consumers of bacteria, removing >100% of their biomass daily. During autumn/winter, the protozooplankton grazed down a large fraction of HNF production (56% to 96% d −1 ). The mesozooplankton consumed 1–6% of the PP d −1 ; the different size fractions of copepods were omnivorous mostly during autumn/winter months, and ctenophores preyed most strongly on small copepods (0.5% to 5% d −1 ). A large part of the PP was channeled through the microbial food web, and only a small part directly to copepods via the herbivore food chain. The microbial food web transfers bacterial or small algal carbon to protozooplankton, and then to mesozooplankton, and a large percentage of this carbon is also available for the gelatinous predators. Because zooplankton are not able to feed on dissolved organic matter and cyanobacteria, the combined feeding activity of zooplankton either by direct (phytoplankton) or indirect (microbial) pathways increases the yield of PP reaching the zooplankton and, eventually, the upper trophic levels. Our findings suggest that the carrying capacity for larger omnivorous and carnivorous metazoans, and even for commercially exploitable pelagic fishes, might be considerably larger than that expected from a simple herbivore‐dominated food chain in coastal upwelling areas.

Formulation and In-Vitro and In-Vivo Evaluation of a Mucoadhesive Gel Containing Freeze Dried Black Raspberries: Implications for Oral Cancer Chemoprevention - Susan R. Mallery; Gary D. Stoner; Peter E. Larsen; Henry W. Fields; Kapila A. Rodrigo; Steven J. Schwartz; Qingguo Tian; Jin Dai; Russell J. Mumper (Pharmaceutical Research, 2007)

Angiotensin II modulates tyr-phosphorylation of IRS-4, an insulin receptor substrate, in rat liver membranes - Rodrigo S. Villarreal; Sergio E. Alvarez; Maximiliano Juri Ayub; Gladys M. Ciuffo (Molecular and Cellular Biochemistry, 2006)

Testing time–place learning in the cichlid fish Nile tilapia - Helton C. Delicio; Ana C. Luchiari; Rodrigo E. Barreto; Ana L. Marcondes (Journal of Ethology, 2006)

Patterns of endemism in south‐eastern Pacific benthic polychaetes of the Chilean coast - Rodrigo A. Moreno; Cristián E. Hernández; Marcelo M. Rivadeneira; Marcela A. Vidal; Nicolás Rozbaczylo (Journal of Biogeography, 2006)
Aim In this study we evaluate patterns of endemism for benthic polychaete species along the southeastern Pacific coast of Chile. Our goals were (1) to describe latitudinal gradients of endemism and identify areas of high endemism, (2) to evaluate the effect of biogeographical limits on endemism patterns, and (3) to evaluate indirectly the role played by evolutionary dynamics on patterns of endemism. Location South‐eastern Pacific coast of Chile, ranging from Arica (18° S) to Cape Horn (56° S). Methods We used a list of 178 species of endemic, shallow benthic polychaetes to evaluate patterns of endemism. Parsimony analysis of endemicity (PAE) and the endemism index (EI) were used to evaluate hierarchical relationships of endemism between different latitudinal bands, and to identify areas with high degrees of endemism and differences in endemism. We evaluated the effect of biogeographical limits on endemic polychaete fauna by testing for the existence of geometric constraints (mid‐domain effect). The role of evolutionary dynamics on latitudinal patterns of endemism was evaluated with nestedness analysis (NA) using the temperature index. Results The PAE analysis indicated two large, separate areas of endemism: (1) the northern area between 18° S and 38° S, and (2) the southern area between 39° S and 56° S. The endemism index showed a maximum value (32 species) around 39°–41° S. Species‐richness curves of each 3° band of latitude showed a clear mid‐domain effect (69%), but the two maximum points of species richness at mid‐latitudes (36° S to 38° S and 39° S to 41° S) did not correspond to the mid‐domain peak in species richness, presenting a greater number of species than expected by the mid‐domain effect. The nestedness analysis showed that the number of genera reaches a maximum of 70 at mid‐latitudes (36°–41° S), decreasing towards both the northern and southern areas. The spatial distribution of the entire data set of endemic species showed a nested pattern ( T ° = 24.5°, P Main conclusions Our results strongly support the existence of a latitudinal gradient of endemism for benthic polychaete species along the Chilean coast. The shape of this gradient is clearly non‐linear, with a marked peak of endemism occurring at mid‐latitudes (36°–41° S, endemism hotspot), which also corresponds to a peak in species richness. Furthermore, this hotspot is the midpoint separating two distinct areas of endemism to the north and south. We suggest that the observed pattern of endemism for benthic polychaete taxa of the Chilean coast can be explained by a combination of geometric constraints and historical mechanisms, such as the processes that affected the Chilean coast during the Neogene (e.g. ENSO, oxygen minimum zone, glaciations).

Pollination by Sexual Mimicry in Mormolyca ringens: A Floral Chemistry that Remarkably Matches the Pheromones of Virgin Queens of Scaptotrigona sp. - Adriana Flach; Anita J. Marsaioli; Rodrigo B. Singer; Maria Do Carmo E. Amaral; Cristiano Menezes; Warwick Estevam Kerr; Luciane G. Batista-Pereira; Arlene G. Corrêa (Journal of Chemical Ecology, 2006)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

The Chemistry of Pollination in Selected Brazilian Maxillariinae Orchids: Floral Rewards and Fragrance - Adriana Flach; Règine Carole Dondon; Rodrigo B. Singer; Samantha Koehler; Maria do Carmo E. Amaral; Anita J. Marsaioli (Journal of Chemical Ecology, 2004)

DIET OF SOUTH AMERICAN FUR SEALS ( ARCTOCEPHALUS AUSTRALIS ) IN ISLA DE LOBOS, URUGUAY - Daniel E. Naya; Matías Arim; Rodrigo Vargas (Marine Mammal Science, 2002)
A bstract The diet of Arctocephalus australis was studied through fecal analysis, from September of 1995 to May of 1998, in Isla de Lobos (35°01′50″S‐54°53′00″W), Uruguay. A total of 539 scats analyzed indicated that the weakfish ( Cynoscion guatucupa ), the cutlasfish ( Trichiurus lepturus ), the anchoveta ( Engraulis anchoita ), the anchovy ( Anchoa marinii ), and cephalopods were the main prey consumed by these fur seals. Prey richness was higher during January. The diet of A. australis varied between years, apparently related to changes in prey availability. C. guatucupa and E. anchoita decreased while T. lepturus and cephalopods increased from 1996 to 1998. South American fur seals fed on fish ranging in length from 5.4 to 104.8 cm and from 0.7 to 629.9 g in wet mass. However, the mean mass of the main items was never more than 200 g. Observations suggests that A. australis is a trophic generalist with the potential to prey on a wide range of species, although most of the diet is comprised of relatively few species. Fur seals and artisan fisheries both took C. guatucupa , with fur seals taking younger individuals (1–2 yr) than artisan fisheries (> 3 yr).

New Immunochromatographic Method for Rapid Detection of Rotaviruses in Stool Samples Compared with Standard Enzyme Immunoassay and Latex Agglutination Techniques - I. Wilhelmi; J. Colomina; D. Martín-Rodrigo; E. Roman; A. Sánchez-Fauquier (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Parasitoeds (Hym.: Aphelinidae) of three scale insects (Hom.: Diaspididae) in a citrus grove in valencia, spain - E. Rodrigo; P. Troncho; F. García-Marí (BioControl, 1996)